Negative electrode active material containing composite silicon particles, method for preparing same, and secondary battery containing negative electrode active material
By using composite silicon particles and carbon particles in the negative electrode active substance of lithium-ion batteries, the structural breakage problem caused by silicon volume expansion is solved, the durability and structural stability of the battery are improved, and the occurrence of lithium well phenomenon is reduced.
Patent Information
- Application Number
- CN202411204636.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-16
- Filing Date
- 2024-08-30
- Publication Date
- 2025-04-18
AI Technical Summary
The silicon negative electrode active substances are broken due to volume expansion in lithium-ion batteries, resulting in a decrease in battery capacity and shortening of life, and are prone to lithium well phenomenon.
Using a negative electrode active material containing composite silicon particles, the contact resistance and conductivity of the silicon particles are optimized to prevent damage caused by volume expansion by forming a nano-silicon particle coating layer and carbon particle filling on the surface of composite silicon particles.
It effectively prevents the destruction of silicon negative electrode active substances during charging and discharging, improves the durability and structural stability of the battery, reduces the occurrence of lithium well phenomena, and extends the battery life.
Smart Images

Figure CN119852346A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a negative electrode active material containing composite silicon particles, a preparation method thereof and a secondary battery containing the negative electrode active material. Background Art
[0002] Currently, the use of fossil energy has led to the generation of greenhouse gases such as carbon dioxide and the rise in global temperature, which is a very serious problem. Countries around the world are strengthening regulations on carbon dioxide emissions, and the introduction of electric vehicles powered by electricity is on a rapid increase in order to replace internal combustion engines powered by fossil fuels.
[0003] Unlike primary batteries that are discarded after being used once, secondary batteries used to power electric vehicles are the core components of electric vehicles that can be used repeatedly by charging. In addition to electric vehicles, secondary batteries are also used in various fields such as laptop computers (PCs), mobile devices, vertical take-off and landing aircraft used as a means of urban air mobility (UAM), and power storage systems. In recent years, with the development of industry, the demand for high-capacity, low-weight and high-efficiency secondary batteries has been increasing, and research on this has become more and more active.
[0004] Representative secondary batteries include lead-acid batteries, nickel-cadmium batteries, and lithium-ion batteries. Among them, lithium secondary batteries use lithium ions (Li + ) to generate electricity through the intercalation and deintercalation reactions. Due to its excellent lightness and high energy density, it is used in various fields such as electric vehicles.
[0005] A lithium secondary battery includes: a positive electrode and a negative electrode; an electrolyte disposed between the positive electrode and the negative electrode; and a separation membrane impregnated in the electrolyte, wherein the positive electrode and the negative electrode respectively include active materials formed on a current collector. The positive electrode active material of the lithium secondary battery includes lithium transition metal oxides, etc. The capacity and average voltage of the lithium ion battery are determined by the lithium ion source, and the negative electrode active material can first store the lithium ions released from the positive electrode and then release them to enable current to flow through an external circuit. The electrolyte has a mediating effect that enables lithium ions to move between the positive electrode and the negative electrode inside the battery.
[0006] Conventionally, crystalline carbon materials or amorphous carbon materials such as natural graphite and artificial graphite have been used as negative electrode active materials for lithium ion batteries.
[0007] Recently, silicon (Si) has attracted much attention as a negative electrode active material instead of carbon. In the past, graphite, which was used as a negative electrode active material, stored 1 lithium ion for every 6 carbon atoms, while each silicon (Si) atom can store 2 to 4.4 lithium ions. Therefore, compared with the previous graphite, it has the advantages of high energy density, theoretical capacity of about 4200mAh / g, and very fast charge and discharge speed, so it has attracted much attention.
[0008] However, silicon negative electrode active materials have the problem of low structural stability. In the process of storing lithium ions, the negative electrode material will increase in volume (lithiation). The volume of graphite increases by about 10-20%, while silicon (Si) has 4.4 lithium ions per silicon to form Li 22 Si5 alloy produces a large volume expansion of 2 to 5 times. In particular, the crystal fragmentation of silicon negative electrode active materials is high. Therefore, when lithium-ion batteries are repeatedly charged and discharged, the silicon-based negative electrode active materials will be pulverized (Pulverization, cracking and destruction of particles), and will be electrically separated from the current collector (Cu plate), resulting in a sharp decrease in energy capacity (capacity decay) and shortened life. Therefore, in order to prevent the fragmentation of negative electrode active materials caused by this silicon volume expansion, it is necessary to prepare negative electrode active materials.
[0009] On the other hand, it is known that in electrodes using silicon powder, as the contact between particles in the electrode weakens, the electron transfer path from the collector to the silicon particles is blocked, resulting in the lithium trap phenomenon. Lithium trap refers to the phenomenon that lithium ions and electrons embedded in the silicon active material during charging cannot escape during discharge. Therefore, the more lithium traps occur, the deeper the charging depth of the electrode after discharge will be. According to the relationship between the lithium traps generated by the cycle and the degradation of the electrode capacity, when the secondary battery is running, due to the large volume change in the initial cycle, cracks are generated on the surface of the active material. As these cracks accumulate, the particles break and the contact between particles in the electrode gradually weakens. In addition, due to the lithium traps, the reversible capacity is reduced.
[0010] Specifically, if silicon particles are broken, electrons cannot move in the broken sections, so the electron transfer resistance of the electrode increases. In particular, when the active material is fragmented due to repeated cracks, the detached active material becomes electrically isolated dead particles and causes an electrical short circuit. During the charging process when the silicon volume increases, the contact between particles becomes stronger, so no major problems occur, but during the discharge process when the volume decreases, the contact between particles becomes weaker and the electron transfer resistance increases significantly. Therefore, the lithium trap phenomenon occurs in which lithium ions and electrons embedded in silicon during charging cannot escape during discharge. When lithium traps occur during discharge, the interior of the silicon is already full of lithium, so in the next cycle of charging, the amount of lithium that can be embedded in the silicon is limited, so the reversible capacity that the silicon electrode can exhibit is reduced.
[0011] In order to prevent the breakage of silicon particles or negative electrode active materials caused by the volume expansion of silicon as described above, it is necessary to minimize the contact resistance of silicon particles, improve conductivity and durability, optimize the size of negative electrode active materials, and control the optimal number of silicon particles contained in the negative electrode active materials.
[0012] In addition, the problem with silicon negative electrode active materials is that the interface state between the negative electrode material (negative electrode active material) and the electrolyte and electrode changes during charging and discharging, so the efficiency drops rapidly. This is because when the battery is charged, if the silicon particles are broken due to the expansion of the negative electrode material, many lithium traps will be generated. In more detail, when the silicon particles expand, the solid electrolyte interphase (SEI) layer is easily destroyed by mechanical stress. When the destruction and regeneration process of the solid electrolyte interphase (SEI) layer is repeated during charging and discharging, the amount of solid electrolyte interphase (SEI) layer generated on the silicon peripheral surface will increase, which will reduce the spacing between particles, thereby weakening the electrical contact between particles and causing lithium traps. The solid electrolyte interphase (SEI) layer refers to a protective film formed on the peripheral surface of the active material when the electrolyte reacts with the active material of the electrode. Although the electron mobility is low, the lithium ion conductivity is high, and it is a channel for the movement of lithium ions between the electrolyte and the negative electrode material. The volume change of graphite is small and does not cause any problem to the solid electrolyte interface (SEI) layer. However, the volume of silicon expands to the extent of destroying the solid electrolyte interface (SEI) layer during charging. Therefore, the lithiation of silicon particles consumes lithium and produces gas, causing the solid electrolyte interface (SEI) layer to gradually harden and thicken. At the same time, lithium ions cannot approach the electrode, limiting the oxidation-reduction reaction of lithium, which causes the problem of shortened battery life.
[0013] Therefore, research is actively being conducted to improve the structural stability of silicon negative electrode active materials in order to prevent the negative electrode active materials from being broken due to the volume expansion of silicon during charge and discharge of secondary batteries.
[0014] In addition, in order to prevent the destruction of the negative electrode active material and the decrease in capacity caused by the volume expansion of silicon during charge and discharge, it is necessary to optimize the size of the negative electrode active material, and research is being conducted to control the optimal number of silicon particles contained in the negative electrode active material.
[0015] In addition, research is being conducted to prevent the destruction of negative electrode active materials and the decrease in capacity caused by the volume expansion of silicon during charge and discharge.
[0016] The background technology related to the present invention is disclosed in Korean Patent Gazette No. 10-2185490 (announcement date: December 2, 2020, invention name: Negative electrode active material for non-aqueous electrolyte secondary battery containing silicon oxide composite and preparation method thereof). Summary of the invention
[0017] Technical issues
[0018] An object of the present invention is to provide a negative electrode active material containing composite silicon particles which minimize contact resistance, are excellent in ion conductivity and electrical conductivity, and can prevent lithium traps from occurring during discharge of a secondary battery.
[0019] Another object of the present invention is to provide a negative electrode active material containing composite silicon particles, which has excellent durability and structural stability, and prevents silicon escape / destruction caused by volume expansion of silicon particles caused by the embedding of lithium ions during charge and discharge, has excellent effects in preventing battery short circuit and reversible capacity, and minimizes resistance increase and energy capacity reduction.
[0020] Another object of the present invention is to provide a negative electrode active material containing composite silicon particles, which has excellent electrical properties and has the characteristics of high capacity, high output and long life, and excellent reversibility and initial efficiency.
[0021] Another object of the present invention is to provide a negative electrode active material containing composite silicon particles, which minimizes the destruction of the negative electrode active material and the reduction in energy capacity caused by the volume expansion of silicon particles caused by lithium ion insertion during charge and discharge.
[0022] Another object of the present invention is to provide a negative electrode active material containing composite silicon particles, which optimizes the number of silicon particles inside the negative electrode active material, prevents the destruction of the negative electrode active material caused by the volume expansion of the silicon particles during charging, and has excellent electrical properties.
[0023] Another object of the present invention is to provide a negative electrode active material containing composite silicon particles, which prevents the destruction of the negative electrode active material caused by the volume expansion of the composite silicon particles by optimizing the number of primary particles filled inside the secondary particles of the negative electrode active material and the number of composite silicon particles filled inside the primary particles, and has excellent electrical properties.
[0024] Another object of the present invention is to provide a negative electrode active material containing composite silicon particles, which can be contained in a high content when preparing a negative electrode for a secondary battery.
[0025] Another object of the present invention is to provide a negative electrode active material containing composite silicon particles having excellent productivity and economic efficiency.
[0026] Another object of the present invention is to provide a method for preparing the negative electrode active material.
[0027] Another object of the present invention is to provide a secondary battery including the negative electrode active material.
[0028] Solutions to the problem
[0029] One aspect of the present invention relates to a negative electrode active material. In a specific example, the negative electrode active material includes: a first hollow core having a first hollow portion formed therein; composite silicon particles filled in the first hollow portion and including nano silicon particles having a first coating layer formed on the surface; carbon particles filled in the first hollow portion; and a second coating layer formed on the outer peripheral surface of the first hollow core, the carbon particles including graphene and graphite, the first coating layer including a middle coating layer, the second coating layer including one or more of a hard coating layer, a middle coating layer and a soft coating layer, the hardness of the hard coating layer is higher than that of the middle coating layer, the hardness of the middle coating layer is higher than that of the soft coating layer, and the hardness of the first hollow core and the second coating layer are different.
[0030] In another specific example of the present invention, the negative electrode active material includes: primary particles, including a first hollow core forming a first hollow portion and composite silicon particles and carbon particles respectively filled in the first hollow portion; and secondary particles, including a second hollow core forming a second hollow portion and one or more primary particles filled in the second hollow portion, the composite silicon particles include nano-silicon particles having a first coating layer formed on the surface, the carbon particles include graphene and graphite, the first coating layer includes a middle coating layer, and the first hollow core and the second hollow core have different hardnesses.
[0031] In a specific example, the average sizes of the graphene and graphite may be 10 to 5000 nm, respectively.
[0032] In a specific example, the graphene may include a layer structure of 1 to 10 layers, and the maximum peak intensity of the (002) plane / the maximum peak intensity of the (101) plane of the graphene in an X-ray diffraction (XRD) spectrum may be 50 or more.
[0033] In one embodiment, the D band peak intensity (I D / I G ) can be less than 0.65.
[0034] In one embodiment, the 2D band peak intensity (I) of the graphene relative to the G band peak intensity in the Raman spectrum is 2D / I G ) can be 0.35~0.65.
[0035] In one specific example, the graphene has a 2D band at 2680-2725 cm in the Raman spectrum. -1 There may be a peak in the wavenumber range.
[0036] In a specific example, in an X-ray diffraction (XRD) spectrum of the negative electrode active material, the maximum peak intensity of the (002) plane of the graphite / the first peak intensity of the (111) plane of the composite silicon particles may be 1.5 to 2.2.
[0037] In a specific example, in an X-ray diffraction (XRD) spectrum of the negative electrode active material, the maximum peak intensity of the (002) plane of the graphite / the second peak intensity of the (220) plane of the composite silicon particles may be 3.5 to 4.5.
[0038] In a specific example, the number (n) of composite silicon particles filled in the first hollow portion may satisfy the condition of the following formula 1:
[0039] Formula 1:
[0040] (In the above formula 1, d is the relative diameter of the expanded composite silicon particle derived from the following formula 1-1, and q is the relative diameter of the expanded composite silicon particle at the center of the first hollow portion derived from the following formula 1-2)
[0041] Formula 1-1: d = r' / R
[0042] (In the above formula 1-1, R is the radius of the first hollow portion, and r' is the radius of the expanded composite silicon particle,
[0043] r'=1.2599*a+b (a is the radius of the composite silicon particle, b is the thickness of the first coating layer)
[0044] Formula 1-2: q = 1-2*d
[0045] (In the above formula 1-2, the d is as defined above).
[0046] In a specific example, the negative electrode active material includes first composite silicon particles and second composite silicon particles having radii r1 and r2, respectively, and the number of particles (n1 and n2) of the first composite silicon and the second composite silicon filled in the first hollow portion may satisfy the condition of the following formula 2:
[0047] Formula 2:
[0048] (In the above formula 2, r1' and r2' are the radii of the first expanded composite silicon particle and the second expanded composite silicon particle, respectively, and R is the radius of the first hollow portion,
[0049] The r1' and r2' are 1.2599*a1+b1 and 1.2599*a2+b2 respectively (the a1 and b1 are the radius of the first nano-silicon particle and the thickness of the first coating layer, and the a2 and b2 are the radius of the second nano-silicon particle and the thickness of the first coating layer).
[0050] In a specific example, the secondary particles include primary particles (1) and primary particles (2) having radii c1 and c2, respectively, and the number of primary particles (1) and primary particles (2) filled in the second hollow portion can satisfy the condition of the following formula 3:
[0051] Formula 3:
[0052] (In the above formula 3, c1 and n3 are the radius and number of primary particles (1), c2 and n4 are the radius and number of primary particles (2), and d is the radius of the second hollow portion).
[0053] In a specific example, the first coating layer may further include a silicon carbide (SiC) layer formed between the nano-silicon particles and the middle coating layer.
[0054] In a specific example, the average particle size of the negative electrode active material may be greater than 1.5 μm and less than 50 μm.
[0055] In a specific example, the average diameter of the first hollow portion may be 1.5 to 20 μm, the average particle size of the composite silicon particles may be 50 to 1500 nm, and the number of the composite silicon particles filled in the first hollow portion may be 5 to 12,000.
[0056] In a specific example, the particle density of the negative electrode active material may be 1 to 3 g / cm 3, the thickness of the first hollow core may be 5 to 300 nm, the thickness of the first coating layer may be 3 to 110 nm, and the thickness of the second coating layer may be 5 to 100 nm.
[0057] In one embodiment, the hard coating layer may have a pencil hardness of 4H or more and a density of more than 1.8 g / cm 3 The pencil hardness of the middle coating layer may be greater than 2H and less than 4H, and the density may be greater than 1.5 g / cm 3 And 1.8g / cm 3 The pencil hardness of the soft coating layer may be less than 2H and the density may be 1.5 g / cm 3 the following.
[0058] In a specific example, the negative electrode active material may include 25 to 80 wt % of composite silicon particles, 1 to 15 wt % of carbon particles, 1 to 40 wt % of the first hollow core, and 1 to 40 wt % of the second coating layer.
[0059] Another aspect of the present invention relates to the method for preparing the negative electrode active material. In a specific example, the method for preparing the negative electrode active material includes: a step of preparing composite silicon particles; a step of preparing a primary dry powder by drying a mixed slurry containing the composite silicon particles, carbon particles and a solvent; a step of preparing a first intermediate using the primary dry powder and a first coating material; and a step of forming a second coating layer on the outer peripheral surface of the first intermediate to prepare a second intermediate, the carbon particles include graphene and graphite, the first coating material includes one or more of a hard coating material, a middle coating material and a soft coating material, and the second intermediate includes: a first hollow core having a first hollow portion formed therein; composite silicon particles and carbon particles filled in the first hollow portion, and including nano silicon particles having a first coating layer formed on the surface; and a second coating layer formed on the outer peripheral surface of the first hollow core, the first coating layer includes a middle coating layer, the second coating layer includes one or more of a hard coating layer, a middle coating layer and a soft coating layer, the hardness of the hard coating layer is higher than that of the middle coating layer, the hardness of the middle coating layer is higher than that of the soft coating layer, and the hardness of the first hollow core and the second coating layer are different.
[0060] In another specific example of the present invention, the method for preparing a negative electrode active material includes: a step of preparing composite silicon particles; a step of preparing a primary dry powder by drying a mixed slurry containing the composite silicon particles, carbon particles, a first coating material and a solvent; a step of preparing a first mixture containing the primary dry powder and a second coating material; and a step of using the first mixture and a third coating material to prepare a first intermediate, the carbon particles include graphene and graphite, the first coating material and the second coating material respectively include one or more of a hard coating material and a soft coating material, the third coating material includes one or more of a hard coating material, a middle coating material and a soft coating material, the first intermediate includes: primary particles, including a first hollow core formed with a first hollow portion and composite silicon particles and carbon particles filled in the first hollow portion; and secondary particles, including a second hollow core formed with a second hollow portion and one or more of the primary particles filled in the second hollow portion, the composite silicon particles include nano silicon particles with a first coating layer formed on the surface, the first coating layer includes a middle coating layer, and the hardness of the first hollow core and the second hollow core is different.
[0061] In a specific example, the step of preparing composite silicon particles includes: a step of preparing a first composition comprising nano-silicon particles and carbon particles; a step of arranging the first composition in a cavity, heating the interior of the cavity to 900-1100°C, and reducing the pressure to below normal pressure; a step of allowing hydrocarbon gas and buffer gas to flow into the reduced pressure cavity to contact the first composition; and a step of gradually increasing the pressure inside the cavity for heat treatment while maintaining the increased temperature, wherein the carbon particles include graphene and graphite.
[0062] In one embodiment, the graphene may be formed by a step including milling the graphite.
[0063] Another aspect of the present invention relates to a secondary battery including the negative electrode active material. In a specific example, the secondary battery includes: a positive electrode; a negative electrode; and an electrolyte formed between the positive electrode and the negative electrode, wherein the negative electrode includes the negative electrode active material.
[0064] Effects of the Invention
[0065] The negative electrode active material of the present invention minimizes contact resistance by including composite silicon particles and carbon particles, has excellent ion conductivity and electrical conductivity, prevents the generation of lithium traps during the discharge process of the secondary battery, has excellent durability and structural stability, prevents silicon from being released / destroyed due to the volume expansion of silicon particles caused by lithium ion insertion during charge and discharge, has excellent effects of preventing battery short circuit and preventing reversible capacity, minimizes resistance increase and energy capacity reduction, minimizes the destruction of the negative electrode active material and the reduction of energy capacity caused by the volume expansion of silicon particles caused by lithium ion insertion during charge and discharge, and optimizes the number of silicon particles inside the negative electrode active material to prevent the destruction of the negative electrode active material caused by the volume expansion of silicon particles during charging, and has excellent electrical characteristics, optimizes the number of primary particles filled in the secondary particles of the negative electrode active material and the number of composite silicon particles filled in the primary particles to prevent the destruction of the negative electrode active material caused by the volume expansion of the composite silicon particles, and has excellent electrical characteristics, and has high capacity, high output and long life characteristics, excellent reversibility and initial efficiency, can be included in a high content when preparing the negative electrode of the secondary battery, and has excellent productivity and economy. BRIEF DESCRIPTION OF THE DRAWINGS
[0066] Figure 1 A negative electrode active material according to a specific example of the present invention is shown.
[0067] Figure 2 Composite silicon particles according to a specific example of the present invention are shown.
[0068] Figure 3 A negative electrode active material according to another specific example of the present invention is shown.
[0069] Figure 4 1 is a graph showing the change in pressure inside a cavity over time when preparing composite silicon particles according to a specific example of the present invention.
[0070] Figure 5 Part (a) is a graph showing the change in X-ray diffraction (XRD) peaks of Example 1 with graphite milling time, Figure 5 Part (b) is a graph showing the change in crystallinity of Example 1 according to X-ray diffraction (XRD) with graphite milling time.
[0071] Figure 6 Part (a) is a graph showing the change in the X-ray diffraction (XRD) peak of the graphite (002) crystal plane with milling time in Example 1, Figure 6 Part (b) is a graph showing the change in the X-ray diffraction (XRD) peak of the graphite (101) crystal plane according to the milling time in Example 1.
[0072] Description of Reference Numerals
[0073] 10: Composite silicon particles 11: Nano silicon particles
[0074] 12: First coating layer 13: Silicon carbide layer
[0075] 14: Middle coating layer 16: Nano carbon particles
[0076] 20: first hollow core 22: first hollow portion
[0077] 24: Second coating layer 30: Second hollow core
[0078] 32: Second hollow part 100, 200: Negative electrode active material DETAILED DESCRIPTION
[0079] When describing the present invention, if it is determined that a detailed description of a related known technology or configuration may unnecessarily obscure the gist of the present invention, the detailed description will be omitted.
[0080] Furthermore, the terms described below are defined in consideration of the functions in the present invention, and may vary depending on the intentions or practices of the user or operator, and therefore, their definitions should be based on the entire content of this specification for explaining the present invention.
[0081] Negative electrode active material containing composite silicon particles
[0082] Another aspect of the present invention relates to a negative electrode active material (a negative electrode active material containing composite silicon particles or a silicon-carbon composite negative electrode active material).
[0083] First specific example
[0084] the following Figure 1 A negative electrode active material according to a specific example of the present invention is shown. Figure 1 The negative electrode active material 100 includes: a first hollow core 20, having a first hollow portion 22 formed therein; composite silicon particles 10, filled in the first hollow portion 22, and including nano silicon particles 11 having a first coating layer 12 formed on the surface; carbon particles 16, filled in the first hollow portion 22; and a second coating layer 24, formed on the outer peripheral surface of the first hollow core 20, wherein the first coating layer 12 includes a middle coating layer 14.
[0085] The second coating layer 24 includes one or more of a hard coating layer, a middle coating layer and a soft coating layer. The hardness of the hard coating layer is higher than that of the middle coating layer, and the hardness of the middle coating layer is higher than that of the soft coating layer. The first hollow core and the second coating layer have different hardnesses.
[0086] In a specific example, the negative electrode active material may include 25 to 80 wt % of composite silicon particles, 1 to 10 wt % of carbon particles, 1 to 40 wt % of the first hollow core, and 1 to 40 wt % of the second coating layer.
[0087] In a specific example, the particle density of the negative electrode active material may be 1 to 3 g / cm 3 Under the above conditions, lightness and output can be excellent.
[0088] In a specific example, the average particle size of the negative electrode active material may be more than 1.5 μm and less than 50 μm. Under the above conditions, under the conditions of the average particle size, it can have excellent high capacity, high output characteristics and structural stability, and can prevent the destruction of the negative electrode active material caused by the volume expansion of the composite silicon particles (or nano silicon particles) during charge and discharge, and can have excellent long life characteristics. For example, it can be 1.5 to 45 μm, 5 to 30 μm, 5 to 25 μm, 10 to 20 μm, 4 to 20 μm or 5 to 20 μm.
[0089] (1) First hollow core: refer to the above Figure 1 The first hollow core 20 has a first hollow portion 22 formed therein, and the composite silicon particles 10 and the carbon particles 16 are filled in the first hollow portion 22. The first hollow core may be spherical or elliptical. For example, it may be spherical.
[0090] In a specific example, the average diameter of the first hollow portion can be 1.5 to 20 μm (radius 0.75 to 10 μm). Under the above conditions, the destruction of the negative electrode active material caused by the volume expansion of the composite silicon particles during charge and discharge can be prevented, and excellent long life characteristics can be obtained. For example, the average diameter can be 2 to 20 μm, 3 to 20 μm, 6 to 20 μm, or 10 to 20 μm.
[0091] In a specific example, the thickness of the first hollow core may be 5 to 300 nm. Under the above conditions, the hardness and mechanical strength are excellent, and the rupture or damage of the negative electrode active material can be prevented even when the composite silicon particles expand. For example, it may be 5 to 300 nm, 5 to 250 nm, 5 to 200 nm, 10 to 200 nm, or 10 to 50 nm.
[0092] The hardness of the first hollow core is different from that of the second coating layer. Under the above conditions, the first hollow core and the second coating layer have an excellent buffering effect on the expansion of the composite silicon particles during the charge and discharge process of the secondary battery, thereby preventing the destruction and rupture of the negative electrode active material and having excellent long life characteristics.
[0093] For example, the density, specific surface area, and electrical conductivity of the first hollow core may be different from those of the second coating layer.
[0094] In a specific example, the density of the first hollow core can be 1.8 to 2.5 g / cm 3 Under the above conditions, the hollow core can have excellent lightness and structural stability. For example, the density of the first hollow core can be 1.8 to 2.1 g / cm 3 .
[0095] In another specific example, the density of the first hollow core may be less than 1.8 g / cm 3 Under the above conditions, the hollow core can have excellent lightness and structural stability. For example, the density of the first hollow core can be 0.3 to 1.7 g / cm 3 .
[0096] In a specific example, the specific surface area (BET) of the first hollow core can be 100 m 2 Under the above conditions, the structure can be excellently stable.
[0097] In another embodiment, the specific surface area (BET) of the first hollow core may exceed 100 m 2 / g. Under the above conditions, it can have excellent structural stability. For example, the specific surface area (BET) can be 110 to 500 m 2 / g.
[0098] In a specific example, the purity (impurity content) of the first hollow core may be less than 100 ppm. Under the above conditions, the negative electrode active material may have excellent conductivity.
[0099] In another specific example, the purity (impurity content) of the first hollow core may be greater than 500 ppm. Under the above conditions, the negative electrode active material may have excellent conductivity. For example, the impurity content may be 500 to 3000 ppm.
[0100] In a specific example, the electrical conductivity (resistivity) of the first hollow core may be 3 to 5 μΩ·m. Under the above conditions, the negative electrode active material may have excellent electrical conductivity.
[0101] In another specific example, the electrical conductivity (resistivity) of the first hollow core may be greater than 20 μΩ·m. Under the above conditions, the negative electrode active material may have excellent electrical conductivity. For example, the electrical conductivity may be 20 to 80 μΩ·m.
[0102] In a specific example, the pencil hardness of the first hollow core measured according to ISO 15184 may be 4H or more. Under the above conditions, the durability and strength of the hollow core are excellent, and lithium ions are embedded in the composite silicon particles, thereby preventing the hollow core (or negative electrode active material) from being broken or damaged during expansion. For example, the pencil hardness of the first hollow core may be 4H to 6H.
[0103] In another specific example, the pencil hardness of the first hollow core measured according to ISO 15184 may be less than 4H. Under the above conditions, the first hollow core has excellent flexibility, and lithium ions are embedded in the composite silicon particles, thereby having an excellent effect of preventing the first hollow core (or negative electrode active material) from being broken or damaged during expansion. For example, the pencil hardness of the first hollow core may be B to 3H. In another specific example, the pencil hardness of the first hollow core may be 2H to 3H.
[0104] In a specific example, the first hollow core may be included in an amount of 1 to 40% by weight relative to the total weight of the negative electrode active material. When included in the above range, the negative electrode active material may have excellent durability and structural stability while having excellent electrical properties. For example, the amount may be 1 to 30% by weight, 1 to 25% by weight, 2 to 20% by weight, or 2 to 15% by weight.
[0105] (2) Composite silicon particles: Figure 2 FIG. 2 shows a composite silicon particle according to a specific example of the present invention. Figure 2 The composite silicon particle 10 includes: a nano-silicon particle 11 ; and a first coating layer 12 formed on the outer peripheral surface of the nano-silicon particle 11 .
[0106] In a specific example, the composite silicon particles may be spherical, polyhedral, elliptical or irregular in shape. For example, they may be spherical.
[0107] In one specific example, the average particle size of the composite silicon particles can be 50 to 1500 nm. Under the above conditions, the high capacity and high output characteristics of the composite silicon particles can be ensured, and the rupture or destruction of the negative electrode active material during the expansion of the composite silicon particles can be prevented, thereby having an excellent long life effect. In another specific example, the average particle size (d50) of the composite silicon particles can be less than 1300 nm, for example, the average particle size (d50) of the composite silicon particles can be 5 nm to 1300 nm, 10 nm to 1200 nm, 20 nm to 1200 nm, 25 nm to 1200 nm, 50 nm to 1100 nm, 300 nm to 1100 nm, 500 nm to 1100 nm or 900 nm to 1100 nm.
[0108] In one specific example, the composite silicon particles may be included in an amount of 25 to 80% by weight relative to the total weight of the negative electrode active material. Within the above content range, the composite silicon particles may have excellent miscibility and durability, and may have excellent high capacity and high output characteristics. For example, the composite silicon particles may be included in an amount of 25 to 70% by weight. In another specific example, the composite silicon particles may be included in an amount of 25 to 75% by weight, 25 to 65% by weight, 25 to 60% by weight, 25 to 50% by weight, 25 to 45% by weight, or 30 to 45% by weight.
[0109] (2-1) Nano silicon particles: In order to ensure high capacity and high output characteristics, the nano silicon particles are included. In a specific example, the nano silicon particles may be spherical, polyhedral, elliptical or irregular. For example, they may be spherical.
[0110] In one specific example, the nano-silicon particles may exhibit higher crystalline properties.
[0111] In a specific example, the average particle size of the nano silicon particles can be 45 to 1450 nm. Under the above conditions, the high capacity and high output characteristics of the nano silicon particles can be ensured, and the rupture or destruction of the negative electrode active material during the expansion of the nano silicon particles can be prevented, thereby having an excellent long life effect. For example, it can be 50 to 1300 nm or 80 to 990 nm.
[0112] In addition, it is also very important to control the maximum value (Dmax) of the average particle size of the nano silicon particles. For example, the Dmax particle size can be below 1450nm, below 1400nm, below 1000nm, or 100-1000nm. Preferably, it can be in the range of 320nm to 360nm. More preferably, it can be in the range of 300nm to 340nm. The lower the Dmax value, the higher the viscosity of the nano silicon slurry can be, and the viscosity of the nano silicon slurry can be controlled below 6500cps (25°C).
[0113] (2-2) First coating layer: refer to Figure 2 , the first coating layer 12 includes a middle coating layer 14 formed on the outer peripheral surface of the nano silicon particle 11. Under the above conditions, excellent conductivity and high output characteristics can be obtained.
[0114] In a specific example, the thickness of the first coating layer can be 3 to 110 nm. Under the above conditions, it has excellent conductivity and high output characteristics, and excellent durability, thereby preventing the destruction of the negative electrode active material during the expansion of the composite silicon particles caused by the embedding of lithium ions during the charge and discharge of the secondary battery, and therefore, it can have excellent long life characteristics. For example, the thickness of the first coating layer can be 5 to 100 nm, 5 to 80 nm, 5 to 60 nm, 5 to 50 nm, 5 to 30 nm or 5 to 20 nm.
[0115] The medium coating layer may be formed by heat treating one or more of a hydrocarbon gas and carbon black. For example, the hydrocarbon gas may include methane (CH4), ethane (C2H6), propane (C3H8), butane (C4H 10 ), pentane (C5H 12 )
[0116] In a specific example, the pencil hardness of the middle coating layer measured according to ISO 15184 may be greater than 2H and less than 4H. Under the above conditions, the cracking or destruction of the negative electrode active material caused by the volume expansion of the nano silicon particles can be prevented, thereby having excellent long life characteristics. For example, the pencil hardness may be 2.5H to 3H.
[0117] In a specific example, the thickness of the middle coating layer can be 2 to 100 nm. Under the above conditions, the rupture or destruction of the negative electrode active material caused by the expansion of the composite silicon particles can be prevented, and excellent high output and conductivity can be achieved. For example, the thickness of the middle coating layer can be 4 to 80 nm, 4 to 70 nm, 5 to 60 nm, 5 to 40 nm, 5 to 30 nm, or 5 to 20 nm.
[0118] In one embodiment, the density of the middle coating layer can be more than 1.5 g / cm 3 And 1.8g / cm 3 Under the above conditions, the coating layer can have excellent lightness and structural stability. For example, the density of the coating layer can be more than 1.5 g / cm 3 And 1.7g / cm 3 the following.
[0119] In a specific example, the specific surface area (BET) of the middle coating layer can be 100 to 200 m 2 Under the above conditions, the structure can be excellently stable.
[0120] In a specific example, the purity (impurity content) of the middle coating layer may be less than 500 ppm. Under the above conditions, the negative electrode active material may have excellent conductivity.
[0121] In a specific example, the electrical conductivity (resistivity) of the middle coating layer may be 20 to 40 μΩ·m. Under the above conditions, the negative electrode active material may have excellent electrical conductivity.
[0122] For example, the first coating layer may further include a silicon carbide (SiC) layer formed between the nano-silicon particles and the middle coating layer. Figure 2 , the first coating layer 12 may include a silicon carbide (SiC) layer 13 and a middle coating layer 14 sequentially formed on the outer peripheral surface of the nano silicon particles 11. Under the above conditions, it has excellent conductivity and high output characteristics, and excellent durability, thereby preventing the destruction of the negative electrode active material during the expansion of the composite silicon particles caused by the insertion of lithium ions during the charge and discharge of the secondary battery, and therefore, it can have excellent long life characteristics.
[0123] The silicon carbide layer improves the ion conductivity and electrical conductivity of the composite silicon particles while ensuring a stable ion charge and discharge channel, thereby having a low contact resistance and preventing the destruction of the composite silicon particles caused by the volume expansion of the nano silicon particles.
[0124] In a specific example, the thickness of the silicon carbide (SiC) layer may be 1 to 10 nm. Under the above conditions, the durability, ion conductivity and electrical conductivity are excellent, and the contact resistance may be low. For example, the thickness may be 1 to 10 nm, 2 to 10 nm, 3 to 10 nm, 3 to 8 nm or 3 to 5 nm.
[0125] In a specific example, the hardness of the silicon carbide layer may be higher than that of the middle coating layer. Under the above conditions, the electrical conductivity is excellent, and the destruction of the composite silicon particles caused by the volume expansion of the nano silicon particles can be prevented.
[0126] For example, the pencil hardness of the silicon carbide layer measured according to ISO 15184 may be 7H or more. For example, it may be 8H or more, or 10H or more, or 8H to 10H.
[0127] In a specific example, the composite silicon particles can contain the first coating layer and nano silicon particles in a weight ratio of 1:0.5 to 1:6. When contained in the above range, the conductivity is excellent, the rupture and destruction of the negative electrode active material caused by the expansion of the composite silicon particles can be prevented, and the capacity reduction can be minimized, thereby having excellent long-life characteristics. For example, it can be contained in a weight ratio of 1:0.5 to 1:5, a weight ratio of 1:0.5 to 1:4, a weight ratio of 1:1 to 1:3.5, a weight ratio of 1:1 to 1:3, a weight ratio of 1:1 to 1:2, or a weight ratio of 1:1.5 to 1:2.
[0128] In a specific example, the 2θ value of the composite silicon particles in the X-ray diffraction (XRD) spectrum may have an effective peak in one or more regions of 26-30°, 47-50°, 53-58°, 68-72°, 74-78° and 88-90°. Under the above conditions, the low contact resistance, high capacity and high output characteristics of the composite silicon particles can be ensured, and the cracking phenomenon of the nano-silicon particles in the composite silicon particles during charging and discharging can be significantly reduced.
[0129] For example, the composite silicon particles may have effective peaks in the diffraction angle (2θ) values in the X-ray diffraction spectrum in the regions of 27-30°, 46-50°, 56-57°, 68-69.5°, 75-76°, and 88-90°, respectively. Under the above conditions, the low contact resistance, high capacity, and high output characteristics of the composite silicon particles can be ensured, and the cracking phenomenon of the nano-silicon particles in the composite silicon particles during charge and discharge can be significantly reduced.
[0130] For example, the composite silicon particles may have effective peaks in the diffraction angle (2θ) values of 28-29.5°, 47-49°, 56-57°, 68-69.5°, 75-76° and 88-90°, respectively, and the effective peaks may represent (111), (220), (311), (400), (331), and (442) crystal planes, respectively.
[0131] For example, the composite silicon particles are used In the X-ray diffraction (XRD) spectrum of CuKα rays, the diffraction angle (2θ) value on the (111) plane can have effective peaks in the range of 26 to 30° and the diffraction angle (2θ) value on the (220) plane can have effective peaks in the range of 46 to 50°.
[0132] For example, in the X-ray diffraction spectrum, the composite silicon particles may have effective peaks at diffraction angles (2θ) values on the (111) plane in the range of 28 to 29.5° and at diffraction angles (2θ) values on the (220) plane in the range of 47 to 49°.
[0133] For example, when using In the X-ray diffraction (XRD) spectrum of CuKα rays and measuring 2θ at 10-70° with a step size of 0.01°, the diffraction angle (2θ) value of the composite silicon particles on the (111) plane can have effective peaks in the region of 26-30° and the diffraction angle (2θ) value on the (220) plane can have effective peaks in the region of 46-50°.
[0134] In one embodiment, the composite silicon particles are used on the (111) and (220) planes. The full width at half maximum (FWHM) of the X-ray diffraction angle (2θ) of CuKα rays can be in the range of 0.40° to 0.80°, more preferably, in the range of 0.52° to 0.68° or 0.59° to 0.71°. Under the above conditions, the low contact resistance, high capacity and high output characteristics of the composite silicon particles can be ensured, and the cracking phenomenon of the silicon particles during charging and discharging can be significantly reduced.
[0135] The number of composite silicon particles filled in the first hollow part
[0136] In a specific example, the composite silicon particles can be filled in the first hollow part in a hexagonal close packing (HCC) or face-centered cubic (FCC) structure. The maximum number of expanded composite silicon particles that can be filled into the hollow part can be calculated using the above method.
[0137] The number of composite silicon particles filled in the first hollow portion may be set such that the total volume of expanded composite silicon particles formed by lithium ions being intercalated into the composite silicon particles is equal to or smaller than the volume of the first hollow portion.
[0138] For example, when the volume of the composite silicon particles (nano silicon particles) expands by 2 times, it can be assumed that the first hollow portion is filled with a hexagonal close packing (HCC) or a face-centered cubic (FCC) structure for calculation.
[0139] For example, the radius k' of the expanded nano-silicon particle whose volume is expanded by 2 times by a spherical nano-silicon particle with a radius of k can be 1.2599*k. 3 =2*(4 / 3)*π*(k) 3 The radius k' of the expanded nano-silicon particle is derived from the relationship 3 √4)*k≈1.2599*k).
[0140] In a specific example, in the case of a composite silicon particle with a radius of a and a thickness of b of the first coating layer, the radius r' of the expanded composite silicon particle whose volume expands by 2 times may be r'=1.2599*a+b.
[0141] In addition, the number of composite silicon particles filled inside the hollow portion can be derived by taking into account the particle filling rate in the hexagonal closest packing or face-centered cubic structure (π*(√3 / 2)≈0.7405).
[0142] In one specific example, the radius (r') of the composite silicon particle with a radius (r) of 500 nm when expanded twice may be about 630 nm. In another specific example, the radius (r') of the composite silicon particle with a radius (r) of 510 nm when expanded twice may be about 643 nm.
[0143] In a specific example, the number (n) of composite silicon particles filled in the first hollow portion may satisfy the condition of the following formula 1:
[0144] Formula 1:
[0145] (In the above formula 1, d is the relative diameter of the expanded composite silicon particle derived from the following formula 1-1, and q is the relative diameter of the expanded composite silicon particle at the center of the first hollow portion derived from the following formula 1-2)
[0146] Formula 1-1: d = r' / R
[0147] (In the above formula 1-1, R is the radius of the first hollow portion, r' is the radius of the expanded composite silicon particle, and r'=1.2599*a+b (a is the radius of the composite silicon particle, and b is the thickness of the first coating layer))
[0148] Formula 1-2: q = 1-2*d
[0149] (In the above formula 1-2, the d is as defined above).
[0150] When the number of composite silicon particles filled in the first hollow portion is set under the condition of Formula 1, rupture or destruction of the first hollow core (or the negative electrode active material) due to expansion of the composite silicon particles can be prevented.
[0151] In a specific example, the average diameter of the first hollow portion can be 1.5 to 20 μm, and the average particle size of the composite silicon particles can be 50 to 1500 nm. Under the conditions of the average diameter of the first hollow portion and the average particle size of the composite silicon particles, the number of composite silicon particles can be easily controlled, the destruction of the hollow core caused by the expansion of the composite silicon particles can be prevented, and the negative electrode active material can have excellent high capacity and high output characteristics.
[0152] For example, the radius of the first hollow portion may be 1.5 to 10 μm (average diameter is 3 to 20 μm), and the average particle size (d50) of the composite silicon particles may be 100 to 1200 nm (radius is 50 to 600 nm).
[0153] In a specific example, the number of composite silicon particles filled in the first hollow part can be 5 to 12000. Under the above conditions, the number of composite silicon particles can be easily controlled, the destruction of the hollow core caused by the expansion of the composite silicon particles can be prevented, and the negative electrode active material can have excellent high capacity and high output characteristics.
[0154] In a specific example, the negative electrode active material may include one or more composite silicon particles with different average particle sizes.
[0155] In a specific example, the negative electrode active material may include a first composite silicon particle and a second composite silicon particle having radii r1 and r2, respectively. The r1 and r2 may be the same or different.
[0156] In a specific example, the negative electrode active material includes first composite silicon particles and second composite silicon particles having radii r1 and r2, respectively, and the number of particles (n1 and n2) of the first composite silicon and the second composite silicon filled in the first hollow portion may satisfy the condition of the following formula 2:
[0157] Formula 2:
[0158] (In the above formula 2, r1' and r2' are the radii of the first expanded composite silicon particle and the second expanded composite silicon particle, respectively, R is the radius of the first hollow portion, r1' and r2' are 1.2599*a1+b1 and 1.2599*a2+b2, respectively (a1 and b1 are the radius of the first nano-silicon particle and the thickness of the first coating layer, and a2 and b2 are the radius of the second nano-silicon particle and the thickness of the first coating layer)).
[0159] When the number of composite silicon particles filled in the hollow portion is set under the condition of Formula 2 above, rupture or destruction of the first hollow core (or negative electrode active material) due to expansion of the composite silicon particles can be prevented.
[0160] In a specific example, the radii (r1' and r2') of the first expanded composite silicon particle and the second expanded composite silicon particle whose volumes are expanded by 2 times with the radii r1 and r2 respectively may be 1.2599*r1 and 1.2599*r2 respectively.
[0161] Therefore, the total volume of the first expanded composite silicon particles and the second expanded composite silicon particles satisfies the first hollow portion volume (n1*2*(4 / 3)*π*(r1') or less. 3 +n2*2*(4 / 3)*π*(r2') 3 ≤2*(4 / 3)*π*(R) 3 ), using the above method, the above formula 2 condition can be derived.
[0162] In a specific example, the average diameter of the first hollow part of the negative electrode active material can be 10-20 μm (radius 5-10 μm), and the average particle size (d50) of the first composite silicon and the second composite silicon particles can be 900-1100 nm (radius 450-550 nm), respectively. Under the above conditions, the composite silicon particles have excellent dispersibility, can prevent the rupture of the hollow core caused by the expansion of the composite silicon particles, and can have excellent high capacity and high output characteristics.
[0163] In a specific example, the number of composite silicon particles filled in the hollow portion may be 5 to 12,000. Under the above conditions, the number of composite silicon particles is easily controlled, the rupture of the hollow core caused by the expansion of the composite silicon particles can be prevented, and excellent high capacity and high output characteristics can be achieved. For example, the number may be 100 to 11,000.
[0164] In a specific example, for the negative electrode active material, the average diameter of the first hollow part can be 6-10 μm (radius 3-5 μm), and can include 250-5000 first composite silicon particles with an average particle size (d50) of 180-240 nm (radius 90-120 nm) and 100-1800 second composite silicon particles with an average particle size (d50) of 280-340 nm (radius 140-170 nm). Under the above conditions, the composite silicon particles can have excellent dispersibility, and the rupture and destruction of the first hollow core during the expansion of the composite silicon particles can be prevented, and excellent high capacity and high output characteristics can be obtained.
[0165] For example, when the first hollow portion with an average diameter of 6 μm (radius 3 μm) includes first composite silicon particles with a radius of 105 nm (nano silicon particles with a radius of 100 nm and a first coating layer thickness of 5 nm) and second composite silicon particles with a radius of 155 nm (nano silicon particles with a radius of 150 nm and a first coating layer thickness of 5 nm), 300 to 4100 first composite silicon particles and 120 to 1150 second composite silicon particles may be included.
[0166] For another example, when the first hollow portion with an average diameter of 6 μm (radius 3 μm) includes first composite silicon particles with a radius of 110 nm (nano silicon particles with a radius of 100 nm, and a first coating layer thickness of 10 nm) and second composite silicon particles with a radius of 160 nm (nano silicon particles with a radius of 150 nm, and a first coating layer thickness of 10 nm), there are 250 to 3600 first composite silicon particles and 110 to 1050 second composite silicon particles.
[0167] For another example, the first hollow portion with an average diameter of 10 μm (radius 5 μm) may include 270 to 300 composite silicon particles with a radius of 500 nm (nano silicon particles with a radius of 490 nm and a first coating layer thickness of 10 nm).
[0168] For another example, the first hollow portion with an average diameter of 10 μm (radius of 5 μm) may include 250 to 280 composite silicon particles with a radius of 510 nm (nano silicon particles with a radius of 500 nm and a first coating layer thickness of 10 nm).
[0169] For another example, the first hollow portion with an average diameter of 20 μm (radius of 10 μm) may include 2500 to 2700 composite silicon particles with a radius of 500 nm (nano silicon particles with a radius of 490 nm and a first coating layer thickness of 10 nm).
[0170] For another example, the first hollow portion with an average diameter of 20 μm (radius of 10 μm) may include 2,300 to 2,500 composite silicon particles with a radius of 510 nm (nano silicon particles with a radius of 500 nm and a first coating layer thickness of 10 nm).
[0171] In a specific example, the packing density of the composite silicon particles may be 75% or less. The packing density of the composite silicon particles may mean the number of composite silicon particles actually filled relative to the maximum number of composite silicon particles filled in the hollow portion. For example, the packing density may be represented by the following formula A.
[0172] Formula A: Packing density = (n1 / n0)*100
[0173] (In the above formula A, n0 is the maximum number of composite silicon particles filled in the first hollow portion according to the following formula 1-3, and n1 is the number of composite silicon particles filled in the first hollow portion according to the above formula 1).
[0174] The n1 can be derived in the same manner as in the above-mentioned Formula 1 or Formula 2.
[0175] The n0 can be derived according to the following formula 1-3.
[0176] Formula 1-3:
[0177] (In the above formula 1-3, d0 is the relative diameter of the composite silicon particle derived from the following formula 1-4, and q0 is the relative diameter of the composite silicon particle at the center of the first hollow portion derived from the following formula 1-5)
[0178] Formula 1-4: d0 = r / R
[0179] (In the above formula 1-4, R is the radius of the first hollow portion, and r is the radius of the composite silicon particle)
[0180] Formula 1-5: q0 = 1-2*d0
[0181] (In the above formula 1-5, the d0 is as defined above).
[0182] Under the packing density conditions, the negative electrode active material can be prevented from being damaged due to the expansion of the composite silicon particles, and excellent high capacity and high output characteristics can be achieved. For example, the packing density can be 20 to 50%. For another example, the packing density can be 20 to 25%.
[0183] In a specific example, the radius of the composite silicon particle filled in the first hollow portion can be derived by assuming that the total volume of the first coating layer of the composite silicon particle when expanded twice is the same as the total volume of the first coating layer of the composite silicon particle that is not expanded.
[0184] Specifically, the radius r1 of the composite silicon particle, the radius a1 of the nano silicon particle and the thickness b1 of the first coating layer may satisfy the relationship r1=a1+b1, and the radius r1' of the composite silicon particle, the radius a1' of the nano silicon particle and the thickness b1' of the first coating layer may satisfy the relationship (r1')=(a1')+(b1').
[0185] By using the above method, the total volume of the first coating layer of the composite silicon particles can satisfy (4 / 3)*π*(r1') 3 -(4 / 3)*π*(a1') 3 The total volume of the first coating layer of the expanded composite silicon particles can satisfy (4 / 3)*π*(r1) 3 -(4 / 3)*π*(a1) 3 relationship.
[0186] Assuming that the total volume of the first coating layer before and after expansion is the same, (4 / 3)*π*(r1') can be satisfied. 3 -(4 / 3)*π*(a1') 3 =(4 / 3)*π*(r1) 3 -(4 / 3)*π*(a1) 3 , in summary, (r1') 3 -(a1') 3 =(r1) 3 -(a1) 3 , from which we can derive (r1') 3 =(a1') 3 +(r1) 3 -(a1) 3 relationship.
[0187] Therefore, the radius r1 of the expanded composite silicon particle can satisfy the following condition of formula 2-1:
[0188] Formula 2-1: (r1') 3 =(a1') 3 +(r1) 3 -(a1) 3
[0189] (In the above formula 2-1, a1 is the radius of the nano-silicon particle, r1 is the radius of the composite silicon particle, and a1' is the radius of the nano-silicon particle after expansion).
[0190] For example, when a composite silicon particle with a radius of 510 nm and a first coating layer with a thickness of 10 nm is used, it can be derived that the radius of the composite silicon particle expanded by 2 times is about 636 nm. In this case, the thickness of the first coating layer of the composite silicon particle expanded by 2 times can be about 6 nm.
[0191] In a specific example, the negative electrode active material includes first composite silicon particles and second composite silicon particles having radii r1 and r2, respectively, and the number of particles (n1 and n2) of the first composite silicon and the second composite silicon filled in the first hollow portion may satisfy the condition of the following formula 2-2:
[0192] Formula 2-2:
[0193] (In the above formula 2-2, r1' and r2' are the radii of the first expanded composite silicon particle and the second expanded composite silicon particle, respectively, R is the radius of the first hollow portion, and r1' and r2' respectively satisfy (r1') 3 =(a1') 3 +(r1) 3 -(a1) 3 and (r2') 3 =(a2') 3 +(r2) 3 -(a2) 3 (a1 is the radius of the nano-silicon particle, r1 is the radius of the composite silicon particle, and a1' is the radius of the nano-silicon particle after expansion)).
[0194] The sizes of the first and second composite silicon particles may be the same or different. Under the above conditions, the composite silicon particles have excellent dispersibility, can prevent the first hollow core from breaking and destroying when the composite silicon particles expand, and can have excellent high capacity and high output characteristics.
[0195] (3) Carbon particles: The carbon particles include graphene and graphite. When the carbon particles are included, the battery can have excellent conductivity and high output characteristics, can prevent capacity reduction, and can have excellent long life characteristics.
[0196] The carbon particles can enhance the conductive network inside and outside the negative electrode active material. The carbon particles not only have the function of an internal current collector, but can also be used as an electrochemically active material. When the composite silicon particles and carbon particles are filled, a stable ion charge and discharge channel is ensured because a low resistance path is stably ensured, and the internal resistance (contact resistance) of the negative electrode material can be reduced.
[0197] In a specific example, the carbon particles fill and disperse between the composite silicon particles in the first hollow portion to form a space, and when the composite silicon particles expand, the expansion can be absorbed in the space.
[0198] In one specific example, the packing ratio may be determined by adjusting the mass, volume ratio, and particle size distribution of the composite silicon particles and carbon particles.
[0199] The carbon particles may be spherical, polyhedral, flake (flat), plate-like or elliptical.
[0200] In one specific example, the density of the carbon particles can be 2.5 g / cm 3 Under the above conditions, the carbon particles can have excellent conductivity and lightness. For example, the density of the carbon particles can be 0.3 to 2.5 g / cm 3 .
[0201] For example, the carbon particles may include a pencil hardness of B to 3H measured according to ISO 15184, an electrical conductivity of 5 to 300 μΩ·m, and a density of 0.3 to 1.5 g / cm 2 The first carbon particles may include graphite and graphene.
[0202] In a specific example, the purity (impurity content) of the carbon particles may be less than 100 ppm. Under the above conditions, the negative electrode active material may have excellent conductivity.
[0203] In another specific example, the purity (impurity content) of the carbon particles may be greater than 300 ppm, for example, 300 to 800 ppm.
[0204] In a specific example, the carbon particles (first carbon particles) may contain graphite and graphene in a weight ratio of 1:0.5 to 1:6. When contained in the above weight ratio, the negative electrode active material has excellent conductivity and capacity characteristics, and can have excellent high output and long life characteristics.
[0205] In a specific example, the average size of the graphite may be 10 to 5000 nm. The size may mean the maximum length or diameter (particle size) of the graphite. For example, the graphite may be flaky or spherical. For example, the graphite may be 50 to 5000 nm, 100 to 5000 nm, 300 to 5000 nm, 500 to 5000 nm, or 500 to 1000 nm.
[0206] In a specific example, the average size of the graphene may be 10 to 5000 nm. The size may mean the maximum length or diameter (particle size) of the graphene. For example, the graphene may be spherical. For example, the graphene may be 50 to 5000 nm, 100 to 5000 nm, 300 to 5000 nm, 500 to 5000 nm, or 500 to 1000 nm.
[0207] The graphene can be formed by a step of milling one or more of natural graphite, artificial graphite and expanded graphite to refine graphite particles and separate graphite layers. When prepared under the above conditions, the graphene can have excellent crystallinity and electrical properties.
[0208] In a specific example, the graphene may include a layer structure of 1 to 10 layers. Under the above conditions, the graphene has excellent crystallinity, the conductivity and capacity characteristics of the negative electrode active material are excellent, and it may have excellent high output and long life characteristics. For example, the graphene may include a layer structure of 2 to 8 layers or 2 to 5 layers.
[0209] In one specific example, the graphene is used In the X-ray diffraction (XRD) spectrum of CuKα rays, the diffraction angle (2θ) value on the (002) plane may have a maximum peak in the region of 25 to 28°, and the diffraction angle (2θ) value on the (101) plane may have a maximum peak in the region of 42 to 47°.
[0210] In a specific example, the maximum peak intensity of the (002) plane / the maximum peak intensity of the (101) plane in the X-ray diffraction (XRD) spectrum of the graphene can be 50 or more. Under the above conditions, the durability of the graphene is excellent, the conductivity and capacity characteristics of the negative electrode active material are excellent, and it can have excellent high output and long life characteristics. For example, the graphene is used In the X-ray diffraction spectrum of CuKα rays, the maximum peak intensity of the (002) plane / the maximum peak intensity of the (101) plane may be 70 or more, 80 or more, 100 or more, 200 or more, 300 or more, or 50 to 10,000.
[0211] In one embodiment, the D band peak intensity (I D / I G ) can be less than 0.65. Under the above conditions, the graphene has excellent durability and excellent conductivity, thereby ensuring high capacity and high output characteristics of the negative electrode active material. For example, the D band peak intensity (I D / I G ) may be less than 0.65, less than 0.55, or 0.10 to 0.55. For example, in the Raman spectrum of the graphene, the 1G band peak measured in a 532nm excitation continuous wave (CW) laser may appear at 1560 to 1600cm -1 In the wave number range, the 1D band peak can appear at 2600-2800 cm -1 Within the wave number range.
[0212] In one embodiment, the 2D band peak intensity (I 2D / I G ) can be 0.35 to 0.65. Under the above conditions, the graphene has excellent durability and excellent conductivity, thereby ensuring high capacity and high output characteristics of the negative electrode active material. For example, in the Raman spectrum, the 2D band peak intensity (I 2D / I G ) can be less than 0.65 or between 0.35 and 0.65.
[0213] For example, in the Raman spectrum of the graphene, the 1G band peak measured by a 532 nm excitation continuous wave (CW) laser may appear at 1560 to 1600 cm -1 In the wave number range, the 1D band peak can appear at 2600-2800 cm -1 In the wave number range, the 2D band peak can appear at 2680~2825cm -1 Within the wave number range.
[0214] In one specific example, in the Raman spectrum of the graphene, the Raman shift of the 2D band measured by a 532 nm excitation continuous wave (CW) laser can be between 2680 and 2725 cm -1 There is a peak in the wave number range. Under the above conditions, the resistance of graphene can be minimized, the conductivity and high output characteristics are excellent, the capacity can be prevented from decreasing, and the excellent long life characteristics can be achieved.
[0215] In a specific example, in the X-ray diffraction (XRD) spectrum of the negative electrode active material, the maximum peak intensity of the (002) plane of the graphite / the first peak intensity of the (111) plane of the composite silicon particles can be 1.5 to 2.2. Under the above conditions, the resistance of the negative electrode active material can be minimized, the conductivity and high output characteristics are excellent, the capacity can be prevented from decreasing, and the negative electrode active material can have excellent long life characteristics. For example, the negative electrode active material is used In the X-ray diffraction spectrum of CuKα rays, the maximum peak intensity of the (002) plane of the graphite / the first peak intensity of the (111) plane of the composite silicon particles can be 1.6 to 2.1, 1.7 to 2.1 or 1.8 to 2.1.
[0216] In a specific example, in the X-ray diffraction (XRD) spectrum of the negative electrode active material, the maximum peak intensity of the (002) plane of the graphite / the second peak intensity of the (220) plane of the composite silicon particles can be 3.5 to 4.5. Under the above conditions, the resistance of the negative electrode active material can be minimized, the conductivity and high output characteristics are excellent, the capacity can be prevented from decreasing, and the negative electrode active material can have excellent long life characteristics. For example, the negative electrode active material is used In the X-ray diffraction spectrum of Cu Kα rays, the maximum peak intensity of the (002) plane of the graphite / the second peak intensity of the (220) plane of the composite silicon particles may be 3.5-4.5, 3.7-4.3 or 3.8-4.3.
[0217] For example, the carbon particles may also include a pencil hardness of 4H to 7H measured according to ISO 15184, a resistivity of 3 to 50 μΩ·m, and a density of 1.8 to 2.5 g / cm 3 of the second carbon particles.
[0218] In a specific example, the average size of the second carbon particles may be 1 to 3000 nm. The size may mean the maximum length or diameter (particle size) of the second carbon particles. For example, the second carbon particles may be flake-shaped or spherical. For example, the second carbon particles may be 1 to 2500 nm, 3 to 1500 nm, 5 to 1000 nm, 10 to 500 nm, 30 to 500 nm, or 50 to 200 nm.
[0219] In a specific example, the first carbon particles and the second carbon particles may be contained in a weight ratio of 1:0.5 to 1:3. When contained in the above weight ratio, the negative electrode active material has excellent conductivity and capacity characteristics, and can have excellent high output and long life characteristics.
[0220] In a specific example, the carbon particles may be included in an amount of 1 to 15% by weight relative to the total weight of the negative electrode active material. Within the above content range, the miscibility and durability are excellent, and the carbon particles may have excellent high capacity and high output characteristics. For example, the carbon particles may be included in an amount of 1 to 12% by weight, 1.5 to 9% by weight, 1 to 8% by weight, 1 to 6% by weight, 1 to 5% by weight, or 1 to 3% by weight.
[0221] (4) Second coating layer: The second coating layer includes one or more of a hard coating layer, a middle coating layer and a soft coating layer.
[0222] In a specific example, the hardness of the first hollow core is different from that of the second coating layer. Under the hardness gradient condition as described above, the strength and durability of the negative electrode active material are excellent, and the rupture or destruction of the first hollow core and the second coating layer caused by the expansion of the composite silicon particles (or nano silicon particles) caused by the embedding of lithium ions can be prevented.
[0223] For example, the hardness of the second coating layer may be higher than the hardness of the first hollow core. For another example, the hardness of the first hollow core may be higher than the hardness of the second coating layer.
[0224] In a specific example, the second coating layer may include 1 to 40 weight % relative to the total weight of the negative electrode active material. When included in the above range, the durability and structural stability of the negative electrode active material can be excellent, and the electrical properties can be excellent. For example, it may include 1 to 35 weight %, 1 to 30 weight %, 1 to 25 weight %, 1 to 20 weight %, 1 to 15 weight %, 1 to 10 weight %, 2 to 10 weight % or 2 to 5 weight %.
[0225] (1) Hard coating layer: The hard coating layer can be formed by sintering a hard coating material described later. When the hard coating layer is included, the negative electrode active material has excellent strength and durability, thereby preventing the negative electrode active material from being destroyed during expansion of the composite silicon particles, and has excellent conductivity, can prevent capacity reduction, and can have excellent long life characteristics.
[0226] The hard coating layer may exhibit high crystallinity and may have excellent durability and strength under the above conditions.
[0227] In a specific example, the crystallinity of the hard coating layer can be higher than the middle coating layer and the soft coating layer described later. In addition, the crystallinity of the middle coating layer can be higher than the soft coating layer. The crystallinity can be confirmed by conventional XRD (X-ray diffraction) analysis. Under the above conditions, the destruction and rupture of the negative electrode active material caused by the expansion of the nano silicon particles can be prevented, thereby having excellent long life characteristics, and having excellent conductivity, strength and high output characteristics of the negative electrode active material.
[0228] In a specific example, the thickness of the hard coating layer may be 5 to 100 nm. Under the above conditions, the hardness and mechanical strength are excellent, thereby preventing the negative electrode active material from being broken or damaged even when the composite silicon particles expand. For example, the thickness may be 5 to 60 nm, 5 to 30 nm, or 5 to 20 nm.
[0229] In one embodiment, the density of the hard coating layer can exceed 1.8 g / cm 3 Under the above conditions, the hard coating layer can have excellent lightness and structural stability. For example, the density of the hard coating layer can be 1.85 to 2.8 g / cm 3 or 1.85~2.65g / cm 3 .
[0230] In one specific example, the specific surface area (BET) of the hard coating layer can be 100 m 2 Under the above conditions, the structure can be excellently stable.
[0231] In a specific example, the purity (impurity content) of the hard coating layer may be 100 ppm or less. Under the above conditions, the negative electrode active material may have excellent conductivity.
[0232] In a specific example, the hard coating layer may have a resistivity of 3 to 5 μΩ·m. Under the above conditions, the negative electrode active material may have excellent conductivity.
[0233] In a specific example, the pencil hardness of the hard coating layer measured according to ISO 15184 may be 4H or more. Under the above conditions, the durability and strength of the hard coating layer are excellent, and lithium ions are embedded in the composite silicon particles, thereby having an excellent effect of preventing the first hollow core (or negative electrode active material) from being broken or damaged during expansion. For example, the pencil hardness of the hard coating layer may be more than 4H or 4.5H to 7H.
[0234] In a specific example, the hard coating layer may be included in an amount of 1 to 20% by weight relative to the total weight of the negative electrode active material. When included in the above range, the hard coating layer may have excellent durability and structural stability of the negative electrode active material and excellent electrical properties. For example, the hard coating layer may be included in an amount of 1 to 15% by weight, 1 to 10% by weight, 2 to 10% by weight, or 2 to 5% by weight.
[0235] (2) Medium coating layer: In a specific example, the medium coating layer can be formed by heat treating one or more of hydrocarbon gas and carbon black. For example, the hydrocarbon gas can include methane (CH4), ethane (C2H6), propane (C3H8), butane (C4H 10 ), pentane (C5H 12 )
[0236] In a specific example, the middle coating layer can be amorphous or crystalline. Under the above conditions, it can have excellent strength and durability.
[0237] In a specific example, the thickness of the middle coating layer can be 5 to 100 nm. Under the above conditions, the hardness, flexibility and mechanical strength are excellent, so even when the composite silicon particles expand, the negative electrode active material can be prevented from being broken or damaged. For example, the thickness can be 5 to 60 nm, 5 to 30 nm or 5 to 20 nm.
[0238] In a specific example, the pencil hardness of the middle coating layer measured according to ISO 15184 may be greater than 2H and less than 4H. Under the above conditions, the cracking and destruction of the negative electrode active material caused by the expansion of the composite silicon particles can be prevented, thereby having excellent long life characteristics. For example, the pencil hardness may be 2H to 3.5H.
[0239] In one embodiment, the density of the middle coating layer can be more than 1.5 g / cm 3 And 1.8g / cm 3 Under the above conditions, the coating layer can have excellent lightness and structural stability. For example, the density of the coating layer can be more than 1.5 g / cm 3 And 1.7g / cm 3 the following.
[0240] In a specific example, the specific surface area (BET) of the middle coating layer can be 100 to 200 m 2 Under the above conditions, the structure can be excellently stable.
[0241] In a specific example, the purity (impurity content) of the middle coating layer may be less than 500 ppm. Under the above conditions, the negative electrode active material may have excellent conductivity.
[0242] In a specific example, the electrical conductivity (resistivity) of the middle coating layer may be 20 to 40 μΩ·m. Under the above conditions, the negative electrode active material may have excellent electrical conductivity.
[0243] In a specific example, the middle coating layer may include 1 to 20 weight % relative to the total weight of the negative electrode active material. When included in the above range, the flexibility, durability and structural stability of the negative electrode active material can be excellent, and the electrical properties can be excellent. For example, it may include 1 to 15 weight %, 1 to 10 weight %, 2 to 10 weight % or 2 to 5 weight %.
[0244] (3) Soft coating layer: In one embodiment, the soft coating layer can be prepared by sintering a soft coating material. In one embodiment, the soft coating material can include one or more of pitch, coke, and a carbon precursor formed from other organic matter. For example, the pitch can include one or more of pyrolysis fuel oil pitch and coal tar pitch.
[0245] In a specific example, the thickness of the soft coating layer may be 5 to 100 nm. Under the above conditions, flexibility and mechanical strength are excellent, so even when the composite silicon particles expand, the negative electrode active material can be prevented from being broken or damaged. For example, the thickness may be 5 to 60 nm, 5 to 30 nm, or 5 to 20 nm.
[0246] In a specific example, the pencil hardness of the soft coating layer measured according to ISO 15184 may be less than 2H. Under the above conditions, the destruction of the negative electrode active material caused by the volume expansion of the composite silicon particles can be prevented, thereby having excellent long life characteristics. For example, the pencil hardness may be B to 1H.
[0247] In a specific example, the density of the soft coating layer can be 1.5 g / cm 3 Under the above conditions, the soft coating layer can have excellent lightness and structural stability. For example, the density of the soft coating layer can be 0.3 g / cm 3 Up to 1.4g / cm 3 .
[0248] In a specific example, the specific surface area (BET) of the soft coating layer can be 300 m 2 / g or more. Under the above conditions, it can have excellent structural stability. For example, the specific surface area (BET) can be 300 to 2500 m 2 / g.
[0249] In a specific example, the purity (impurity content) of the soft coating layer may be above 1000 ppm. Under the above conditions, the negative electrode active material may have excellent conductivity. For example, it may be 1000 to 5000 ppm.
[0250] In a specific example, the soft coating layer may have a resistivity of 50 μΩ·m or more. Under the above conditions, the soft coating layer may have excellent conductivity of the negative electrode active material. For example, the resistivity may be 50 to 300 μΩ·m.
[0251] In a specific example, the second coating layer may include a soft (or hard) coating layer and a hard (or soft) coating layer sequentially formed on the outer peripheral surface of the first hollow core.
[0252] For example, the second coating layer may include the soft coating layer and the hard coating layer in a weight ratio of 1:0.5 to 1:4. When included in the above weight ratio range, the negative electrode active material can be prevented from being broken and damaged during the expansion of the composite silicon particles, and can have excellent conductivity, high output and long life characteristics. For example, it can be included in a weight ratio of 1:1 to 1:2.
[0253] In another specific example, the second coating layer may include a soft (or hard) coating layer, a hard (or soft) coating layer, and a middle coating layer sequentially formed on the outer peripheral surface of the first hollow core.
[0254] For example, the second coating layer may include the soft coating layer, the hard coating layer, and the middle coating layer in a weight ratio of 1:0.5 to 4:0.5 to 5. When included in the above weight ratio range, the negative electrode active material can be prevented from being broken and damaged during the expansion of the composite silicon particles, and can have excellent conductivity, high output, and long life characteristics. For example, it can be included in a weight ratio of 1:1 to 2:0.5 to 3.
[0255] In a specific example, the second coating layer and the first hollow core can be included in a weight ratio of 1:0.5 to 1:5. When included in the above weight ratio range, the negative electrode active material can be prevented from being broken and damaged even when the volume of the composite silicon particles expands, and excellent high output and long life characteristics can be obtained. For example, the second coating layer and the first hollow core can be included in a weight ratio of 1:1 to 1:4, a weight ratio of 1:1 to 1:3, or a weight ratio of 1:1.5 to 1:3.
[0256] Second specific example
[0257] Figure 3 Another specific example of the negative electrode active material according to the present invention is shown. Figure 3 The negative electrode active material 200 includes: primary particles, including a first hollow core 20 forming a first hollow portion 22 and composite silicon particles 10 and carbon particles 16 filled in the first hollow portion 22; and secondary particles, including a second hollow core 30 forming a second hollow portion 32 and one or more of the primary particles filled in the second hollow portion 32.
[0258] Refer to the Figure 3 , the first coating layer 12 includes a middle coating layer 14 .
[0259] In a specific example, the first hollow core and the second hollow core have different hardnesses. Under the above conditions, the negative electrode active material can be prevented from being broken and damaged during the expansion of the composite silicon particles, and can have excellent conductivity, high output and long life characteristics.
[0260] In a specific example, relative to the total weight of the negative electrode active material, the negative electrode active material may include 25 to 80 weight % of the composite silicon particles, 1 to 40 weight % of the first hollow cores, and 1 to 40 weight % of the second hollow cores.
[0261] In a specific example, the particle density of the negative electrode active material can be 1 to 3 g / cm 3 Under the above conditions, it can have excellent lightness and output.
[0262] In a specific example, the average particle size of the negative electrode active material can be more than 1.5 μm and less than 50 μm. Under the above conditions, under the average particle size condition, high capacity, high output characteristics and excellent structural stability can be achieved, and the destruction of the negative electrode active material caused by the volume expansion of the composite silicon particles during charging and discharging can be prevented, and excellent long life characteristics can be achieved. For example, it can be 5 to 45 μm, 5 to 40 μm, 6 to 40 μm, 10 to 40 μm, 10 to 30 μm or 10 to 25 μm.
[0263] Primary particles
[0264] (1) First hollow core: refer to the above Figure 3 A first hollow portion 22 is formed inside the first hollow core 20, and the first hollow portion 22 is filled with composite silicon particles 10 and carbon particles 16. The first hollow core may be spherical or elliptical. For example, it may be spherical.
[0265] In a specific example, the first hollow core is formed by sintering one or more coating materials of a hard coating material and a soft coating material described later.
[0266] The hardness of the first hollow core is different from that of the second hollow core. Under the above conditions, the electrical conductivity, hardness and mechanical strength are excellent, and during the charging process of the secondary battery, lithium ions are embedded in the composite silicon particles, thereby preventing the first hollow core (or negative electrode active material) from being broken or damaged during expansion, preventing the capacity from being reduced, and having excellent long life characteristics.
[0267] In a specific example, the average diameter of the first hollow portion can be 1.5 to 20 μm (radius 0.75 to 10 μm). Under the above conditions, the destruction of the negative electrode active material caused by the volume expansion of the composite silicon particles during charge and discharge can be prevented, thereby having excellent long life characteristics. For example, the average diameter can be 2 to 20 μm, 3 to 20 μm, 6 to 20 μm or 10 to 20 μm.
[0268] In a specific example, the thickness of the first hollow core may be 5 to 300 nm. Under the above conditions, the hardness and mechanical strength are excellent, and the rupture or damage of the negative electrode active material can be prevented even when the composite silicon particles expand. For example, it may be 5 to 300 nm, 5 to 250 nm, 5 to 200 nm, 10 to 200 nm, or 10 to 50 nm.
[0269] In a specific example, the density of the first hollow core can be 1.8 to 2.5 g / cm 3 Under the above conditions, it can have excellent lightness and structural stability. For example, the density of the hollow core can be 1.8 to 2.1 g / cm 3 .
[0270] In another specific example, the density of the first hollow core may be less than 1.8 g / cm 3 Under the above conditions, it can have excellent lightness and structural stability. For example, the density of the hollow core can be 0.3 to 1.7 g / cm 3 .
[0271] In a specific example, the specific surface area (BET) of the first hollow core can be 100 m 2 Under the above conditions, the structure can be excellently stable.
[0272] In another embodiment, the specific surface area (BET) of the first hollow core may exceed 100 m 2 / g. Under the above conditions, it can have excellent structural stability. For example, the specific surface area (BET) can be 110 to 500 m 2 / g.
[0273] In a specific example, the purity (impurity content) of the first hollow core may be less than 100 ppm. Under the above conditions, the negative electrode active material may have excellent conductivity.
[0274] In another specific example, the purity (impurity content) of the first hollow core may be greater than 500 ppm. Under the above conditions, the negative electrode active material may have excellent conductivity. For example, the impurity content may be 500 to 3000 ppm.
[0275] In a specific example, the electrical conductivity (resistivity) of the first hollow core may be 3 to 5 μΩ·m. Under the above conditions, the negative electrode active material may have excellent electrical conductivity.
[0276] In another specific example, the electrical conductivity (resistivity) of the first hollow core may be greater than 20 μΩ·m. Under the above conditions, the negative electrode active material may have excellent electrical conductivity. For example, the electrical conductivity may be 20 to 80 μΩ·m.
[0277] In a specific example, the pencil hardness of the first hollow core measured according to ISO 15184 may be 4H or more. Under the above conditions, the durability and strength of the hollow core are excellent, and lithium ions are embedded in the composite silicon particles, thereby having an excellent effect of preventing the hollow core (or negative electrode active material) from being broken or damaged during expansion. For example, the pencil hardness of the first hollow core may be 4H to 6H.
[0278] In another specific example, the pencil hardness of the first hollow core measured according to ISO 15184 may be less than 4H. Under the above conditions, the first hollow core has excellent flexibility, and lithium ions are embedded in the composite silicon particles, thereby having an excellent effect of preventing the first hollow core (or negative electrode active material) from being broken or damaged during expansion. For example, the pencil hardness of the first hollow core may be B to 3H. In another specific example, the pencil hardness of the first hollow core may be 2H to 3H.
[0279] In a specific example, the first hollow core may be included in an amount of 1 to 40% by weight relative to the total weight of the negative electrode active material. When included in the above range, the negative electrode active material may have excellent durability and structural stability while having excellent electrical properties. For example, it may include 1 to 30% by weight, 1 to 25% by weight, 1 to 20% by weight, 1 to 15% by weight, 2 to 15% by weight, 3 to 15% by weight, or 5 to 15% by weight.
[0280] (2) Composite silicon particles: refer to the above Figure 3 The composite silicon particle 10 includes: a nano-silicon particle 11 ; and a first coating layer 12 formed on the outer peripheral surface of the nano-silicon particle 11 .
[0281] In a specific example, the composite silicon particles may be spherical, polyhedral, elliptical or irregular in shape. For example, they may be spherical.
[0282] In one specific example, the average particle size of the composite silicon particles can be 50 to 1500 nm. Under the above conditions, the high capacity and high output characteristics of the composite silicon particles can be ensured, and the rupture or destruction of the negative electrode active material during the expansion of the composite silicon particles can be prevented, thereby having an excellent long life effect. In another specific example, the average particle size (d50) of the composite silicon particles can be less than 1300 nm, for example, the average particle size (d50) of the composite silicon particles can be 5 nm to 1300 nm, 10 nm to 1200 nm, 20 nm to 1200 nm, 25 nm to 1200 nm, 50 nm to 1100 nm, 300 nm to 1100 nm, 500 nm to 1100 nm or 900 nm to 1100 nm.
[0283] In one specific example, the composite silicon particles may be included in an amount of 25 to 80% by weight relative to the total weight of the negative electrode active material. Within the above content range, the composite silicon particles may have excellent miscibility and durability, and may have excellent high capacity and high output characteristics. For example, the composite silicon particles may be included in an amount of 25 to 70% by weight. In another specific example, the composite silicon particles may be included in an amount of 25 to 75% by weight, 25 to 65% by weight, 25 to 60% by weight, 25 to 50% by weight, 25 to 45% by weight, or 30 to 45% by weight.
[0284] (2-1) Nano silicon particles: In order to ensure high capacity and high output characteristics, the nano silicon particles are included. In a specific example, the nano silicon particles may be spherical, polyhedral, elliptical or irregular. For example, they may be spherical.
[0285] In one specific example, the nano-silicon particles may exhibit higher crystalline properties.
[0286] In a specific example, the average particle size of the nano silicon particles can be 45 to 1450 nm. Under the above conditions, the high capacity and high output characteristics of the nano silicon particles can be ensured, and the rupture or destruction of the negative electrode active material during the expansion of the nano silicon particles can be prevented, thereby having an excellent long life effect. For example, it can be 50 to 1300 nm or 80 to 990 nm.
[0287] In addition, it is also very important to control the maximum value (Dmax) of the average particle size of the nano silicon particles. For example, the Dmax particle size can be below 1450nm, below 1400nm, below 1000nm, or 100-1000nm. Preferably, it can be in the range of 320nm to 360nm. More preferably, it can be in the range of 300nm to 340nm. The lower the Dmax value, the higher the viscosity of the nano silicon slurry can be, and the viscosity of the nano silicon slurry can be controlled below 6500cps (25°C).
[0288] (2-2) First coating layer: refer to the above Figure 3 , the first coating layer 12 includes a middle coating layer 14 formed on the outer peripheral surface of the nano silicon particle 11. Under the above conditions, excellent conductivity and high output characteristics can be obtained.
[0289] In a specific example, the thickness of the first coating layer can be 3 to 110 nm. Under the above conditions, it has excellent conductivity and high output characteristics, and excellent durability, thereby preventing the destruction of the negative electrode active material during the expansion of the composite silicon particles caused by the embedding of lithium ions during the charge and discharge of the secondary battery, and therefore, it can have excellent long life characteristics. For example, the thickness of the first coating layer can be 5 to 100 nm, 5 to 80 nm, 5 to 60 nm, 5 to 50 nm, 5 to 30 nm or 5 to 20 nm.
[0290] The medium coating layer may be formed by heat treating one or more of a hydrocarbon gas and carbon black. For example, the hydrocarbon gas may include methane (CH4), ethane (C2H6), propane (C3H8), butane (C4H 10 ), pentane (C5H 12 )
[0291] In a specific example, the pencil hardness of the middle coating layer measured according to ISO 15184 may be greater than 2H and less than 4H. Under the above conditions, the cracking or destruction of the negative electrode active material caused by the volume expansion of the nano silicon particles can be prevented, thereby having excellent long life characteristics. For example, the pencil hardness may be 2.5H to 3H.
[0292] In a specific example, the thickness of the middle coating layer can be 2 to 100 nm. Under the above conditions, the rupture or destruction of the negative electrode active material caused by the expansion of the composite silicon particles can be prevented, and excellent high output and conductivity can be achieved. For example, the thickness of the middle coating layer can be 4 to 80 nm, 4 to 70 nm, 5 to 60 nm, 5 to 40 nm, 5 to 30 nm, or 5 to 20 nm.
[0293] In one embodiment, the density of the middle coating layer can be more than 1.5 g / cm 3 And 1.8g / cm 3 Under the above conditions, the coating layer can have excellent lightness and structural stability. For example, the density of the coating layer can be more than 1.5 g / cm 3 And 1.7g / cm 3 the following.
[0294] In a specific example, the specific surface area (BET) of the middle coating layer can be 100 to 200 m 2 Under the above conditions, the structure can be excellently stable.
[0295] In a specific example, the purity (impurity content) of the middle coating layer may be less than 500 ppm. Under the above conditions, the negative electrode active material may have excellent conductivity.
[0296] In a specific example, the electrical conductivity (resistivity) of the middle coating layer may be 20 to 40 μΩ·m. Under the above conditions, the negative electrode active material may have excellent electrical conductivity.
[0297] For example, the first coating layer may further include a silicon carbide (SiC) layer formed between the nano-silicon particles and the middle coating layer. Figure 3 , the first coating layer 12 may include a silicon carbide (SiC) layer 13 and a middle coating layer 14 sequentially formed on the outer peripheral surface of the nano silicon particles 11. Under the above conditions, it has excellent conductivity and high output characteristics, and excellent durability, thereby preventing the destruction of the negative electrode active material during the expansion of the composite silicon particles caused by the insertion of lithium ions during the charge and discharge of the secondary battery, and therefore, it can have excellent long life characteristics.
[0298] The silicon carbide layer improves the ion conductivity and electrical conductivity of the composite silicon particles while ensuring a stable ion charge and discharge channel, thereby having a low contact resistance and preventing the destruction of the composite silicon particles caused by the volume expansion of the nano silicon particles.
[0299] In a specific example, the thickness of the silicon carbide (SiC) layer may be 1 to 10 nm. Under the above conditions, the durability, ion conductivity and electrical conductivity are excellent, and the contact resistance may be low. For example, the thickness may be 1 to 10 nm, 2 to 10 nm, 3 to 10 nm, 3 to 8 nm or 3 to 5 nm.
[0300] In a specific example, the hardness of the silicon carbide layer may be higher than that of the middle coating layer. Under the above conditions, the electrical conductivity is excellent, and the destruction of the composite silicon particles caused by the volume expansion of the nano silicon particles can be prevented.
[0301] For example, the pencil hardness of the silicon carbide layer measured according to ISO 15184 may be 7H or more. For example, it may be 8H or more, or 10H or more, or 8H to 10H.
[0302] In a specific example, the composite silicon particles can contain the first coating layer and nano silicon particles in a weight ratio of 1:0.5 to 1:6. When contained in the above range, the conductivity is excellent, the rupture and destruction of the negative electrode active material caused by the expansion of the composite silicon particles can be prevented, and the capacity reduction can be minimized, thereby having excellent long-life characteristics. For example, it can be contained in a weight ratio of 1:0.5 to 1:5, a weight ratio of 1:0.5 to 1:4, a weight ratio of 1:1 to 1:3.5, a weight ratio of 1:1 to 1:3, a weight ratio of 1:1 to 1:2, or a weight ratio of 1:1.5 to 1:2.
[0303] In a specific example, the composite silicon particles may have effective peaks in one or more regions of 26-30°, 47-50°, 53-58°, 68-72°, 74-78°, and 88-90° in the 2θ value of the X-ray diffraction (XRD) spectrum. Under the above conditions, the low contact resistance, high capacity, and high output characteristics of the composite silicon particles can be ensured, and the cracking phenomenon of the nano-silicon particles in the composite silicon particles during charge and discharge can be significantly reduced.
[0304] For example, the composite silicon particles may have effective peaks in the diffraction angle (2θ) values in the X-ray diffraction spectrum in the regions of 27-30°, 46-50°, 56-57°, 68-69.5°, 75-76°, and 88-90°, respectively. Under the above conditions, the low contact resistance, high capacity, and high output characteristics of the composite silicon particles can be ensured, and the cracking phenomenon of the nano-silicon particles in the composite silicon particles during charge and discharge can be significantly reduced.
[0305] For example, the composite silicon particles may have effective peaks in the diffraction angle (2θ) values of 28-29.5°, 47-49°, 56-57°, 68-69.5°, 75-76° and 88-90°, respectively, and the effective peaks may represent (111), (220), (311), (400), (331), and (442) crystal planes, respectively.
[0306] For example, the composite silicon particles are used In the X-ray diffraction (XRD) spectrum of CuKα rays, the diffraction angle (2θ) value on the (111) plane can have effective peaks in the range of 26 to 30° and the diffraction angle (2θ) value on the (220) plane can have effective peaks in the range of 46 to 50°.
[0307] For example, in the X-ray diffraction spectrum, the composite silicon particles may have effective peaks in the diffraction angle (2θ) values on the (111) plane in the range of 28 to 29.5° and on the (220) plane in the range of 47 to 49°.
[0308] For example, when using In the X-ray diffraction (XRD) spectrum of CuKα rays and measuring 2θ at 10-70° with a step size of 0.01°, the diffraction angle (2θ) value of the composite silicon particles on the (111) plane can have effective peaks in the region of 26-30° and the diffraction angle (2θ) value on the (220) plane can have effective peaks in the region of 46-50°.
[0309] In one embodiment, the composite silicon particles are used on the (111) and (220) planes. The full width at half maximum (FWHM) of the X-ray diffraction angle (2θ) of CuKα rays can be in the range of 0.40° to 0.80°, more preferably, in the range of 0.52° to 0.68° or 0.59° to 0.71°. Under the above conditions, the low contact resistance, high capacity and high output characteristics of the composite silicon particles can be ensured, and the cracking phenomenon of the silicon particles during charging and discharging can be significantly reduced.
[0310] The number of composite silicon particles filled in the first hollow part
[0311] The number of composite silicon particles filled in the first hollow portion can be adjusted in the same manner as described above.
[0312] For example, when the volume of the composite silicon particles (nano silicon particles) expands by 2 times, it can be assumed that the first hollow portion is filled with a hexagonal close packing (HCC) or a face-centered cubic (FCC) structure for calculation.
[0313] For example, the radius k' of the expanded nano-silicon particle whose volume is expanded by 2 times by a spherical nano-silicon particle with a radius of k can be 1.2599*k. 3 =2*(4 / 3)*π*(k) 3 The radius k' of the expanded nano-silicon particle is derived from the relationship 3 √4)*k≈1.2599*k).
[0314] In a specific example, in the case of a composite silicon particle with a radius of a and a thickness of b of the first coating layer, the radius r' of the expanded composite silicon particle whose volume expands by 2 times may be r'=1.2599*a+b.
[0315] In addition, the number of composite silicon particles filled inside the hollow portion can be derived by taking into account the particle filling rate in the hexagonal closest packing or face-centered cubic structure (π*(√3 / 2)≈0.7405).
[0316] In one specific example, the radius (r') of the composite silicon particle with a radius (r) of 500 nm when expanded twice may be about 630 nm. In another specific example, the radius (r') of the composite silicon particle with a radius (r) of 510 nm when expanded twice may be about 643 nm.
[0317] In a specific example, the number (n) of composite silicon particles filled in the first hollow portion may satisfy the condition of the following formula 1:
[0318] Formula 1:
[0319] (In the above formula 1, d is the relative diameter of the expanded composite silicon particle derived from the following formula 1-1, and q is the relative diameter of the expanded composite silicon particle at the center of the first hollow portion derived from the following formula 1-2)
[0320] Formula 1-1: d = r' / R
[0321] (In the above formula 1-1, R is the radius of the first hollow portion, r' is the radius of the expanded composite silicon particle, and r'=1.2599*a+b (a is the radius of the composite silicon particle, and b is the thickness of the first coating layer))
[0322] Formula 1-2: q = 1-2*d
[0323] (In the above formula 1-2, the d is as defined above).
[0324] When the number of composite silicon particles filled in the first hollow portion is set under the condition of Formula 1, rupture or destruction of the first hollow core (or the negative electrode active material) due to expansion of the composite silicon particles can be prevented.
[0325] In a specific example, the average diameter of the first hollow portion can be 1.5 to 20 μm, and the average particle size of the composite silicon particles can be 50 to 1500 nm. Under the conditions of the average diameter of the first hollow portion and the average particle size of the composite silicon particles, the number of composite silicon particles can be easily controlled, the destruction of the hollow core caused by the expansion of the composite silicon particles can be prevented, and the negative electrode active material can have excellent high capacity and high output characteristics.
[0326] For example, the radius of the first hollow portion may be 1.5 to 10 μm (average diameter is 3 to 20 μm), and the average particle size (d50) of the composite silicon particles may be 100 to 1200 nm (radius is 50 to 600 nm).
[0327] In a specific example, the number of composite silicon particles filled in the first hollow part can be 5 to 12000. Under the above conditions, the number of composite silicon particles can be easily controlled, the destruction of the hollow core caused by the expansion of the composite silicon particles can be prevented, and the negative electrode active material can have excellent high capacity and high output characteristics.
[0328] In a specific example, the negative electrode active material may include one or more composite silicon particles with different average particle sizes.
[0329] In a specific example, the negative electrode active material may include a first composite silicon particle and a second composite silicon particle having radii r1 and r2, respectively. The r1 and r2 may be the same or different.
[0330] In a specific example, the negative electrode active material includes first composite silicon particles and second composite silicon particles having radii r1 and r2, respectively, and the number of particles (n1 and n2) of the first composite silicon and the second composite silicon filled in the first hollow portion may satisfy the condition of the following formula 2:
[0331] Formula 2:
[0332] (In the above formula 2, r1' and r2' are the radii of the first expanded composite silicon particle and the second expanded composite silicon particle, respectively, R is the radius of the first hollow portion, r1' and r2' are 1.2599*a1+b1 and 1.2599*a2+b2, respectively (a1 and b1 are the radius of the first nano-silicon particle and the thickness of the first coating layer, and a2 and b2 are the radius of the second nano-silicon particle and the thickness of the first coating layer)).
[0333] When the number of composite silicon particles filled in the hollow portion is set under the condition of Formula 2 above, rupture or destruction of the first hollow core (or negative electrode active material) due to expansion of the composite silicon particles can be prevented.
[0334] In a specific example, the radii (r1' and r2') of the first expanded composite silicon particle and the second expanded composite silicon particle whose volumes are expanded by 2 times with the radii r1 and r2 respectively may be 1.2599*r1 and 1.2599*r2 respectively.
[0335] Therefore, the total volume of the first expanded composite silicon particles and the second expanded composite silicon particles satisfies the first hollow portion volume (n1*2*(4 / 3)*π*(r1') or less. 3 +n2*2*(4 / 3)*π*(r2') 3 ≤2*(4 / 3)*π*(R) 3 ), using the above method, the above formula 2 condition can be derived.
[0336] In a specific example, the average diameter of the first hollow part of the negative electrode active material can be 10-20 μm (radius 5-10 μm), and the average particle size (d50) of the first composite silicon and the second composite silicon particles can be 900-1100 nm (radius 450-550 nm), respectively. Under the above conditions, the composite silicon particles have excellent dispersibility, can prevent the rupture of the hollow core caused by the expansion of the composite silicon particles, and can have excellent high capacity and high output characteristics.
[0337] In a specific example, the number of composite silicon particles filled in the hollow portion may be 5 to 12,000. Under the above conditions, the number of composite silicon particles is easily controlled, the rupture of the hollow core caused by the expansion of the composite silicon particles can be prevented, and excellent high capacity and high output characteristics can be achieved. For example, the number may be 100 to 11,000.
[0338] In a specific example, for the negative electrode active material, the average diameter of the first hollow part can be 6-10 μm (radius 3-5 μm), and can include 250-5000 first composite silicon particles with an average particle size (d50) of 180-240 nm (radius 90-120 nm) and 100-1800 second composite silicon particles with an average particle size (d50) of 280-340 nm (radius 140-170 nm). Under the above conditions, the composite silicon particles can have excellent dispersibility, and the rupture and destruction of the first hollow core during the expansion of the composite silicon particles can be prevented, and excellent high capacity and high output characteristics can be obtained.
[0339] For example, when the first hollow portion with an average diameter of 6 μm (radius 3 μm) includes first composite silicon particles with a radius of 105 nm (nano silicon particles with a radius of 100 nm and a first coating layer thickness of 5 nm) and second composite silicon particles with a radius of 155 nm (nano silicon particles with a radius of 150 nm and a first coating layer thickness of 5 nm), 300 to 4100 first composite silicon particles and 120 to 1150 second composite silicon particles may be included.
[0340] For another example, when the first hollow portion with an average diameter of 6 μm (radius 3 μm) includes first composite silicon particles with a radius of 110 nm (nano silicon particles with a radius of 100 nm, and a first coating layer thickness of 10 nm) and second composite silicon particles with a radius of 160 nm (nano silicon particles with a radius of 150 nm, and a first coating layer thickness of 10 nm), there are 250 to 3600 first composite silicon particles and 110 to 1050 second composite silicon particles.
[0341] For another example, the first hollow portion with an average diameter of 10 μm (radius 5 μm) may include 270 to 300 composite silicon particles with a radius of 500 nm (nano silicon particles with a radius of 490 nm and a first coating layer thickness of 10 nm).
[0342] For another example, the first hollow portion with an average diameter of 10 μm (radius 5 μm) may include 250 to 280 composite silicon particles with a radius of 510 nm (nano silicon particles with a radius of 500 nm and a first coating layer thickness of 10 nm).
[0343] For another example, the first hollow portion with an average diameter of 20 μm (radius of 10 μm) may include 2500 to 2700 composite silicon particles with a radius of 500 nm (nano silicon particles with a radius of 490 nm and a first coating layer thickness of 10 nm).
[0344] For another example, the first hollow portion with an average diameter of 20 μm (radius of 10 μm) may include 2,300 to 2,500 composite silicon particles with a radius of 510 nm (nano silicon particles with a radius of 500 nm and a first coating layer thickness of 10 nm).
[0345] In a specific example, the packing density of the composite silicon particles may be 75% or less. The packing density of the composite silicon particles may mean the number of composite silicon particles actually filled relative to the maximum number of composite silicon particles filled in the hollow portion. For example, the packing density may be represented by the following formula A.
[0346] Formula A: Packing density = (n1 / n0)*100
[0347] (In the above formula A, n0 is the maximum number of composite silicon particles filled in the first hollow portion according to the following formula 1-3, and n1 is the number of composite silicon particles filled in the first hollow portion according to the above formula 1).
[0348] The n1 can be derived in the same manner as in the above-mentioned Formula 1 or Formula 2.
[0349] The n0 can be derived according to the following formula 1-3.
[0350] Formula 1-3:
[0351] (In the above formula 1-3, d0 is the relative diameter of the composite silicon particle derived from the following formula 1-4, and q0 is the relative diameter of the composite silicon particle at the center of the first hollow portion derived from the following formula 1-5)
[0352] Formula 1-4: d0 = r / R
[0353] (In the above formula 1-4, R is the radius of the first hollow portion, and r is the radius of the composite silicon particle)
[0354] Formula 1-5: q0 = 1-2*d0
[0355] (In the above formula 1-5, the d0 is as defined above).
[0356] Under the packing density conditions, the negative electrode active material can be prevented from being damaged due to the expansion of the composite silicon particles, and excellent high capacity and high output characteristics can be achieved. For example, the packing density can be 20 to 50%. For another example, the packing density can be 20 to 25%.
[0357] In a specific example, the radius of the composite silicon particle filled in the first hollow portion can be derived by assuming that the total volume of the first coating layer of the composite silicon particle when expanded twice is the same as the total volume of the first coating layer of the composite silicon particle that is not expanded.
[0358] Specifically, the radius r1 of the composite silicon particle, the radius a1 of the nano silicon particle and the thickness b1 of the first coating layer may satisfy the relationship r1=a1+b1, and the radius r1' of the composite silicon particle, the radius a1' of the nano silicon particle and the thickness b1' of the first coating layer may satisfy the relationship (r1')=(a1')+(b1').
[0359] By using the above method, the total volume of the first coating layer of the composite silicon particles can satisfy (4 / 3)*π*(r1') 3 -(4 / 3)*π*(a1') 3 The total volume of the first coating layer of the expanded composite silicon particles can satisfy (4 / 3)*π*(r1) 3 -(4 / 3)*π*(a1) 3 relationship.
[0360] Assuming that the total volume of the first coating layer before and after expansion is the same, (4 / 3)*π*(r1') can be satisfied. 3 -(4 / 3)*π*(a1') 3 =(4 / 3)*π*(r1) 3 -(4 / 3)*π*(a1) 3 , in summary, (r1') 3 -(a1') 3 =(r1) 3 -(a1) 3 , from which we can derive (r1') 3 =(a1') 3 +(r1) 3 -(a1) 3 relationship.
[0361] Therefore, the radius r1 of the expanded composite silicon particle can satisfy the following condition of formula 2-1:
[0362] Formula 2-1: (r1') 3 =(a1') 3 +(r1) 3 -(a1) 3
[0363] (In the above formula 2-1, a1 is the radius of the nano-silicon particle, r1 is the radius of the composite silicon particle, and a1' is the radius of the nano-silicon particle after expansion).
[0364] For example, when a composite silicon particle with a radius of 510 nm and a first coating layer with a thickness of 10 nm is used, it can be derived that the radius of the composite silicon particle expanded by 2 times is about 636 nm. In this case, the thickness of the first coating layer of the composite silicon particle expanded by 2 times can be about 6 nm.
[0365] In a specific example, the negative electrode active material includes first composite silicon particles and second composite silicon particles having radii r1 and r2, respectively, and the number of particles (n1 and n2) of the first composite silicon and the second composite silicon filled in the first hollow portion may satisfy the condition of the following formula 2-2:
[0366] Formula 2-2:
[0367] (In the above formula 2-2, r1' and r2' are the radii of the first expanded composite silicon particle and the second expanded composite silicon particle, respectively, R is the radius of the first hollow portion, and r1' and r2' respectively satisfy (r1') 3 =(a1') 3 +(r1) 3 -(a1) 3 and (r2') 3 =(a2') 3 +(r2) 3 -(a2) 3 (a1 is the radius of the nano-silicon particle, r1 is the radius of the composite silicon particle, and a1' is the radius of the nano-silicon particle after expansion)).
[0368] The sizes of the first and second composite silicon particles may be the same or different. Under the above conditions, the composite silicon particles have excellent dispersibility, can prevent the first hollow core from breaking and destroying when the composite silicon particles expand, and can have excellent high capacity and high output characteristics.
[0369] In one specific example, the composite silicon particles may be included in an amount of 25 to 80% by weight relative to the total weight of the negative electrode active material. Within the above content range, the composite silicon particles may have excellent miscibility and durability, and may have excellent high capacity and high output characteristics. For example, the composite silicon particles may be included in an amount of 25 to 70% by weight. In another specific example, the composite silicon particles may be included in an amount of 25 to 75% by weight, 25 to 65% by weight, 25 to 60% by weight, 25 to 50% by weight, 25 to 45% by weight, or 30 to 45% by weight.
[0370] (3) Carbon particles: The carbon particles include graphene and graphite. When the carbon particles are included, the battery can have excellent conductivity and high output characteristics, can prevent capacity reduction, and can have excellent long life characteristics.
[0371] The carbon particles can enhance the conductive network inside and outside the negative electrode active material. The carbon particles not only have the function of an internal current collector, but can also be used as an electrochemically active material. When the composite silicon particles and carbon particles are filled, a stable ion charge and discharge channel is ensured because a low resistance path is stably ensured, and the internal resistance (contact resistance) of the negative electrode material can be reduced.
[0372] In a specific example, the carbon particles fill and disperse between the composite silicon particles in the first hollow portion to form a space, and when the composite silicon particles expand, the expansion can be absorbed in the space.
[0373] In one specific example, the packing ratio may be determined by adjusting the mass, volume ratio, and particle size distribution of the composite silicon particles and carbon particles.
[0374] The carbon particles may be spherical, polyhedral, flake (flat), plate-like or elliptical.
[0375] In one specific example, the density of the carbon particles can be 2.5 g / cm 3 Under the above conditions, the carbon particles can have excellent conductivity and lightness. For example, the density of the carbon particles can be 0.3 to 2.5 g / cm 3 .
[0376] For example, the carbon particles may include a pencil hardness of B to 3H measured according to ISO 15184, an electrical conductivity of 5 to 300 μΩ·m, and a density of 0.3 to 1.5 g / cm 2 The first carbon particles may include graphite and graphene.
[0377] In a specific example, the purity (impurity content) of the carbon particles may be less than 100 ppm. Under the above conditions, the negative electrode active material may have excellent conductivity.
[0378] In another specific example, the purity (impurity content) of the carbon particles may be greater than 300 ppm, for example, 300 to 800 ppm.
[0379] In a specific example, the carbon particles (first carbon particles) may contain graphite and graphene in a weight ratio of 1:0.5 to 1:6. When contained in the above weight ratio, the negative electrode active material has excellent conductivity and capacity characteristics, and can have excellent high output and long life characteristics.
[0380] In a specific example, the average size of the graphite may be 10 to 5000 nm. The size may mean the maximum length or diameter (particle size) of the graphite. For example, the graphite may be flaky or spherical. For example, the graphite may be 50 to 5000 nm, 100 to 5000 nm, 300 to 5000 nm, 500 to 5000 nm, or 500 to 1000 nm.
[0381] In a specific example, the average size of the graphene may be 10 to 5000 nm. The size may mean the maximum length or diameter (particle size) of the graphene. For example, the graphene may be spherical. For example, the graphene may be 50 to 5000 nm, 100 to 5000 nm, 300 to 5000 nm, 500 to 5000 nm, or 500 to 1000 nm.
[0382] The graphene may be formed by a process including subjecting one or more of natural graphite, artificial graphite, and expanded graphite to a milling process to miniaturize graphite particles and separating graphite layers.
[0383] In a specific example, the graphene may include a layer structure of 1 to 10 layers. Under the above conditions, the conductivity and capacity characteristics of the negative electrode active material are excellent, and it may have excellent high output and long life characteristics. For example, the graphene may include a layer structure of 2 to 8 layers or 2 to 5 layers.
[0384] In one specific example, the graphene is used In the X-ray diffraction (XRD) spectrum of CuKα rays, the diffraction angle (2θ) value on the (002) plane may have a maximum peak in the region of 25 to 28°, and the diffraction angle (2θ) value on the (101) plane may have a maximum peak in the region of 42 to 47°.
[0385] In a specific example, the maximum peak intensity of the (002) plane / the maximum peak intensity of the (101) plane in the X-ray diffraction (XRD) spectrum of the graphene can be 50 or more. Under the above conditions, the durability of the graphene is excellent, the conductivity and capacity characteristics of the negative electrode active material are excellent, and it can have excellent high output and long life characteristics. For example, the graphene is used In the X-ray diffraction spectrum of CuKα rays, the maximum peak intensity of the (002) plane / the maximum peak intensity of the (101) plane may be 70 or more, 80 or more, 100 or more, 200 or more, 300 or more, or 50 to 10,000.
[0386] In one embodiment, the D band peak intensity (I D / I G ) can be less than 0.65. Under the above conditions, the graphene has excellent durability and excellent conductivity, thereby ensuring high capacity and high output characteristics of the negative electrode active material. For example, the D band peak intensity (I D / I G ) may be less than 0.65, less than 0.55, or 0.10 to 0.55. For example, in the Raman spectrum of the graphene, the 1G band peak measured in a 532nm excitation continuous wave (CW) laser may appear at 1560 to 1600cm -1 In the wave number range, the 1D band peak can appear at 2600-2800 cm -1 Within the wave number range.
[0387] In one embodiment, the 2D band peak intensity (I 2D / I G ) can be 0.35 to 0.65. Under the above conditions, the graphene has excellent durability and excellent conductivity, thereby ensuring high capacity and high output characteristics of the negative electrode active material. For example, in the Raman spectrum, the 2D band peak intensity (I 2D / I G ) can be less than 0.65 or between 0.35 and 0.65.
[0388] For example, in the Raman spectrum of the graphene, the 1G band peak measured by a 532 nm excitation continuous wave (CW) laser may appear at 1560 to 1600 cm -1 In the wave number range, the 1D band peak can appear at 2600-2800 cm -1 In the wave number range, the 2D band peak can appear at 2680~2825cm-1 Within the wave number range.
[0389] In one specific example, in the Raman spectrum of the graphene, the Raman shift of the 2D band measured by a 532 nm excitation continuous wave (CW) laser can be between 2680 and 2725 cm -1 There is a peak in the wave number range. Under the above conditions, the resistance of graphene can be minimized, the conductivity and high output characteristics are excellent, the capacity can be prevented from decreasing, and the excellent long life characteristics can be achieved.
[0390] In a specific example, in the X-ray diffraction (XRD) spectrum of the negative electrode active material, the maximum peak intensity of the (002) plane of the graphite / the first peak intensity of the (111) plane of the composite silicon particles can be 1.5 to 2.2. Under the above conditions, the resistance of the negative electrode active material can be minimized, the conductivity and high output characteristics are excellent, the capacity can be prevented from decreasing, and the negative electrode active material can have excellent long life characteristics. For example, the negative electrode active material is used In the X-ray diffraction spectrum of CuKα rays, the maximum peak intensity of the (002) plane of the graphite / the first peak intensity of the (111) plane of the composite silicon particles can be 1.6 to 2.1, 1.7 to 2.1 or 1.8 to 2.1.
[0391] In a specific example, in the X-ray diffraction (XRD) spectrum of the negative electrode active material, the maximum peak intensity of the (002) plane of the graphite / the second peak intensity of the (220) plane of the composite silicon particles can be 3.5 to 4.5. Under the above conditions, the resistance of the negative electrode active material can be minimized, the conductivity and high output characteristics are excellent, the capacity can be prevented from decreasing, and the negative electrode active material can have excellent long life characteristics. For example, the negative electrode active material is used In the X-ray diffraction spectrum of Cu Kα rays, the maximum peak intensity of the (002) plane of the graphite / the second peak intensity of the (220) plane of the composite silicon particles may be 3.5-4.5, 3.7-4.3 or 3.8-4.3.
[0392] For example, the carbon particles may also include a pencil hardness of 4H to 7H measured according to ISO 15184, a resistivity of 3 to 50 μΩ·m, and a density of 1.8 to 2.5 g / cm 3 of the second carbon particles.
[0393] In a specific example, the average size of the second carbon particles may be 1 to 3000 nm. The size may mean the maximum length or diameter (particle size) of the second carbon particles. For example, the second carbon particles may be flake-shaped or spherical. For example, the second carbon particles may be 1 to 2500 nm, 3 to 1500 nm, 5 to 1000 nm, 10 to 500 nm, 30 to 500 nm, or 50 to 200 nm.
[0394] In a specific example, the first carbon particles and the second carbon particles may be contained in a weight ratio of 1:0.5 to 1:3. When contained in the above weight ratio, the negative electrode active material has excellent conductivity and capacity characteristics, and can have excellent high output and long life characteristics.
[0395] In a specific example, the carbon particles may be included in an amount of 1 to 15% by weight relative to the total weight of the negative electrode active material. Within the above content range, the miscibility and durability are excellent, and the carbon particles may have excellent high capacity and high output characteristics. For example, the carbon particles may be included in an amount of 1 to 12% by weight, 1.5 to 9% by weight, 1 to 8% by weight, 1 to 6% by weight, 1 to 5% by weight, or 1 to 3% by weight.
[0396] Secondary particles
[0397] Refer to the Figure 3 The secondary particles include a second hollow core 30 formed with a second hollow portion 32 and one or more primary particles filled in the second hollow portion 32 .
[0398] Although not mentioned Figure 3 As shown in the figure, carbon particles 16 may be further filled between the spaces filled with the primary particles in the second hollow part. The carbon particles include graphene and graphite. When the carbon particles are included, the electrical conductivity and high output characteristics are excellent, the capacity can be prevented from decreasing, and an excellent long life characteristic can be obtained.
[0399] In a specific example, relative to the total weight of the negative electrode active material, the sum of the carbon particles filled in the first hollow part and the carbon particles filled between the second hollow part and the primary particles may contain 1 to 10 weight %. Within the above content range, the miscibility and durability are excellent, and excellent high capacity and high output characteristics may be obtained. For example, 1.5 to 9 weight % may be included. For another example, the carbon particles may contain 0.5 to 10 weight %, 0.5 to 8 weight %, 1 to 6 weight %, 1 to 5 weight % or 1 to 3 weight %.
[0400] The second hollow core may be spherical or elliptical. For example, it may be spherical.
[0401] The diameter of the second hollow portion is greater than the diameter of the first hollow portion.
[0402] In a specific example, the average diameter of the second hollow part can be 3 to 50 μm. Under the above conditions, the destruction of the negative electrode active material caused by the expansion of the primary particles can be prevented, and excellent long life characteristics can be achieved. For example, the average diameter of the second hollow part can be 5 to 50 μm, 6 to 50 μm, 10 to 50 μm, 6 to 45 μm, 5 to 40 μm or 10 to 40 μm.
[0403] In a specific example, the thickness of the second hollow core may be 5 to 500 nm. Under the above conditions, the hardness and mechanical strength are excellent, thereby preventing the rupture or damage of the negative electrode active material caused by the expansion of the primary particles. For example, it may be 5 to 250 nm, 10 to 300 nm, or 10 to 50 nm.
[0404] In a specific example, the hardness of the second hollow core is different from that of the first hollow core. Under the above conditions, the conductivity, hardness and mechanical strength are excellent, and the second hollow core (or negative electrode active material) can be prevented from being broken or damaged when the primary particles (or composite silicon particles) expand during the charging process of the secondary battery, thereby preventing the capacity from being reduced, and having excellent long life characteristics.
[0405] For example, the density, specific surface area, and electrical conductivity of the second hollow core may be different from those of the first hollow core.
[0406] In a specific example, the density of the second hollow core can be 1.8 to 2.5 g / cm 3 Under the above conditions, the hollow core can have excellent lightness and structural stability. For example, the density of the second hollow core can be 1.8 to 2.1 g / cm 3 .
[0407] In another specific example, the density of the second hollow core may be less than 1.8 g / cm 3 Under the above conditions, the hollow core can have excellent lightness and structural stability. For example, the density of the second hollow core can be 0.3 to 1.7 g / cm 3 .
[0408] In a specific example, the specific surface area (BET) of the second hollow core can be 100 m 2 Under the above conditions, the structure can be excellently stable.
[0409] In another embodiment, the specific surface area (BET) of the second hollow core may be more than 100 m 2 / g. Under the above conditions, it can have excellent structural stability. For example, the specific surface area (BET) can be 110 to 500 m2 / g.
[0410] In a specific example, the purity (impurity content) of the second hollow core may be 100 ppm or less. Under the above conditions, the negative electrode active material may have excellent conductivity.
[0411] In another specific example, the purity (impurity content) of the second hollow core may be greater than 500 ppm. Under the above conditions, the negative electrode active material may have excellent conductivity. For example, the impurity content may be 500 to 3000 ppm.
[0412] In a specific example, the electrical conductivity (resistivity) of the second hollow core may be 3 to 5 μΩ·m. Under the above conditions, the negative electrode active material may have excellent electrical conductivity.
[0413] In another specific example, the electrical conductivity (resistivity) of the second hollow core may be greater than 20 μΩ·m. Under the above conditions, the negative electrode active material may have excellent electrical conductivity. For example, the electrical conductivity may be 20 to 80 μΩ·m.
[0414] In a specific example, the pencil hardness of the second hollow core measured according to ISO 15184 may be 4H or more. Under the above conditions, the durability and strength of the hollow core are excellent, and lithium ions are embedded in the composite silicon particles, thereby having an excellent effect of preventing the hollow core (or negative electrode active material) from being broken or damaged during expansion. For example, the pencil hardness of the second hollow core may be 4H to 6H.
[0415] In another specific example, the pencil hardness of the second hollow core measured according to ISO 15184 may be less than 4H. Under the above conditions, the second hollow core has excellent flexibility, and lithium ions are embedded in the composite silicon particles, thereby having an excellent effect of preventing the second hollow core (or negative electrode active material) from being broken or damaged during expansion. For example, the pencil hardness of the second hollow core may be B to 3H. In another specific example, the pencil hardness of the second hollow core may be 2H to 3H.
[0416] In a specific example, the pencil hardness of the first hollow core measured according to ISO 15184 may be 4H or more, and the pencil hardness of the second hollow core may be less than 4H. For example, the pencil hardness of the first hollow core may be 4H to 6H, and the pencil hardness of the second hollow core may be B to 1H.
[0417] In a specific example, the pencil hardness of the first hollow core measured according to ISO 15184 may be less than 4H, and the pencil hardness of the second hollow core may be greater than 4H. For example, the pencil hardness of the first hollow core may be B to 1H, and the pencil hardness of the second hollow core may be 4H to 6H.
[0418] In a specific example, the second hollow core may be included in an amount of 1 to 40% by weight relative to the total weight of the negative electrode active material. When included in the above range, the durability and structural stability of the negative electrode active material may be excellent, and the electrical properties may be excellent. For example, 1 to 30% by weight, 1 to 25% by weight, 1 to 20% by weight, 1 to 15% by weight, 2 to 15% by weight, 3 to 15% by weight, or 5 to 15% by weight may be included.
[0419] In a specific example, the negative electrode active material can include the second hollow core and the first hollow core in a weight ratio of 1:0.5 to 1:6. When included in the above weight ratio, the negative electrode active material has excellent durability and structural stability while having excellent long life, high output and electrical characteristics. For example, the negative electrode active material can include the second hollow core and the first hollow core in a weight ratio of 1:1 to 1:5, a weight ratio of 1:1.5 to 1:5, a weight ratio of 1:2 to 1:4 or a weight ratio of 1:2 to 1:3.
[0420] The number of primary particles filled in the second hollow portion
[0421] In a specific example, the secondary particles may include primary particles (1) and primary particles (2) having radii c1 and c2, respectively. The radii c1 and c2 of the primary particles (1) and (2) may be the same or different.
[0422] In a specific example, the number of primary particles (1) and primary particles (2) filled in the second hollow portion may satisfy the condition of the following formula 3:
[0423] Formula 3:
[0424] (In the above formula 3, c1 and n3 are the radius and number of primary particles (1), c2 and n4 are the radius and number of primary particles (2), and d is the radius of the second hollow portion).
[0425] When the number of primary particles (1) and (2) filled in the second hollow portion of the secondary particle is derived under the condition of the above formula 2, the second hollow core (or negative electrode active material) can be prevented from being broken or destroyed due to expansion of the primary particles.
[0426] In a specific example, the number of the primary particles filled in the second hollow portion may be 5 to 500. Under the above conditions, it can have excellent high output, long life and electrical characteristics. For example, the number of the primary particles may be 5 to 300, for example, the number of the primary particles may be 100 to 300.
[0427] In a specific example, the average diameter of the second hollow portion is 6 to 18 μm, and the second hollow portion may include 13 to 445 primary particles (1) having an average particle size (d50) of 2 to 3 μm (or a radius of 1.0 to 1.5 μm) and 1 to 125 primary particles (2) having an average particle size (d50) of 3 to 4 μm (or a radius of 1.5 to 2.0 μm). Under the above conditions, it is easy to control the number of primary particles, prevent the destruction of the second hollow core caused by the expansion of the primary particles (or composite silicon particles), and have excellent high capacity and high output characteristics of the negative electrode active material.
[0428] Second coating layer
[0429] In a specific example, the negative electrode active material may further include a second coating layer formed on the outer peripheral surface of the second hollow core.
[0430] In a specific example, the second coating layer may include one or more of a hard coating layer, a soft coating layer, and a middle coating layer.
[0431] The second coating layer may have a hardness different from that of the second hollow core. Under the above conditions, the negative electrode active material may be prevented from being broken or damaged when the composite silicon particles are expanded, thereby preventing a decrease in capacity and having excellent long life characteristics.
[0432] In a specific example, the thickness of the second coating layer can be 5 to 150 nm. Under the above conditions, rupture and damage caused by the expansion of the second hollow core (or negative electrode active material) can be prevented, and excellent high output and long life characteristics can be obtained. For example, it can be 5 to 120 nm, 5 to 100 nm, 5 to 90 nm, 5 to 60 nm, 5 to 80 nm, 10 to 80 nm, 10 to 50 nm, 10 to 40 nm or 10 to 30 nm.
[0433] (1) Hard coating layer: The hard coating layer can be formed by sintering a hard coating material described later. When the hard coating layer is included, the negative electrode active material has excellent strength and durability, thereby preventing damage during expansion of the composite silicon particles, and has excellent conductivity, can prevent capacity reduction, and can have excellent long life characteristics.
[0434] In a specific example, the thickness of the hard coating layer may be 5 to 100 nm. Under the above conditions, the hardness and mechanical strength are excellent, and the rupture or damage of the negative electrode active material can be prevented even when the second hollow core expands due to the expansion of the primary particles (or composite silicon particles). For example, the thickness may be 5 to 60 nm, 5 to 30 nm, 5 to 20 nm, 5 to 15 nm, or 5 to 10 nm.
[0435] In a specific example, the density of the hard coating layer can be 1.8 to 2.5 g / cm 3 Under the above conditions, the hard coating layer can have excellent lightness and structural stability. For example, the density of the hard coating layer can be 1.8 to 2.1 g / cm 3 .
[0436] In one specific example, the specific surface area (BET) of the hard coating layer can be 100 m 2 Under the above conditions, the structure can be excellently stable.
[0437] In a specific example, the purity (impurity content) of the hard coating layer may be 100 ppm or less. Under the above conditions, the negative electrode active material may have excellent conductivity.
[0438] In a specific example, the hard coating layer may have a resistivity of 3 to 5 μΩ·m. Under the above conditions, the negative electrode active material may have excellent conductivity.
[0439] In a specific example, the pencil hardness of the hard coating layer measured according to ISO 15184 may be 4H or more. Under the above conditions, the hard coating layer has excellent durability and strength, and can have an excellent effect of preventing the second hollow core (or negative electrode active material) from being broken or damaged due to the expansion of the primary particles (or composite silicon particles). For example, the pencil hardness of the hard coating layer may be 4H to 6H.
[0440] In one specific example, the hard coating layer has a higher hardness than the middle coating layer.
[0441] In a specific example, the hard coating layer may be included in an amount of 1 to 20 wt % relative to the total weight of the negative electrode active material. When included in the above range, the hard coating layer may have excellent durability and structural stability of the negative electrode active material and excellent electrical properties. For example, the hard coating layer may be included in an amount of 1 to 15 wt %, 1 to 10 wt %, 1 to 8 wt %, 2 to 8 wt % or 2 to 5 wt %.
[0442] (2) Medium coating layer: In one specific example, the medium coating layer may be formed by heat treating one or more of a hydrocarbon gas and carbon black. For example, the hydrocarbon gas may include methane (CH4), ethane (C2H6), propane (C3H8), butane (C4H 10 ), pentane (C5H 12 )
[0443] The middle coating layer can be in an amorphous state or a crystalline state. Under the above conditions, it can have excellent strength and durability.
[0444] In a specific example, the pencil hardness of the middle coating layer measured according to ISO 15184 may be 2H or more and less than 4H. Under the above conditions, the destruction of the second hollow core caused by the volume expansion of the primary particles (or composite silicon particles) can be prevented, and excellent long life characteristics can be obtained.
[0445] In a specific example, the thickness of the middle coating layer can be 5 to 100 nm. Under the above conditions, the expansion of the second hollow core caused by the expansion of the primary particles (or composite silicon particles) has an excellent buffering effect, thereby preventing rupture or damage. For example, the thickness can be 5 to 60 nm, 5 to 30 nm, or 5 to 20 nm.
[0446] In one embodiment, the density of the middle coating layer may be less than 1.8 g / cm 3 Under the above conditions, it can have excellent lightness and structural stability. For example, the density of the middle coating layer can be more than 1.5g / cm 3 And 1.7g / cm 3 the following.
[0447] In a specific example, the specific surface area (BET) of the middle coating layer can be 100 to 200 m 2 Under the above conditions, the structure can be excellently stable.
[0448] In a specific example, the purity (impurity content) of the middle coating layer may be less than 500 ppm. Under the above conditions, the negative electrode active material may have excellent conductivity.
[0449] In a specific example, the electrical conductivity (resistivity) of the middle coating layer may be 20 to 40 μΩ·m. Under the above conditions, the negative electrode active material may have excellent electrical conductivity.
[0450] In a specific example, the middle coating layer may be included in an amount of 1 to 20% by weight relative to the total weight of the negative electrode active material. When included in the above range, the conductivity is excellent, and the rupture and destruction of the second hollow core caused by the expansion of the primary particles (or composite silicon particles) can be prevented, so that the capacity reduction is minimized, thereby having excellent long-life characteristics. For example, 1 to 15% by weight, 1 to 10% by weight, 2 to 8% by weight, or 2 to 5% by weight may be included.
[0451] (3) Soft coating layer: In one embodiment, the soft coating layer can be prepared by sintering a soft coating material. In one embodiment, the soft coating material can include one or more of pitch, coke, and a carbon precursor formed from other organic matter. For example, the pitch can include one or more of pyrolysis fuel oil pitch and coal tar pitch.
[0452] In a specific example, the pencil hardness of the soft coating layer measured according to ISO 15184 may be B to 3H. Under the above conditions, the destruction of the negative electrode active material caused by the volume expansion of the composite silicon particles can be prevented, thereby having excellent long life characteristics. For example, the pencil hardness may be B to 1H.
[0453] In a specific example, the thickness of the soft coating layer may be 5 to 100 nm. Under the above conditions, the expansion of the second hollow core caused by the expansion of the primary particles (or composite silicon particles) has an excellent buffering effect, thereby preventing rupture or damage. For example, the thickness may be 5 to 80 nm, 5 to 60 nm, 5 to 30 nm, or 5 to 20 nm.
[0454] In a specific example, the density of the soft coating layer can be 1.5 g / cm 3 Under the above conditions, the soft coating layer can have excellent lightness and structural stability. For example, the density of the soft coating layer can be 0.3 g / cm 3 Up to 1.5g / cm 3 .
[0455] In a specific example, the specific surface area (BET) of the soft coating layer can be 300 m 2 / g or more. Under the above conditions, it can have excellent structural stability. For example, the specific surface area (BET) can be 300 to 2500 m 2 / g.
[0456] In a specific example, the purity (impurity content) of the soft coating layer may be above 1000 ppm. Under the above conditions, the negative electrode active material may have excellent conductivity. For example, it may be 1000 to 5000 ppm.
[0457] In a specific example, the soft coating layer may have a resistivity of 50 μΩ·m or more. Under the above conditions, the soft coating layer may have excellent conductivity of the negative electrode active material. For example, the resistivity may be 50 to 300 μΩ·m.
[0458] In a specific example, the soft coating layer may be included in an amount of 1 to 20% by weight relative to the total weight of the negative electrode active material. When included in the above range, the rupture and destruction of the second hollow core caused by the expansion of the primary particles (or composite silicon particles) can be prevented, and the capacity reduction can be minimized, thereby having excellent long-life characteristics. For example, 1 to 15% by weight, 1 to 10% by weight, 2 to 8% by weight, or 2 to 5% by weight may be included.
[0459] In a specific example, the second coating layer of the negative electrode active material may include a hard (or soft) coating layer and a middle coating layer formed in sequence.
[0460] In a specific example, the crystallinity of the hard coating layer is higher than that of the middle coating layer and the soft coating layer, and the crystallinity of the middle coating layer can be higher than that of the soft coating layer. The crystallinity can be confirmed by conventional XRD (X-ray diffraction) analysis. Under the above conditions, the negative electrode active material can have excellent conductivity, strength and high output characteristics.
[0461] In a specific example, the second coating layer can include a hard (or soft) coating layer and a middle coating layer in a weight ratio of 1:0.5 to 1:3. When included in the above range, the conductivity is excellent, and the rupture and destruction of the second hollow core caused by the expansion of the primary particles (or nano silicon particles) can be prevented, and the capacity reduction is minimized, thereby having excellent long life characteristics. For example, it can be included in a weight ratio of 1:1 to 1:3 or a weight ratio of 1:1.5 to 1:2.5.
[0462] Method for preparing negative electrode active material
[0463] Another aspect of the present invention relates to a method for preparing the negative electrode active material.
[0464] First specific example
[0465] In a specific example, the method for preparing a negative electrode active material includes: a step of preparing composite silicon particles (S10); a step of preparing a primary dry powder (S20); a step of preparing a first intermediate (S30); and a step of preparing a second intermediate (S40).
[0466] Step of preparing composite silicon particles (S10): The step is a step of preparing composite silicon particles. In a specific example, the method for preparing composite silicon particles includes: a step of preparing a first composition comprising nano-silicon particles and carbon particles (S1); a step of arranging the first composition in a cavity, heating the interior of the cavity to 900-1100°C, and reducing the pressure to below normal pressure (S2); a step of allowing hydrocarbon gas and buffer gas to flow into the reduced pressure cavity to contact the first composition (S3); and a step of gradually increasing the pressure inside the cavity for heat treatment while maintaining the increased temperature (S4), wherein the carbon particles include graphene and graphite.
[0467] First composition preparation step (S1): the step is a step of preparing a first composition containing nano-silicon particles and carbon particles.
[0468] In a specific example, conventional nano silicon particles can be used. For example, they can be prepared by drying nano silicon slurry. In a specific example, the preparation process of the nano silicon slurry may include the following steps: adding silicon raw material powder and a dispersant to a solvent and dispersing to prepare a dispersion; and preparing nano silicon particles by crushing the dispersion.
[0469] In a specific example, the solvent may include one or more of water, ethanol, isopropyl alcohol, and potassium hydroxide (KOH). When the solvent is included, the silicon raw material powder will not be oxidized and has excellent mixing and dispersibility.
[0470] In a specific example, the dispersant may include one or more of polyvinyl pyrrolidone, nitrile rubber, hydrogenated nitrile rubber, stearic acid, palmitic acid, oleic acid and lauric acid. For another example, the dispersant may include one or more of stearic acid, pyrolysis fuel oil pitch, coal tar, tar, glucose, sucrose, polyimide, polyacrylic acid (PAA) and polyvinyl alcohol (PVA). When the above dispersant is included, the silicon powder has excellent dispersibility, so that nano silicon slurry containing nano silicon particles can be easily prepared. For example, stearic acid may be included. For example, the dispersant may be mixed with stearic acid and N-methylpyrrolidone (NMP).
[0471] In a specific example, the nano silicon slurry may include 100 parts by weight of silicon raw material powder, 5 to 1500 parts by weight of solvent, and 0.1 to 30 parts by weight of dispersant. Under the above conditions, the miscibility and dispersibility of the nano silicon particles are excellent, and the nano silicon slurry can be easily prepared. For example, the nano silicon slurry may include 100 parts by weight of silicon raw material powder, 800 to 1000 parts by weight of solvent, and 0.5 to 25 parts by weight of dispersant.
[0472] For example, after adding the dispersant in the above-mentioned content to the solvent for mixing, the silicon raw material powder is added and mixed to prepare a dispersion, and the dispersion is pulverized, thereby preparing the nano-silicon slurry.
[0473] In one specific example, the pulverization can be performed by milling. In one specific example, the milling can be performed by beads mill, ball-mill, high energy ball mill, planetary mill, stirred ball mill, vibration mill, etc.
[0474] For example, the ball mill can be made of a chemically inert material that does not react with the silicon powder and other organic components. For example, it can include zirconium oxide (ZrO2). In a specific example, the average particle size of the ball mill can be 0.1 to 1 mm. Under the above conditions, nano silicon particles can be easily prepared.
[0475] The powder size of the nano silicon particles and the negative electrode active material can be easily adjusted by drying the nano silicon slurry. For example, the drying can be carried out using a spray dryer or the like. For example, the drying can be carried out using a spray dryer equipped with a single fluid nozzle, a two fluid nozzle or a four fluid nozzle.
[0476] In a specific example, the primary dry powder may be spherical, polyhedral or elliptical. For example, it may be spherical.
[0477] In a specific example, the average particle size (or size) of the primary dry powder may be 0.1 to 15 μm. Under the above conditions, the primary dry powder may have excellent mixing and forming properties.
[0478] In one specific example, when a single-fluid nozzle is used to spray-dry the nano-silicon slurry, the outlet temperature of the spray dryer is set to 70-130°C, and the average particle size of the primary dry powder prepared under the condition of a gas flow rate of 650-850sccm can be 7-14μm. In another specific example, when a four-fluid nozzle is used to spray-dry the nano-silicon slurry, the average particle size of the primary dry powder can be 0.1-8μm.
[0479] In one embodiment, the carbon particles may include graphene and graphite.
[0480] Conventional carbon particles can be used. The carbon particles may be spherical, polyhedral, flake (flat), plate-like or elliptical.
[0481] In one specific example, the density of the carbon particles can be 2.5 g / cm 3 Under the above conditions, the carbon particles can have excellent conductivity and lightness. For example, the density of the carbon particles can be 0.3 to 2.5 g / cm 3 .
[0482] For example, the carbon particles may include a pencil hardness of 4H to 6H, a resistivity of 3 to 5 μΩ·m, and a density of 1.8 to 2.5 g / cm3 as measured according to ISO 15184. 3 The first carbon particles.
[0483] For another example, the carbon particles may include a pencil hardness of B to 3H measured according to ISO 15184, an electrical conductivity of 50 to 300 μΩ·m, and a density of 0.3 to 1.5 g / cm 2 of the second carbon particles.
[0484] In a specific example, the purity (impurity content) of the carbon particles may be less than 100 ppm. Under the above conditions, the negative electrode active material may have excellent conductivity.
[0485] In another specific example, the purity (impurity content) of the carbon particles may be greater than 300 ppm, for example, 300 to 800 ppm.
[0486] In a specific example, the carbon particles may contain graphite and graphene in a weight ratio of 1:0.5 to 1:6. When contained in the above weight ratio, the negative electrode active material has excellent conductivity and capacity characteristics, and can have excellent high output and long life characteristics.
[0487] In a specific example, the average size of the graphite may be 10 to 5000 nm. The size may mean the maximum length or diameter (particle size) of the graphite. For example, the graphite may be flaky or spherical. For example, the graphite may be 50 to 5000 nm, 100 to 5000 nm, 300 to 5000 nm, 500 to 5000 nm, or 500 to 1000 nm.
[0488] In a specific example, the average size of the graphene may be 10 to 5000 nm. The size may mean the maximum length or diameter (particle size) of the graphene. For example, the graphene may be spherical. For example, the graphene may be 50 to 5000 nm, 100 to 5000 nm, 300 to 5000 nm, 500 to 5000 nm, or 500 to 1000 nm.
[0489] In a specific example, the forming of the graphene may include: a step of milling the graphite.
[0490] The formation of the graphene may include a step of separating the graphite layers while refining the graphite particles of one or more of natural graphite and artificial graphite by a milling process. The milling may be performed, for example, for 20 to 80 minutes or 30 to 70 minutes. Under the above conditions, graphene can be easily formed from the graphite.
[0491] In a specific example, the graphene may include a layer structure of 1 to 10 layers. Under the above conditions, the conductivity and capacity characteristics of the negative electrode active material are excellent, and it may have excellent high output and long life characteristics. For example, the graphene may include a layer structure of 2 to 8 layers or 2 to 5 layers.
[0492] In a specific example, the first composition may include 100 parts by weight of nano silicon particles and 0.1 to 20 parts by weight of carbon particles. Under the above conditions, the first coating layer can be easily formed. For example, relative to the 100 parts by weight of nano silicon particles, the carbon particles may include 0.1 to 15 parts by weight, 0.1 to 10 parts by weight, or 0.1 to 5 parts by weight.
[0493] The step of heating and decompressing the cavity (S2) is to place the first composition in the cavity, heat the interior of the cavity to 900-1100°C, and decompress the cavity to below normal pressure.
[0494] The temperature inside the cavity is raised to 900-1100° C. When the temperature is raised to below 900° C., the first coating layer is not easily formed, and when the temperature is raised to a temperature exceeding 1100° C., the first coating layer is formed to a thickness beyond necessity, thereby increasing the resistance value, and therefore, the movement of lithium ions may be slowed down or the lithium storage space of silicon may be reduced. In addition, due to the increase in carbon precursor gas consumption and the increase in energy cost, the economic efficiency may be reduced.
[0495] In a specific example, the heat treatment can be performed under a vacuum condition lower than normal pressure. Under the above conditions, the hydrocarbon gas is uniformly diffused between the nano-silicon particles, and a first coating layer can be formed on the outer peripheral surface of the nano-silicon particles during the heat treatment. -1 ~10 -6 The vacuum condition is reduced to torr.
[0496] The hydrocarbon and buffer gas inflow step (S3) is a step of flowing hydrocarbon gas and buffer gas into the chamber with increased temperature and reduced pressure to contact the first composition.
[0497] In a specific example, the buffer gas may include nitrogen (N2) gas. When the above buffer gas is included, the buffer gas and the hydrocarbon gas easily penetrate between the nano-silicon particles arranged in the reduced pressure cavity, so that the first coating layer can be uniformly formed. In particular, the hydrocarbon gas easily penetrates between the plurality of nano-silicon particles, so that the first coating layer has excellent homogeneity and can be formed into a uniform thickness.
[0498] Pressure increasing and heat treatment step (S4): This step is a step of gradually increasing the pressure inside the chamber to perform heat treatment while maintaining the increased temperature.
[0499] Figure 4 1 is a graph showing the change in pressure inside the cavity over time when preparing composite silicon particles according to a specific example of the present invention. Figure 4 , the composite silicon particles are decompressed and heated in a cavity containing the first composition, and after the hydrocarbon gas and the buffer gas flow in, the pressure inside the decompressed cavity is gradually increased while the temperature is maintained, so that a first coating layer including a middle coating layer can be formed on the outer surface of the nano silicon particles. When formed under the above conditions, a middle coating layer with uniform thickness and excellent homogeneity can be formed. In particular, the hydrocarbon gas can easily penetrate between multiple nano silicon particles, so that the middle coating layer has excellent homogeneity and can be formed to a uniform thickness. For example, the pressure inside the cavity is gradually increased to 10 1 Support up to 10 5torr to be able to prepare composite silicon particles.
[0500] For example, as the composite silicon particles, a silicon carbide layer may be formed between the nano silicon particles and the intermediate coating layer.
[0501] In one specific example, the silicon carbide layer may have a higher hardness than the mid-coating layer.
[0502] For example, the pencil hardness of the silicon carbide layer measured according to ISO 15184 may be 7H or more. For example, it may be 8H or more, or 10H or more, or 8H to 10H.
[0503] The middle coating layer may be formed by heat treating one or more of a hydrocarbon gas and carbon black. For example, the hydrocarbon gas may include methane (CH4), ethane (C2H6), propane (C3H8), butane (C4H 10 ), pentane (C5H 12 )
[0504] In a specific example, the medium coating layer may be in an amorphous state or a crystalline state. Under the above conditions, it may have excellent strength and durability.
[0505] In a specific example, the pencil hardness of the middle coating layer measured according to ISO 15184 may be greater than 2H and less than 4H. Under the above conditions, the cracking or destruction of the negative electrode active material caused by the volume expansion of the nano silicon particles can be prevented, thereby having excellent long life characteristics. For example, the pencil hardness may be 2H to 3H.
[0506] In a specific example, the thickness of the middle coating layer can be 3 to 50 nm. Under the above conditions, the rupture or destruction of the negative electrode active material caused by the expansion of the nano silicon particles can be prevented, and excellent high output and conductivity can be achieved. For example, the thickness can be 3 to 15 nm, 5 to 15 nm, 6 to 15 nm, or 10 to 15 nm.
[0507] In one embodiment, the density of the middle coating layer can be more than 1.5 g / cm 3 And 1.8g / cm 3 Under the above conditions, the coating layer can have excellent lightness and structural stability. For example, the density of the coating layer can be more than 1.5 g / cm 3 And 1.7g / cm 3 the following.
[0508] In a specific example, the specific surface area (BET) of the middle coating layer can be 100 to 200 m 2Under the above conditions, the structure can be excellently stable.
[0509] In a specific example, the purity (impurity content) of the middle coating layer may be less than 500 ppm. Under the above conditions, the negative electrode active material may have excellent conductivity.
[0510] In a specific example, the electrical conductivity (resistivity) of the middle coating layer may be 20 to 40 μΩ·m. Under the above conditions, the negative electrode active material may have excellent electrical conductivity.
[0511] The step of preparing a primary dry powder (S20): the step is to dry the mixed slurry containing the composite silicon particles, carbon particles and a solvent to prepare a primary dry powder.
[0512] In a specific example, the solvent may include one or more of water, an alcohol solvent, an amide solvent, an ester solvent and a hydrocarbon solvent. When the above solvents are included, excellent miscibility and operability may be obtained. As the alcohol solvent, one or more of methanol, ethanol, isopropanol and butanol may be included. As the amide solvent, one or more of N-methyl-2-pyrrolidone (NMP), dimethylacetamide (DMAC) and dimethylformamide (DMF) may be included. As the hydrocarbon solvent, one or more of toluene and xylene may be included.
[0513] In a specific example, the composite silicon particles may be included in an amount of 25 to 95% by weight relative to the total weight of the mixed slurry. Under the above conditions, the composite silicon particles have excellent miscibility and dispersibility, thereby preparing a negative electrode active material having a uniform size. For example, the composite silicon particles may be included in an amount of 30 to 85% by weight, 35 to 80% by weight, 35 to 70% by weight, 35 to 60% by weight, 40 to 50% by weight, or 45 to 50% by weight.
[0514] In one specific example, the carbon particles may be the same particles as those described above. In one specific example, the carbon particles may include graphene and graphite.
[0515] Conventional carbon particles can be used. The carbon particles may be spherical, polyhedral, flake (flat), plate-like or elliptical.
[0516] In a specific example, the forming of the graphene may include: a step of milling the graphite.
[0517] For example, the carbon particles may be included in an amount of 0.1 to 15 wt % relative to the total weight of the mixed slurry. Under the above conditions, the carbon particles may have excellent miscibility and dispersibility. For example, the carbon particles may be included in an amount of 0.1 to 15 wt %, 0.5 to 10 wt %, 1 to 10 wt %, 2 to 8 wt % or 3 to 8 wt %.
[0518] In a specific example, the mixed slurry may contain 5 to 75% by weight of the solvent relative to the total weight of the mixed slurry. Under the above conditions, it can have excellent miscibility and dispersibility. For example, it may contain 10 to 70% by weight, 10 to 65% by weight, 15 to 60% by weight, 15 to 50% by weight, 20 to 50% by weight, or 25 to 50% by weight of the solvent.
[0519] The powder size of the negative electrode active material can be easily adjusted by drying the mixed slurry. For example, the drying can be performed using a spray dryer or the like. For example, the drying can be performed using a spray dryer equipped with a single-fluid nozzle, a two-fluid nozzle, or a four-fluid nozzle.
[0520] In a specific example, the primary dry powder may be spherical, polyhedral or elliptical. For example, it may be spherical.
[0521] The step of preparing a first intermediate (S30): the step may be a step of preparing a first intermediate using the primary dry powder and the first coating material.
[0522] In a specific example, the first coating material may include one or more of a hard coating material, a middle coating material, and a soft coating material.
[0523] In one specific example, the first intermediate body may be prepared by mixing the primary dry powder and the hard coating material and sintering the mixture.
[0524] The hard coating material forms the hollow core and ensures excellent hardness and strength, thereby preventing the negative electrode active material from being destroyed when the composite silicon particles are expanded and having excellent electrical characteristics.
[0525] For example, the hard coating material may include a carbon-based material.
[0526] In a specific example, the pencil hardness of the hard coating material measured according to ISO 15184 may be 4H or more. Under the above conditions, the negative electrode active material can be prevented from being destroyed when the composite silicon particles expand, and excellent electrical properties can be obtained. For example, the pencil hardness may be 4H to 6H. For example, the hard coating material may include a carbon material having a pencil hardness of 4H to 6H.
[0527] For example, as the hard coating material, NanoMollisAdamas product of Lemon Energy Co., Ltd. of Korea may be used.
[0528] The hard coating material may be amorphous. In addition, the hard coating material is self-assembled, has excellent isotropic properties, and has excellent thermal stability, so that the structure does not change even at high temperatures (about 3000° C.).
[0529] The hard coating material has high gas impermeability, and can have excellent chemical resistance and electrical conductivity. In addition, the hard coating material can be dust-free, and the purity (impurity content) can be 5 ppm or less or 2 ppm or less. Under the above conditions, while having excellent strength and electrical properties, it can have excellent conductivity of the negative electrode active material.
[0530] In a specific example, the hard coating material may have a resistivity of 3 to 5 μΩ·m. Under the above conditions, the negative electrode active material may have excellent conductivity.
[0531] In a specific example, the average particle size (d50) of the hard coating material may be 3 nm to 2.5 μm. Under the above conditions, the first intermediate may be easily formed. For example, the average particle size may be 5 to 500 nm, 10 to 500 nm, or 15 to 200 nm.
[0532] In a specific example, the sintering can be performed at a temperature of 900-1050° C. Under the above conditions, the first intermediate can be easily formed. For example, the sintering can be performed at a temperature of 965-1000° C.
[0533] For example, the sintering may be performed under an inert gas atmosphere. The inert gas may include nitrogen.
[0534] For example, the sintered product is subjected to a conventional dry pulverization process such as a disc mill, an air classifier mill (ACM), a jet mill, a pin mill, etc., and then classified to prepare the first intermediate.
[0535] In another specific example, the primary dry powder may be heat-treated using a coating material to prepare the first intermediate. For example, the primary dry powder may be heat-treated under a hydrocarbon gas atmosphere to prepare the first intermediate. For another example, the primary dry powder may be mixed with carbon black and heat-treated to form the first intermediate.
[0536] In a specific example, the coating material may include one or more of hydrocarbon gas and carbon black. For example, the hydrocarbon gas may include methane (CH4), ethane (C2H6), propane (C3H8), butane (C4H 10 ), pentane (C5H 12 )
[0537] For example, the heat treatment may be performed at a temperature of 850 to 970° C. Under the above conditions, the first intermediate may be easily formed. For example, the heat treatment may be performed at a temperature of 890 to 910° C.
[0538] In one specific example, the heat treatment may be performed under vacuum conditions. Under the above conditions, the hydrocarbon gas is uniformly diffused between the primary dry powder particles arranged in the cavity, and a uniform intermediate coating layer may be formed during the heat treatment. For example, the heat treatment may be performed under vacuum conditions. -1 ~10 -6 The process is carried out under vacuum conditions of torr.
[0539] In a specific example, the step of preparing the first intermediate may include: heating the interior of the cavity where the primary dry powder is arranged to 850-970° C., and reducing the pressure to 10 -1 to 10- 6 The steps of increasing the pressure by 1 torr; allowing hydrocarbon gas to flow into the decompressed cavity so that the primary dry powder contacts the hydrocarbon gas; and gradually increasing the pressure inside the cavity while maintaining the elevated temperature to form a coating layer on the outer peripheral surface of the primary dry powder through thermal decomposition of the hydrocarbon gas to prepare a first intermediate.
[0540] When the pressure inside the cavity is reduced under the above conditions, the hydrocarbon gas can easily penetrate between the primary dry powders arranged in the cavity, so that the middle coating layer can be uniformly formed. In particular, the hydrocarbon gas easily penetrates between the plurality of primary dry powders, so that the middle coating layer has excellent homogeneity and can be formed with a uniform thickness, thereby forming a first intermediate.
[0541] In addition, when the pressure inside the chamber is increased under the above conditions, a middle coating layer having a uniform gas thickness and excellent homogeneity is formed on the outer peripheral surface of the primary dry powder, thereby preparing a first intermediate.
[0542] At this time, the pressure inside the cavity can be gradually increased from vacuum. For example, the pressure inside the cavity can be gradually increased to 10 1 Support up to 10 5 torr to prepare the first intermediate.
[0543] In another specific example, the first intermediate can be prepared by mixing the primary dry powder with a soft coating material and sintering. For example, the primary dry powder and the soft coating material can be mixed and sintered at 850 to 975° C. to prepare. When sintered under the temperature conditions, the first intermediate including the soft coating layer can be easily formed.
[0544] In a specific example, the soft coating material may include one or more of pitch, coke, and carbon precursors formed from other organic substances. For example, the pitch may include one or more of pyrolysis fuel oil pitch and coal tar pitch.
[0545] In a specific example, the first intermediate body can be formed by mixing the primary dry powder and a soft coating liquid including a soft coating material and a solvent and then sintering the mixture.
[0546] In a specific example, the solvent may include one or more of water, an alcohol solvent, an amide solvent, an ester solvent and a hydrocarbon solvent. When the above solvents are included, excellent miscibility and operability may be obtained. As the alcohol solvent, one or more of methanol, ethanol, isopropanol and butanol may be included. As the amide solvent, one or more of N-methyl-2-pyrrolidone (NMP), dimethylacetamide (DMAC) and dimethylformamide (DMF) may be included. As the hydrocarbon solvent, one or more of toluene and xylene may be included.
[0547] In a specific example, the average particle size (d50) of the soft coating material may be 0.03 to 10 μm. Under the above conditions, the first intermediate may be easily formed. For example, the average particle size may be 0.3 to 5 μm.
[0548] In a specific example, the step of preparing the first intermediate includes: sintering or heat treating a compressed product prepared by mixing the primary dry powder and the first coating material and pressurizing to 20 to 60 atm. When the compressed product is prepared under the pressurized conditions, the negative electrode active material can have excellent electrical characteristics and long life and capacity characteristics by adjusting the internal void volume of the negative electrode active material.
[0549] Step of preparing a second intermediate body (S40): This step is a step of forming a second coating layer on the outer peripheral surface of the first intermediate body to prepare the second intermediate body.
[0550] The second coating layer includes one or more of a hard coating layer, a middle coating layer and a soft coating layer.
[0551] In one specific example, the second coating layer has a hardness different from that of the first hollow core.
[0552] In a specific example, the hard coating layer can be prepared by mixing the first intermediate and the hard coating material and sintering. The hard coating material can use the same material as in the first intermediate preparation step (S30). In a specific example, the sintering can be performed at a temperature of 900 to 1050° C. Under the above conditions, the second intermediate can be easily prepared.
[0553] The middle coating layer can be prepared by heat treating the first intermediate and the middle carbon hard material. For example, the second intermediate can be prepared by heat treating the first intermediate under a hydrocarbon gas atmosphere. For another example, the second intermediate can be formed by mixing the first intermediate and carbon black and heat treating them.
[0554] In a specific example, the heat treatment may be performed under vacuum conditions. Under the above conditions, the hydrocarbon gas is uniformly diffused between the first intermediate particles arranged in the cavity, and a uniform intermediate coating layer may be formed during the heat treatment. For example, the heat treatment may be performed under vacuum conditions. -1 ~10 -6 The process is carried out under vacuum conditions of torr.
[0555] In a specific example, the step of preparing the second intermediate may include: heating the interior of the cavity where the first intermediate is arranged to 850-970° C. and reducing the pressure to 10 -1 Up to 10 -6 The steps of increasing the pressure by 1 torr; allowing hydrocarbon gas to flow into the reduced-pressure chamber so that the first intermediate is in contact with the hydrocarbon gas; and gradually increasing the pressure inside the chamber while maintaining the increased temperature, forming a middle coating layer on the outer peripheral surface of the first intermediate through thermal decomposition of the hydrocarbon gas to prepare a second intermediate.
[0556] The soft coating layer can be prepared by mixing the first intermediate and the soft coating material and sintering. The soft coating material can use the same material as in the step (S30) of preparing the first intermediate. In a specific example, the sintering can be performed at a temperature of 850 to 975° C. Under the above conditions, the second intermediate can be easily prepared.
[0557] In a specific example, the hard coating layer may have high crystallinity. Under the above conditions, the hard coating layer may have excellent durability and strength.
[0558] In a specific example, the thickness of the hard coating layer may be 5 to 100 nm. Under the above conditions, the hardness and mechanical strength are excellent, thereby preventing the negative electrode active material from being broken or damaged even when the composite silicon particles expand. For example, the thickness may be 5 to 60 nm, 5 to 30 nm, or 5 to 20 nm.
[0559] In one embodiment, the density of the hard coating layer can be greater than 1.8 g / cm 3 And 2.8g / cm 3 Under the above conditions, the hard coating layer can have excellent lightness and structural stability. For example, the density of the hard coating layer can be 1.85 to 2.5 g / cm 3 .
[0560] In one specific example, the specific surface area (BET) of the hard coating layer can be 100 m 2 Under the above conditions, the structure can be excellently stable.
[0561] In a specific example, the purity (impurity content) of the hard coating layer may be 100 ppm or less. Under the above conditions, the negative electrode active material may have excellent conductivity.
[0562] In a specific example, the hard coating layer may have a resistivity of 3 to 5 μΩ·m. Under the above conditions, the negative electrode active material may have excellent conductivity.
[0563] In a specific example, the pencil hardness of the hard coating layer measured according to ISO 15184 may be 4H or more. Under the above conditions, the durability and strength of the hard coating layer are excellent, and lithium ions are embedded in the composite silicon particles, thereby having an excellent effect of preventing the first hollow core (or negative electrode active material) from being broken or damaged during expansion. For example, the pencil hardness of the hard coating layer may be 4.5H to 7H or 4.5H to 6H.
[0564] In a specific example, the middle coating layer can be amorphous or crystalline. Under the above conditions, it can have excellent strength and durability.
[0565] In a specific example, the thickness of the middle coating layer can be 5 to 100 nm. Under the above conditions, the hardness, flexibility and mechanical strength are excellent, so even when the composite silicon particles expand, the negative electrode active material can be prevented from being broken or damaged. For example, the thickness can be 5 to 60 nm, 5 to 30 nm or 5 to 20 nm.
[0566] In a specific example, the pencil hardness of the middle coating layer measured according to ISO 15184 may be greater than 2H and less than 4H. Under the above conditions, the cracking and destruction of the negative electrode active material caused by the expansion of the composite silicon particles can be prevented, thereby having excellent long life characteristics. For example, the pencil hardness may be 2.5H to 3.5H.
[0567] In one embodiment, the density of the middle coating layer can be more than 1.5 g / cm 3 And 1.8g / cm 3 Under the above conditions, the coating layer can have excellent lightness and structural stability. For example, the density of the coating layer can be more than 1.5 g / cm 3 And 1.7g / cm 3 the following.
[0568] In a specific example, the specific surface area (BET) of the middle coating layer can be 100 to 200 m 2 Under the above conditions, the structure can be excellently stable.
[0569] In a specific example, the purity (impurity content) of the middle coating layer may be less than 500 ppm. Under the above conditions, the negative electrode active material may have excellent conductivity.
[0570] In a specific example, the electrical conductivity (resistivity) of the middle coating layer may be 20 to 40 μΩ·m. Under the above conditions, the negative electrode active material may have excellent electrical conductivity.
[0571] In a specific example, the middle coating layer may include 1 to 20 weight % relative to the total weight of the negative electrode active material. When included in the above range, the flexibility, durability and structural stability of the negative electrode active material can be excellent, and the electrical properties can be excellent. For example, it may include 1 to 15 weight %, 1 to 10 weight %, 2 to 10 weight % or 2 to 5 weight %.
[0572] In a specific example, the thickness of the soft coating layer may be 5 to 100 nm. Under the above conditions, flexibility and mechanical strength are excellent, so even when the composite silicon particles expand, the negative electrode active material can be prevented from being broken or damaged. For example, the thickness may be 5 to 60 nm, 5 to 30 nm, or 5 to 20 nm.
[0573] In a specific example, the pencil hardness of the soft coating layer measured according to ISO 15184 may be less than 2H. Under the above conditions, the destruction of the negative electrode active material caused by the volume expansion of the composite silicon particles can be prevented, thereby having excellent long life characteristics. For example, the pencil hardness may be B to 3H or B to 1H.
[0574] In a specific example, the density of the soft coating layer can be 1.5 g / cm 3 Under the above conditions, the soft coating layer can have excellent lightness and structural stability. For example, the density of the soft coating layer can be 0.3 g / cm 3 Up to 1.4g / cm 3 .
[0575] In a specific example, the specific surface area (BET) of the soft coating layer can be 300 m 2 / g or more. Under the above conditions, it can have excellent structural stability. For example, the specific surface area (BET) can be 300 to 2500 m 2 / g.
[0576] In a specific example, the purity (impurity content) of the soft coating layer may be above 1000 ppm. Under the above conditions, the negative electrode active material may have excellent conductivity. For example, it may be 1000 to 5000 ppm.
[0577] In a specific example, the soft coating layer may have a resistivity of 50 μΩ·m or more. Under the above conditions, the soft coating layer may have excellent conductivity of the negative electrode active material. For example, the resistivity may be 50 to 300 μΩ·m.
[0578] In a specific example, the second coating layer may include 1 to 40 weight % relative to the total weight of the negative electrode active material. When included in the above range, the durability and structural stability of the negative electrode active material can be excellent, and the electrical properties can be excellent. For example, it may include 1 to 35 weight %, 1 to 30 weight %, 1 to 25 weight %, 1 to 20 weight %, 1 to 15 weight %, 1 to 10 weight %, 2 to 10 weight % or 2 to 5 weight %.
[0579] In a specific example, the second coating layer and the first hollow core can be included in a weight ratio of 1:0.5 to 1:5. When included in the above weight ratio range, even when the volume of the composite silicon particles expands, the rupture and destruction of the negative electrode active material can be prevented, and excellent high output and long life characteristics can be achieved. For example, the second coating layer and the first hollow core can be included in a weight ratio of 1:1 to 1:4, a weight ratio of 1:1 to 1:3, or a weight ratio of 1:1.5 to 1:3.
[0580] In a specific example, the second coating layer may include a soft (or hard) coating layer and a hard (or soft) coating layer sequentially formed on the outer peripheral surface of the first hollow core.
[0581] For example, the second intermediate can be prepared by mixing the first intermediate and a soft coating material and sintering them at 850-975°C to form a soft coating layer, and mixing the first intermediate having the soft coating layer and a hard coating material and sintering them at 900-1050°C to form a hard coating layer.
[0582] For example, the second coating layer may include the soft coating layer and the hard coating layer in a weight ratio of 1:0.5 to 1:4. When included in the above weight ratio range, the negative electrode active material can be prevented from being broken and damaged during the expansion of the composite silicon particles, and can have excellent conductivity, high output and long life characteristics. For example, it can be included in a weight ratio of 1:1 to 1:2.
[0583] In another specific example, the second coating layer may include a soft (or hard) coating layer, a hard (or soft) coating layer, and a middle coating layer sequentially formed on the outer peripheral surface of the first hollow core.
[0584] For example, the second coating layer may include the soft coating layer, the hard coating layer, and the middle coating layer in a weight ratio of 1:0.5 to 4:0.5 to 5. When included in the above weight ratio range, the negative electrode active material can be prevented from breaking and damaging when the composite silicon particles expand, and can have excellent conductivity, high output, and long life characteristics. For example, it includes a weight ratio of 1:1 to 2:0.5 to 3.
[0585] For example, the second intermediate can be prepared by mixing the first intermediate and a soft coating material, sintering at 850-975° C. to form a soft coating layer, mixing the first intermediate having the soft coating layer and a hard coating material, sintering at 900-1050° C. to form a hard coating layer, and placing the first intermediate having the hard coating layer in a cavity, raising the temperature inside the cavity to 850-970° C., and reducing the pressure to 10 -1 Up to 10 -6 The steps of: allowing hydrocarbon gas to flow into the decompressed cavity so that the first intermediate body is in contact with the hydrocarbon gas; and gradually increasing the pressure inside the cavity while maintaining the elevated temperature, thereby forming a middle coating layer on the peripheral surface of the hard coating layer of the first intermediate body through thermal decomposition of the hydrocarbon gas.
[0586] The second intermediate includes: a first hollow core, having a first hollow portion formed therein; composite silicon particles, filled in the first hollow portion, and including nano-silicon particles having a first coating layer formed on the surface; carbon particles, filled in the first hollow portion; and a second coating layer, formed on the outer peripheral surface of the first hollow core, the first coating layer including a middle coating layer, the second coating layer including one or more of a hard coating layer, a middle coating layer and a soft coating layer, the hardness of the hard coating layer is higher than that of the middle coating layer, the hardness of the middle coating layer is higher than that of the soft coating layer, and the hardness of the first hollow core and the second coating layer are different.
[0587] For example, the carbon particles may include a pencil hardness of B to 3H measured according to ISO 15184, an electrical conductivity of 5 to 300 μΩ·m, and a density of 0.3 to 1.5 g / cm 2 The first carbon particles may include graphite and graphene. The graphite and graphene may be as described above.
[0588] For example, the carbon particles may also include a pencil hardness of 4H to 7H measured according to ISO 15184, a resistivity of 3 to 50 μΩ·m, and a density of 1.8 to 2.5 g / cm 3 of the second carbon particles.
[0589] In a specific example, the average size of the second carbon particles may be 1 to 3000 nm. The size may mean the maximum length or diameter (particle size) of the second carbon particles. For example, the second carbon particles may be flake-shaped or spherical. For example, the second carbon particles may be 1 to 2500 nm, 3 to 1500 nm, 5 to 1000 nm, 10 to 500 nm, 30 to 500 nm, or 50 to 200 nm.
[0590] In a specific example, the first carbon particles and the second carbon particles may be contained in a weight ratio of 1:0.5 to 1:3. When contained in the above weight ratio, the negative electrode active material has excellent conductivity and capacity characteristics, and can have excellent high output and long life characteristics.
[0591] In a specific example, the first coating layer may further include a silicon carbide (SiC) layer formed between the nano-silicon particles and the middle coating layer.
[0592] In a specific example, the number of composite silicon particles filled in the first hollow portion may be set in consideration of the maximum expandable volume when lithium ions are embedded. For example, when the volume of the composite silicon particles (nano silicon particles) expands by 2 times, it may be assumed that the first hollow portion is filled with a hexagonal close packing (HCC) or a face-centered cubic (FCC) structure for calculation.
[0593] The number of composite silicon particles filled in the first hollow portion may be set so that the total volume of expanded composite silicon particles formed by lithium ions being intercalated into the composite silicon particles satisfies or is smaller than the volume of the first hollow portion.
[0594] In a specific example, the number (n) of composite silicon particles filled in the first hollow portion may satisfy the condition of the following formula 1:
[0595] Formula 1:
[0596] (In the above formula 1, d is the relative diameter of the expanded composite silicon particle derived from the following formula 1-1, and q is the relative diameter of the expanded composite silicon particle at the center of the first hollow portion derived from the following formula 1-2)
[0597] Formula 1-1: d = r' / R
[0598] (In the above formula 1-1, R is the radius of the first hollow portion, r' is the radius of the expanded composite silicon particle, and r'=1.2599*a+b (a is the radius of the composite silicon particle, and b is the thickness of the first coating layer))
[0599] Formula 1-2: q = 1-2*d
[0600] (In the above formula 1-2, the d is as defined above).
[0601] In a specific example, the negative electrode active material includes first composite silicon particles and second composite silicon particles having radii r1 and r2, respectively, and the number of particles (n1 and n2) of the first composite silicon and the second composite silicon filled in the first hollow portion may satisfy the condition of the following formula 2:
[0602] Formula 2:
[0603] (In the above formula 2, r1' and r2' are the radii of the first expanded composite silicon particle and the second expanded composite silicon particle, respectively, R is the radius of the first hollow portion, r1' and r2' are 1.2599*a1+b1 and 1.2599*a2+b2, respectively (a1 and b1 are the radius of the first nano-silicon particle and the thickness of the first coating layer, and a2 and b2 are the radius of the second nano-silicon particle and the thickness of the first coating layer)).
[0604] In a specific example, the radius of the composite silicon particle filled in the first hollow portion can be derived by assuming that the total volume of the first coating layer of the composite silicon particle when expanded twice is the same as the total volume of the first coating layer of the composite silicon particle that is not expanded.
[0605] The radius r1 of the expanded composite silicon particle can satisfy the following equation 2-1:
[0606] Formula 2-1: (r1') 3 =(a1') 3 +(r1) 3 -(a1) 3
[0607] (In the above formula 2-1, a1 is the radius of the nano-silicon particle, r1 is the radius of the composite silicon particle, and a1' is the radius of the nano-silicon particle after expansion)
[0608] In a specific example, the negative electrode active material includes first composite silicon particles and second composite silicon particles having radii r1 and r2, respectively, and the number of particles (n1 and n2) of the first composite silicon and the second composite silicon filled in the first hollow portion may satisfy the condition of the following formula 2-2:
[0609] Formula 2-2:
[0610] (In the above formula 2, r1' and r2' are the radii of the first expanded composite silicon particle and the second expanded composite silicon particle, respectively, R is the radius of the first hollow portion, and r1' and r2' respectively satisfy (r1') 3 =(a1') 3 +(r1) 3 -(a1) 3 and (r2') 3 =(a2') 3 +(r2) 3 -(a2) 3 (In the above formula 2-2, a1 is the radius of the nano-silicon particle, r1 is the radius of the composite silicon particle, and a1' is the radius of the nano-silicon particle after expansion)).
[0611] The sizes of the first and second composite silicon particles may be the same or different. Under the above conditions, the composite silicon particles have excellent dispersibility, can prevent the first hollow core from breaking and destroying when the composite silicon particles expand, and can have excellent high capacity and high output characteristics.
[0612] Second specific example
[0613] In another specific example of the present invention, the method for preparing a negative electrode active material includes: a step of preparing composite silicon particles (S11); a step of preparing a primary dry powder (S21); a step of preparing a first mixture (S31); and a step of preparing a first intermediate (S41).
[0614] The step of preparing composite silicon particles (S11): The step is a step of preparing composite silicon particles. The step is a step of preparing composite silicon particles. In a specific example, the method for preparing composite silicon particles includes: a step of preparing a first composition including nano-silicon particles and carbon particles (S1); a step of arranging the first composition in a cavity, heating the interior of the cavity to 900-1100°C, and reducing the pressure to below normal pressure (S2); a step of allowing hydrocarbon gas and buffer gas to flow into the reduced pressure cavity to contact the first composition (S3); and a step of gradually increasing the pressure inside the cavity for heat treatment while maintaining the increased temperature (S4), wherein the carbon particles include graphene and graphite.
[0615] The steps (S1) to (S4) can be performed in the same manner as the above-mentioned steps of preparing the composite silicon particles, and thus detailed descriptions thereof are omitted.
[0616] The step of preparing a primary dry powder (S21): the step is a step of preparing a primary dry powder by drying a mixed slurry including the composite silicon particles, carbon particles, a first coating material and a solvent.
[0617] The carbon particles may be the same particles as those described above. For example, the carbon particles may include one or more of graphene and graphite. The carbon particles may be spherical, polyhedral, flaky (flat), plate-like or elliptical. In a specific example, the formation of the graphene may include: a step of milling the graphite.
[0618] In a specific example, the first coating material includes one or more of a hard coating material and a soft coating material.
[0619] The hard coating material may ensure excellent hardness and strength, thereby preventing the negative electrode active material from being destroyed when the composite silicon particles expand, and may have excellent electrical characteristics.
[0620] For example, the hard coating material may include a carbon-based material.
[0621] In a specific example, the pencil hardness of the hard coating material measured according to ISO 15184 may be 4H or more. Under the above conditions, the negative electrode active material can be prevented from being destroyed when the composite silicon particles expand, and excellent electrical properties can be obtained. For example, the pencil hardness may be 4H to 6H. For example, the hard coating material may include a carbon material having a pencil hardness of 4H to 6H.
[0622] For example, as the hard coating material, NanoMollisAdamas product of Lemon Energy Co., Ltd. of Korea may be used.
[0623] The hard coating material may be amorphous. In addition, the hard coating material is self-assembled, has excellent isotropic properties, and has excellent thermal stability, so that the structure does not change even at high temperatures (about 3000° C.).
[0624] The hard coating material has high gas impermeability, and can have excellent chemical resistance and electrical conductivity. In addition, the hard coating material can be dust-free, and the purity (impurity content) can be 5 ppm or less or 2 ppm or less. Under the above conditions, while having excellent strength and electrical properties, it can have excellent conductivity of the negative electrode active material.
[0625] In a specific example, the hard coating material may have a resistivity of 3 to 5 μΩ·m. Under the above conditions, the negative electrode active material may have excellent conductivity.
[0626] In a specific example, the average particle size (d50) of the hard coating material may be 3 nm to 2.5 μm, for example, 5 to 500 nm, 10 to 500 nm, or 15 to 200 nm.
[0627] In a specific example, the soft coating material may include one or more of pitch, coke, and carbon precursors formed from other organic substances. For example, the pitch may include one or more of pyrolysis fuel oil pitch and coal tar pitch.
[0628] In a specific example, the average particle size (d50) of the soft coating material may be 0.03 to 10 μm, for example, 0.3 to 5 μm.
[0629] In a specific example, the solvent may include one or more of water, an alcohol solvent, an amide solvent, an ester solvent and a hydrocarbon solvent. When the above solvents are included, excellent miscibility and operability may be obtained. As the alcohol solvent, one or more of methanol, ethanol, isopropanol and butanol may be included. As the amide solvent, one or more of N-methyl-2-pyrrolidone (NMP), dimethylacetamide (DMAC) and dimethylformamide (DMF) may be included. As the hydrocarbon solvent, one or more of toluene and xylene may be included.
[0630] In a specific example, the composite silicon particles may be included in an amount of 25 to 95% by weight relative to the total weight of the mixed slurry. Under the above conditions, the composite silicon particles have excellent miscibility and dispersibility, thereby preparing a negative electrode active material having a uniform size. For example, the composite silicon particles may be included in an amount of 30 to 85% by weight, 35 to 80% by weight, 35 to 70% by weight, 35 to 60% by weight, 40 to 50% by weight, or 45 to 50% by weight.
[0631] For example, the carbon particles may be included in an amount of 0.1 to 15 wt % relative to the total weight of the mixed slurry. Under the above conditions, the carbon particles may have excellent miscibility and dispersibility. For example, the carbon particles may be included in an amount of 0.1 to 15 wt %, 0.5 to 10 wt %, 1 to 10 wt %, 2 to 8 wt % or 3 to 8 wt %.
[0632] In a specific example, the first coating material may be included in an amount of 1 to 30% by weight relative to the total weight of the mixed slurry. Under the above conditions, the mixed slurry may have excellent miscibility and dispersibility. For example, the first coating material may be included in an amount of 1 to 25% by weight, 1 to 20% by weight, 1 to 15% by weight, 1 to 10% by weight, 2 to 9% by weight, or 2 to 5% by weight.
[0633] In a specific example, the mixed slurry may contain 5 to 75% by weight of the solvent relative to the total weight of the mixed slurry. Under the above conditions, it can have excellent miscibility and dispersibility. For example, it may contain 10 to 70% by weight, 10 to 65% by weight, 15 to 60% by weight, 15 to 50% by weight, 20 to 50% by weight, or 25 to 50% by weight of the solvent.
[0634] The powder size of the negative electrode active material can be easily adjusted by drying the mixed slurry. For example, the drying can be performed using a spray dryer or the like. For example, the drying can be performed using a spray dryer equipped with a single-fluid nozzle, a two-fluid nozzle, or a four-fluid nozzle.
[0635] In a specific example, the primary dry powder may be spherical, polyhedral or elliptical. For example, it may be spherical.
[0636] First mixture preparation step (S31): said step is a step of preparing a first mixture including said primary dry powder and a second coating material.
[0637] In a specific example, the second coating material includes one or more of a hard coating material and a soft coating material.
[0638] The hard coating material may ensure excellent hardness and strength, thereby preventing the negative electrode active material from being destroyed when the composite silicon particles expand, and may have excellent electrical characteristics.
[0639] For example, the hard coating material may include a carbon-based material.
[0640] In a specific example, the pencil hardness of the hard coating material measured according to ISO 15184 may be 4H or more. Under the above conditions, the negative electrode active material can be prevented from being destroyed when the composite silicon particles expand, and excellent electrical properties can be obtained. For example, the pencil hardness may be 4H to 6H. For example, the hard coating material may include a carbon material having a pencil hardness of 4H to 6H.
[0641] For example, as the hard coating material, NanoMollisAdamas product of Lemon Energy Co., Ltd. of Korea may be used.
[0642] The hard coating material may be amorphous. In addition, the hard coating material is self-assembled, has excellent isotropic properties, and has excellent thermal stability, so that the structure does not change even at high temperatures (about 3000° C.).
[0643] The hard coating material has high gas impermeability, and can have excellent chemical resistance and electrical conductivity. In addition, the hard coating material can be dust-free, and the purity (impurity content) can be 5 ppm or less or 2 ppm or less. Under the above conditions, while having excellent strength and electrical properties, it can have excellent conductivity of the negative electrode active material.
[0644] In a specific example, the hard coating material may have a resistivity of 3 to 5 μΩ·m. Under the above conditions, the negative electrode active material may have excellent conductivity.
[0645] In a specific example, the average particle size (d50) of the hard coating material may be 3 nm to 2.5 μm. Under the above conditions, the first mixture may be easily formed. For example, the average particle size may be 5 to 500 nm, 10 to 500 nm, or 15 to 200 nm.
[0646] In a specific example, the soft coating material may include one or more of pitch, coke, and carbon precursors formed from other organic substances. For example, the pitch may include one or more of pyrolysis fuel oil pitch and coal tar pitch.
[0647] In a specific example, the average particle size (d50) of the soft coating material may be 0.03 to 10 μm. Under the above conditions, the first mixture can be easily formed. For example, it may be 0.3 to 5 μm.
[0648] The step of preparing a first intermediate body (S41): the step is a step of preparing a first intermediate body using the first mixture and the third coating material.
[0649] In a specific example, the third coating material includes one or more of a hard coating material, a middle coating material and a soft coating material.
[0650] In a specific example, in the step of preparing the first intermediate, the second intermediate may be prepared by heat treating (or sintering) the second mixture including the first mixture and the hard coating material at a temperature of 900-1050°C.
[0651] The hard coating material may ensure excellent hardness and strength, thereby preventing the negative electrode active material from being destroyed when the composite silicon particles expand, and may have excellent electrical characteristics.
[0652] For example, the hard coating material may include a carbon-based material.
[0653] In a specific example, the pencil hardness of the hard coating material measured according to ISO 15184 may be 4H or more. Under the above conditions, the negative electrode active material can be prevented from being destroyed when the composite silicon particles expand, and excellent electrical properties can be obtained. For example, the pencil hardness may be 4H to 6H. For example, the hard coating material may include a carbon material having a pencil hardness of 4H to 6H.
[0654] For example, as the hard coating material, NanoMollisAdamas product of Lemon Energy Co., Ltd. of Korea may be used.
[0655] The hard coating material may be amorphous. In addition, the hard coating material is self-assembled, has excellent isotropic properties, and has excellent thermal stability, so that the structure does not change even at high temperatures (about 3000° C.).
[0656] The hard coating material has high gas impermeability, and can have excellent chemical resistance and electrical conductivity. In addition, the hard coating material can be dust-free, and the purity (impurity content) can be 5 ppm or less or 2 ppm or less. Under the above conditions, while having excellent strength and electrical properties, it can have excellent conductivity of the negative electrode active material.
[0657] In a specific example, the hard coating material may have a resistivity of 3 to 5 μΩ·m. Under the above conditions, the negative electrode active material may have excellent conductivity.
[0658] In a specific example, the average particle size (d50) of the hard coating material may be 3 nm to 2.5 μm. Under the above conditions, the first intermediate may be easily formed. For example, the average particle size may be 5 to 500 nm, 10 to 500 nm, or 15 to 200 nm.
[0659] In another specific example, the first intermediate can be prepared by heat treating the first mixture and the intermediate coating material.
[0660] In a specific example, the coating material may include one or more of hydrocarbon gas and carbon black. For example, the hydrocarbon gas may include methane (CH4), ethane (C2H6), propane (C3H8), butane (C4H 10 ), pentane (C5H 12 )
[0661] For example, the first intermediate may be prepared by heat-treating the first mixture under a hydrocarbon gas atmosphere.
[0662] In a specific example, the heat treatment may be performed under vacuum conditions. Under the above conditions, the hydrocarbon gas is uniformly diffused between the first mixture particles arranged in the cavity, and a uniform middle coating layer may be formed during the heat treatment. For example, the heat treatment may be performed under vacuum conditions. -1 ~10 -6 The process is carried out under vacuum conditions of torr.
[0663] In a specific example, the step of preparing the first intermediate may include: heating the interior of the cavity in which the first mixture is arranged to 850-970° C., and reducing the pressure to 10 -1 Up to 10 -6The steps of increasing the pressure by 1 torr; allowing hydrocarbon gas to flow into the reduced-pressure chamber so that the first mixture and the hydrocarbon gas come into contact; and gradually increasing the pressure inside the chamber while maintaining the increased temperature to form a coating layer on the outer peripheral surface of the first mixture through thermal decomposition of the hydrocarbon gas to prepare a first intermediate.
[0664] When the pressure inside the cavity is reduced under the above conditions, the hydrocarbon gas can easily penetrate between the primary dry powders arranged in the cavity, so that the middle coating layer can be uniformly formed. In particular, the hydrocarbon gas easily penetrates between the plurality of primary dry powders, so that the middle coating layer has excellent homogeneity and can be formed with a uniform thickness, thereby forming a first intermediate.
[0665] In addition, when the pressure inside the cavity is increased under the above conditions, a middle coating layer with uniform gas thickness and excellent homogeneity is formed on the outer peripheral surface of the primary dry powder, thereby preparing the first intermediate. At this time, the pressure inside the cavity can be gradually increased under vacuum. For example, the pressure inside the cavity can be gradually increased to 10 1 Support up to 10 5 torr to prepare the first intermediate.
[0666] For another example, the first intermediate can be prepared by heat treating the second mixture including the first mixture and carbon black. For example, the heat treatment can be performed at a temperature of 850 to 970° C. Under the above conditions, the first intermediate can be easily formed. For example, the heat treatment can be performed at a temperature of 890 to 910° C.
[0667] In another specific example, the first intermediate body can be prepared by mixing a second mixture including the first mixture and a soft coating material and sintering. For example, the second mixture can be prepared by mixing the primary dry powder and the soft coating material and sintering at a temperature of 850 to 975° C. When sintering is performed under the above temperature conditions, the first intermediate body including the soft coating layer can be easily formed.
[0668] In a specific example, the soft coating material may include one or more of pitch, coke, and carbon precursors formed from other organic substances. For example, the pitch may include one or more of pyrolysis fuel oil pitch and coal tar pitch.
[0669] In a specific example, the average particle size (d50) of the soft coating material may be 0.03 to 10 μm. Under the above conditions, the first intermediate may be easily formed. For example, the average particle size may be 0.3 to 5 μm.
[0670] In a specific example, the second mixture may be heat treated at 850-1050°C. When sintered under the above conditions, the first intermediate may be easily formed and may have excellent durability and long life characteristics. For example, the heat treatment may be performed at 850-1050°C, 870-1050°C, 900-1000°C, 930-975°C, or 930-960°C.
[0671] For example, the second mixture may be heat treated under an inert gas atmosphere. The inert gas may include nitrogen. For example, the sintered sintered product may be subjected to a conventional dry pulverization process such as a disc mill, an air classifier mill (ACM), a jet mill, and a pin mill, and then classified to prepare the first intermediate.
[0672] In a specific example, the step of preparing the first intermediate may include: sintering the first mixture for the first time at a temperature of 850 to 950°C, and sintering the second mixture including the first sintered first mixture and the third coating material for the second time at a temperature of more than 950°C and less than 1050°C. Under the above conditions, a first intermediate including a second hollow core having a second hollow portion and a secondary particle structure of one or more primary particles filled in the second hollow portion can be easily formed. The third coating material may include one or more of a hard coating material and a soft coating material.
[0673] For example, the first sintering and the second sintering may be performed under an inert gas atmosphere. The inert gas may include nitrogen.
[0674] For example, during the first sintering, a primary particle structure including a first hollow core having a first hollow portion and nano-silicon particles filling the first hollow portion may be formed, and during the second sintering, a secondary particle structure including a second hollow core having a second hollow portion and one or more primary particles filling the second hollow portion may be formed.
[0675] In a specific example, the second sintering may be performed at a higher temperature than the first sintering. Under the above conditions, the primary particles and secondary particles are formed with higher strength, thereby having excellent durability, electrical properties, long life properties and capacity properties of the negative electrode active material.
[0676] In a specific example, the first mixture sintered for the first time is pressurized to prepare a compressed product, and a second mixture is prepared by mixing the compressed product with a soft coating material. The second mixture may be sintered for the second time.
[0677] For example, the compressed product can be prepared by pressing the first mixture of the first sintering at a pressure of 10 to 60 atm in one direction (or uniaxial compression). When the compressed product is prepared under the pressurized conditions, the internal void volume of the negative electrode active material is adjusted, so that the electrical characteristics and long life and capacity characteristics of the negative electrode active material can be excellent. Then, the second mixture including the compressed product and the third coating material can be sintered for the second time under the above conditions to prepare the first intermediate.
[0678] In a specific example, the first intermediate includes: primary particles, including a first hollow core forming a first hollow portion and composite silicon particles and carbon particles filling the first hollow portion; and secondary particles, including a second hollow core forming a second hollow portion and one or more of the primary particles filled in the second hollow portion, the carbon particles including graphene and graphite, the composite silicon particles including nano-silicon particles having a first coating layer formed on the surface, the first coating layer including a middle coating layer, and the first hollow core and the second hollow core have different hardnesses.
[0679] For example, the carbon particles may include a pencil hardness of B to 3H measured according to ISO 15184, an electrical conductivity of 5 to 300 μΩ·m, and a density of 0.3 to 1.5 g / cm 2 The first carbon particles may include graphite and graphene. The graphite and graphene may be as described above.
[0680] For example, the carbon particles may also include a pencil hardness of 4H to 7H measured according to ISO 15184, a resistivity of 3 to 50 μΩ·m, and a density of 1.8 to 2.5 g / cm 3 of the second carbon particles.
[0681] In a specific example, the average size of the second carbon particles may be 1 to 3000 nm. The size may mean the maximum length or diameter (particle size) of the second carbon particles. For example, the second carbon particles may be flake-shaped or spherical. For example, the second carbon particles may be 1 to 2500 nm, 3 to 1500 nm, 5 to 1000 nm, 10 to 500 nm, 30 to 500 nm, or 50 to 200 nm.
[0682] In a specific example, the first carbon particles and the second carbon particles may be contained in a weight ratio of 1:0.5 to 1:3. When contained in the above weight ratio, the negative electrode active material has excellent conductivity and capacity characteristics, and can have excellent high output and long life characteristics.
[0683] In a specific example, the first coating layer may further include a silicon carbide (SiC) layer formed between the nano-silicon particles and the middle coating layer.
[0684] In a specific example, the number of nano-silicon particles filled in the first hollow part can be set so that the total volume of the expanded nano-silicon particles formed when lithium ions are embedded in the nano-silicon particles is less than the volume of the first hollow part. When the number of nano-silicon particles is set in the manner as described above, the first hollow core (or negative electrode active material) can be prevented from being broken or damaged when the nano-silicon particles expand.
[0685] In a specific example, the number of composite silicon particles filled in the first hollow part of the primary particles can be set in consideration of the maximum expandable volume when lithium ions are embedded. For example, when the volume of the composite silicon particles (nano silicon particles) expands by 2 times, the first hollow part can be calculated by assuming that it is filled with hexagonal close packing (HCC) or face-centered cubic (FCC) structure.
[0686] The number of composite silicon particles filled in the first hollow portion may be set so that the total volume of expanded composite silicon particles formed by lithium ions being intercalated into the composite silicon particles satisfies or is smaller than the volume of the first hollow portion.
[0687] In a specific example, the number (n) of composite silicon particles filled in the first hollow portion may satisfy the condition of the following formula 1:
[0688] Formula 1:
[0689] (In the above formula 1, d is the relative diameter of the expanded composite silicon particle derived from the following formula 1-1, and q is the relative diameter of the expanded composite silicon particle at the center of the first hollow portion derived from the following formula 1-2)
[0690] Formula 1-1: d = r' / R
[0691] (In the above formula 1-1, R is the radius of the first hollow portion, r' is the radius of the expanded composite silicon particle, and r'=1.2599*a+b (a is the radius of the composite silicon particle, and b is the thickness of the first coating layer))
[0692] Formula 1-2: q = 1-2*d
[0693] (In the above formula 1-2, the d is as defined above).
[0694] In a specific example, the negative electrode active material includes first composite silicon particles and second composite silicon particles having radii r1 and r2, respectively, and the number of particles (n1 and n2) of the first composite silicon and the second composite silicon filled in the first hollow portion may satisfy the condition of the following formula 2:
[0695] Formula 2:
[0696] (In the above formula 2, r1' and r2' are the radii of the first expanded composite silicon particle and the second expanded composite silicon particle, respectively, R is the radius of the first hollow portion, r1' and r2' are 1.2599*a1+b1 and 1.2599*a2+b2, respectively (a1 and b1 are the radius of the first nano-silicon particle and the thickness of the first coating layer, and a2 and b2 are the radius of the second nano-silicon particle and the thickness of the first coating layer)).
[0697] In a specific example, the radius of the composite silicon particle filled in the first hollow portion can be derived by assuming that the total volume of the first coating layer of the composite silicon particle when expanded twice is the same as the total volume of the first coating layer of the composite silicon particle that is not expanded.
[0698] The radius r1 of the expanded composite silicon particle can satisfy the following equation 2-1:
[0699] Formula 2-1: (r1') 3 =(a1') 3 +(r1) 3 -(a1) 3
[0700] (In the above formula 2-1, a1 is the radius of the nano-silicon particle, r1 is the radius of the composite silicon particle, and a1' is the radius of the nano-silicon particle after expansion)
[0701] In a specific example, the negative electrode active material includes first composite silicon particles and second composite silicon particles having radii r1 and r2, respectively, and the number of particles (n1 and n2) of the first composite silicon and the second composite silicon filled in the first hollow portion may satisfy the condition of the following formula 2-2:
[0702] Formula 2-2:
[0703] (In the above formula 2, r1' and r2' are the radii of the first expanded composite silicon particle and the second expanded composite silicon particle, respectively, R is the radius of the first hollow portion, and r1' and r2' respectively satisfy (r1') 3 =(a1') 3 +(r1)3 -(a1) 3 and (r2') 3 =(a2') 3 +(r2) 3 -(a2) 3 (In the above formula 2-2, a1 is the radius of the nano-silicon particle, r1 is the radius of the composite silicon particle, and a1' is the radius of the nano-silicon particle after expansion)).
[0704] The sizes of the first and second composite silicon particles may be the same or different. Under the above conditions, the composite silicon particles have excellent dispersibility, can prevent the first hollow core from breaking and destroying when the composite silicon particles expand, and can have excellent high capacity and high output characteristics.
[0705] In a specific example, the number of primary particles (1) and primary particles (2) filled in the second hollow portion may satisfy the condition of the following formula 3:
[0706] Formula 3:
[0707] (In the above formula 3, c1 and n3 are the radius and number of primary particles (1), c2 and n4 are the radius and number of primary particles (2), and b is the radius of the second hollow portion).
[0708] When the number of primary particles (1) and primary particles (2) filled in the second hollow portion of the secondary particles is derived under the conditions of the above formula 3, the second hollow core (or negative electrode active material) can be prevented from being broken or damaged due to expansion of the primary particles.
[0709] Second coating layer forming step (S51)
[0710] In a specific example, after the step of preparing the first intermediate ( S41 ), the step of forming a second coating layer on the outer peripheral surface of the first intermediate ( S51 ) may be further included.
[0711] In a specific example, the second coating layer may include one or more of a soft coating layer, a middle coating layer, and a hard coating layer.
[0712] The second coating layer may have a hardness different from that of the second hollow core. Under the above conditions, the negative electrode active material may be prevented from being broken or damaged due to expansion of the composite silicon particles.
[0713] In a specific example, the forming of the soft coating layer may include: mixing the first intermediate and the soft coating material and sintering the mixture.
[0714] In a specific example, the sintering may be performed at a temperature of 850 to 975° C. Under the above conditions, the soft coating layer may be easily formed on the outer peripheral surface of the first intermediate body. For example, the sintering may be performed at a temperature of 860 to 975° C. or 900 to 960° C.
[0715] In a specific example, the soft coating material may include one or more of pitch, coke, and carbon precursors formed from other organic substances. For example, the pitch may include one or more of pyrolysis fuel oil pitch and coal tar pitch.
[0716] In a specific example, the soft coating layer may be formed by coating and sintering a soft coating liquid including a soft coating material and a solvent.
[0717] In a specific example, the solvent may include one or more of water, an alcohol solvent, an amide solvent, an ester solvent and a hydrocarbon solvent. When the above solvents are included, excellent miscibility and operability may be obtained. As the alcohol solvent, one or more of methanol, ethanol, isopropanol and butanol may be included. As the amide solvent, one or more of N-methyl-2-pyrrolidone (NMP), dimethylacetamide (DMAC) and dimethylformamide (DMF) may be included. As the hydrocarbon solvent, one or more of toluene and xylene may be included.
[0718] In a specific example, the pencil hardness of the soft coating layer measured according to ISO 15184 may be B to 3H. Under the above conditions, the volume expansion of the negative electrode active material caused by the volume expansion of the nano-silicon particles is excellent in buffering effect, the hard hollow core can be prevented from being destroyed, and an excellent long life characteristic can be obtained. For example, the pencil hardness may be B to 1H.
[0719] In a specific example, the forming of the intermediate coating layer may include: a step of heat treating the first intermediate under a hydrocarbon gas atmosphere.
[0720] In one specific example, the medium coating layer may be formed by heat treating one or more of a hydrocarbon gas and carbon black. For example, the hydrocarbon gas may include methane (CH4), ethane (C2H6), propane (C3H8), butane (C4H 10 ), pentane (C5H 12 )
[0721] For example, the heat treatment may be performed at a temperature of 850 to 970° C. Under the above conditions, the middle coating layer may be easily formed. For example, the heat treatment may be performed at a temperature of 890 to 910° C.
[0722] In one specific example, the heat treatment may be performed under vacuum conditions. Under the above conditions, the hydrocarbon gas is easily diffused, thereby forming a uniform middle coating layer. For example, the heat treatment may be performed under 10 -1 ~10 -6 The process is carried out under vacuum conditions of torr.
[0723] In a specific example, the pencil hardness of the middle coating layer measured according to ISO 15184 may be 2H or more and less than 4H. Under the above conditions, the volume expansion of the negative electrode active material caused by the volume expansion of the nano silicon particles is excellent in buffering effect, the destruction of the hard hollow core can be prevented, and excellent long life characteristics can be achieved.
[0724] In a specific example, the thickness of the middle coating layer may be 5 to 100 nm. Under the above conditions, even when the nano-silicon particles expand, the negative electrode active material can be prevented from being broken or damaged.
[0725] For example, the forming of the first coating layer may include the steps of: forming a soft coating layer on the outer peripheral surface of the first intermediate body; and forming a middle coating layer on the outer peripheral surface of the soft coating layer.
[0726] In a specific example, the forming of the hard coating layer may include: mixing the first intermediate and a hard coating material and sintering the mixture.
[0727] In a specific example, the hard coating layer can be formed by sintering the hard coating material. When the hard coating layer is included, the strength and durability of the negative electrode active material are excellent, thereby preventing the destruction of the negative electrode active material caused by the expansion of the primary particles (or nano silicon particles), the conductivity is excellent, the capacity can be prevented from being reduced, and the excellent long life characteristics can be obtained.
[0728] The hard coating material may be the same material as described above.
[0729] In a specific example, 100 parts by weight of the first intermediate and 0.1 to 30 parts by weight of the hard coating material may be mixed and sintered. When the above content conditions are applied, the strength and durability of the negative electrode active material are excellent, thereby preventing the damage during the expansion of the nano silicon particles, and the conductivity is excellent, the capacity can be prevented from being reduced, and an excellent long life characteristic can be obtained.
[0730] In a specific example, the sintering may be performed by mixing the first intermediate and the hard coating material at 900 to 1050° C. Under the above conditions, a hard coating layer may be easily formed on the outer peripheral surface of the first intermediate (or the second hollow core). For example, the sintering may be performed at a temperature of 965 to 1000° C.
[0731] The sintering may be performed under an inert gas atmosphere. The inert gas may include nitrogen.
[0732] In a specific example, the average particle size (d50) of the hard coating material may be 3 nm to 2.5 μm. Under the above conditions, a hard coating layer can be easily formed. For example, it may be 5 to 1000 nm, 10 to 500 nm, or 15 to 200 nm.
[0733] For example, the forming of the second coating layer may include the steps of: forming a hard coating layer on the outer peripheral surface of the first intermediate body; and forming a middle coating layer on the outer peripheral surface of the hard coating layer.
[0734] Secondary battery including negative electrode active material
[0735] Another aspect of the present invention relates to a secondary battery including the silicon-carbon composite negative electrode active material. In a specific example, the secondary battery includes: a positive electrode; a negative electrode; and an electrolyte formed between the positive electrode and the negative electrode, wherein the negative electrode includes the negative electrode active material.
[0736] The secondary battery may include a lithium secondary battery. In a specific example, the lithium secondary battery may include: a positive electrode including a positive electrode active material; a negative electrode disposed separately from the positive electrode and including the negative electrode active material; an electrolyte disposed between the negative electrode and the positive electrode; and a separation membrane disposed between the negative electrode and the positive electrode to prevent electrical short circuit between the negative electrode and the positive electrode.
[0737] In a specific example, the positive electrode and the negative electrode can be prepared by coating a mixture including an active material, a conductive material and a binder on one surface of an electrode plate (collector) respectively, followed by drying and pressing.
[0738] In a specific example, the positive electrode plate and the negative electrode plate may respectively include one or more of copper, stainless steel, aluminum, nickel, and titanium.
[0739] For another example, the negative electrode plate may be a polyimide film coated with nickel foam, copper foam, a conductive metal, or a combination thereof.
[0740] For another example, the negative electrode plate may include copper foil, carbon-coated copper foil, copper foil with a surface roughness of 5 nm or more, nickel foil, stainless steel foil, nickel-coated iron (Fe) foil, and copper foil with pores of 1 to 50 μm in size.
[0741] In a specific example, the positive electrode active material may include a composite oxide of a metal and lithium. The metal may include one or more of cobalt (Co), manganese (Mn), aluminum (Al) and nickel (Ni). For example, it may include one or more of lithium-nickel oxide, lithium-nickel-cobalt oxide, lithium-nickel-cobalt-manganese oxide, and lithium-nickel-cobalt-aluminum oxide.
[0742] In a specific example, the conductive material may include one or more of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, carbon fiber, metal fiber, carbon fluoride, aluminum, nickel powder, zinc oxide, potassium titanate, titanium oxide and polystyrene compounds.
[0743] In a specific example, the binder may include polyvinyl fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene-diene monomer (EPDM), styrene rubber, fluororubber, etc.
[0744] In a specific example, the separation membrane may use a conventional separation membrane. For example, the separation membrane may include one or more of polyester, polyethylene, polypropylene, and polytetrafluoroethylene (PTFE). The separation membrane may be in the form of a non-woven fabric or a woven fabric. The separation membrane is porous with an average pore size of 0.01 to 10 μm, and the thickness of the separation membrane may be 5 to 500 μm.
[0745] In a specific example, the electrolyte may include a non-aqueous organic solvent and a lithium salt. For example, the non-aqueous organic solvent may include one or more of carbonate, ester, ether and ketone solvents. The carbonate solvent may include one or more of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl methyl carbonate (EMC), ethyl propyl carbonate (EPC), ethylene carbonate (EC), propylene carbonate (PC) and butylene carbonate (BC).
[0746] The ester solvent may include at least one of butyrolactone, decanolide, valerolactone, caprolactone, methyl acetate, ethyl acetate and propyl acetate. The ether solvent may include dibutyl ether, etc. The ketone solvent may include polymethyl vinyl ketone.
[0747] The lithium salt can be used as a source of lithium ions in a battery. For example, the lithium salt may include, but is not limited to, one or more of LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiCF3SO3, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiAlO4, and LiAlCl4.
[0748] In a specific example, the electrolyte may further include one or more of vinylene carbonate, vinyl ethylene carbonate, monofluoroethylene carbonate, difluoroethylene carbonate, succinic anhydride, and 1,3-propane sultone.
[0749] In a specific example, the lithium secondary battery may include a square battery, a cylindrical battery, a pouch-type battery, and the like.
[0750] Below, the composition and function of the present invention are further described in detail by the preferred embodiments of the present invention. However, this is proposed as a preferred example of the present invention, and the present invention cannot be construed as limited in any meaning. For the contents not recorded in this article, as long as it is a person of ordinary skill in the art, it can be fully inferred technically, so its description is omitted.
[0751] Examples and Comparative Examples
[0752] Example 1
[0753] (1) Preparation of nano silicon particles: A silicon raw material powder having an average particle size (d50) of 0.5 μm was prepared. A dispersion comprising 100 parts by weight of the silicon raw material powder, 0.1 parts by weight of a dispersant (stearic acid) and 900 parts by weight of a first solvent (ethanol) was prepared, and the dispersion was milled and crushed to prepare a nano silicon slurry (viscosity 4320 cPs at 25°C) having an average particle size (d50) of 200 nm (radius 100 nm). Next, a rotary spray dryer was used to dry the nano silicon slurry at a disk rotation rate (20,000 to 30,000 rpm) to prepare nano silicon particles.
[0754] (2) Preparation of composite silicon particles: A first composition comprising the nano-silicon particles and graphite is prepared. The first composition is added into a cavity, and the temperature inside the cavity is raised to 950-1100°C and the pressure is reduced to 10 -2 Up to 10-6 Next, hydrocarbon (CH4) gas and buffer gas (nitrogen (N2) gas) are flowed into the decompressed chamber so that the first composition is in contact with the hydrocarbon gas and the buffer gas. Next, while maintaining the elevated temperature, the pressure inside the decompressed chamber is gradually increased to 10 2 ~10 3 torr, and composite silicon particles having a first coating layer (a silicon carbide layer and a middle coating layer are sequentially formed) formed on the surface of the nano-silicon particles through thermal decomposition of the hydrocarbon gas.
[0755] (3) Preparation of carbon particles: Spherical artificial graphite (graphite) was mechanically milled (Gyro mixer milling machine, KM Tech, South Korea) at 50-100 rpm for 60 minutes using zirconium oxide balls to remove the rough parts of the graphite to prepare graphene with a 2-5 layer structure. Next, carbon particles including the spherical graphite and plate-like graphene were prepared.
[0756] (4) Preparation of mixed slurry and primary dry powder: A mixed slurry including the composite silicon particles, the carbon particles and a solvent (ethanol) was dried at a disk rotation rate (20,000 to 30,000 rpm) using a rotary spray dryer to prepare a primary dry powder.
[0757] (5) Preparation of a first intermediate: Under an inert gas atmosphere, a second mixture including the primary dry powder and a first coating material (a hard coating material, a carbon-based material having an average particle size (d50) of 0.01 to 0.5 μm and an ISO 15184 standard pencil hardness of 4 to 6H (NanoMollisAdamas from Lemon Energy Co., Ltd., South Korea)) is sintered at a temperature of 900 to 1050°C to prepare a first intermediate.
[0758] (6) Formation of a second coating layer and preparation of a negative electrode active material: The first intermediate and a soft coating material (including asphalt having an average particle size (d50) of 3 to 5 μm) are mixed and sintered at a temperature of 850 to 975°C to form a second coating layer (soft coating layer) to prepare a second intermediate, and the intermediate formed body is ground and graded to prepare a negative electrode active material.
[0759] The negative electrode active material comprises: a first hollow core (thickness of 20-30 nm, ISO 15184 standard pencil hardness of 4H-6H and density of 1.8-2.3 g / cm 3), a first hollow portion is formed inside thereof; composite silicon particles and carbon particles are filled in the first hollow portion; and a second coating layer (thickness of 10 to 20 nm, ISO 15184 standard pencil hardness of B and density of 1.5 g / cm 3 A soft coating layer) is formed on the outer peripheral surface of the first hollow core, and the average diameter of the first hollow part is 10 μm (radius (R) 5 μm).
[0760] The carbon particles contain plate-like graphene (ISO 15184 standard pencil hardness of B to 2H, average size of 50 to 300 nm, conductivity of 5 to 30 μΩ·m, and density of 0.5 to 1.5 g / cm 3 ) and spherical graphite (ISO 15184 standard pencil hardness is B~2H, average particle size (d50) is 30~100nm, conductivity is 50~200μΩ·m and density is 0.5~1.5cm 3 ).
[0761] The average radius (d50) of the composite silicon particles is 500nm and 510nm. The composite silicon particles include a first coating layer (a silicon carbide layer with a thickness of 3nm and a pencil hardness of 7H or more according to ISO 15184) and a silicon carbide layer with a thickness of 7nm, a pencil hardness of 2H to 3H according to ISO 15184 and a density of 1.6 to 1.7 g / cm 3 Nano-silicon particles (average radius (d50) 490nm, 500nm) in the middle coating layer.
[0762] The negative electrode active material includes 25 to 80 weight percent of composite silicon particles, 1 to 10 weight percent of carbon particles, 1 to 40 weight percent of a first hollow core, and 1 to 40 weight percent of a second coating layer.
[0763] Example 2
[0764] The second mixture including the primary dry powder of Example 1 and the first coating material (soft coating material including pitch having an average particle size (d50) of 3 to 5 μm) was sintered at 850 to 975° C. to prepare a first intermediate.
[0765] Next, under an inert atmosphere, a second mixture including the first intermediate and a hard coating material (carbon material with an average particle size (d50) of 0.01 to 0.5 μm and a pencil hardness of 4 to 6H according to ISO15184 (NanoMollisAdamas of Lemon Energy, South Korea)) was sintered at a temperature of 900 to 1050° C. to form a second coating layer (hard coating layer) to prepare a second intermediate. The second intermediate was ground and classified to prepare a negative electrode active material.
[0766] The negative electrode active material includes: a first hollow core (thickness 20-30 nm, ISO 15184 standard pencil hardness B and density 1.4 g / cm 3 ), a first hollow portion is formed inside thereof; composite silicon particles and carbon particles are filled in the first hollow portion; and a second coating layer (thickness 10-20 nm, ISO 15184 standard pencil hardness 4H-6H and density 1.85-2.5 g / cm 3 A hard coating layer) is formed on the outer peripheral surface of the first hollow core, and the average diameter of the first hollow part is 20 μm (radius (R) 10 μm).
[0767] The carbon particles include plate-like graphene (ISO 15184 standard pencil hardness of B to 2H, average size of 50 to 300 nm, conductivity of 5 to 30 μΩ·m, and density of 0.5 to 1.5 g / cm 3 ) and spherical graphite (ISO 15184 standard pencil hardness is B~2H, average particle size (d50) is 30~100nm, conductivity is 50~200μΩ·m and density is 0.5~1.5cm 3 ).
[0768] The average radius (d50) of the composite silicon particles is 500nm and 510nm. The composite silicon particles include a first coating layer (a silicon carbide layer with a thickness of 3nm and a pencil hardness of 7H or more according to ISO 15184 and a thickness of 7nm, a pencil hardness of 2H to 3H according to ISO15184 and a density of 1.6 to 1.7g / cm 3 Nano-silicon particles (average radius (d50) 490nm, 500nm) in the middle coating layer.
[0769] The negative electrode active material includes 25 to 80 weight percent of composite silicon particles, 1 to 10 weight percent of carbon particles, 1 to 40 weight percent of a first hollow core, and 1 to 40 weight percent of a second coating layer.
[0770] (1) Derivation of the number of composite silicon particles filled in the first hollow portion
[0771] On the other hand, the number of composite silicon particles (n1) filled in the first hollow portion in Examples 1 and 2 satisfies the condition of the following formula 1:
[0772] Formula 1:
[0773] (In the above formula 1, d1 is the relative diameter of the expanded composite silicon particle derived from the following formula 1-1, and q1 is the relative diameter of the expanded composite silicon particle at the center of the first hollow portion derived from the following formula 1-2)
[0774] Formula 1-1: d1 = r' / R
[0775] (In the above formula 1-1, R is the radius of the first hollow portion, r' is the radius of the expanded composite silicon particle, and r'=1.2599*a+b (a is the radius of the composite silicon particle, and b is the thickness of the first coating layer))
[0776] Formula 1-2: q1 = 1-2*d1
[0777] (In the above formula 1-2, the d1 is as defined above).
[0778] On the other hand, the maximum number (n1) of composite silicon particles filled in the first hollow portion in Examples 1 and 2 satisfies the following formula 1-3:
[0779] Formula 1-3:
[0780] (In the above formula 1-3, the d0 is the relative diameter of the nano silicon particle derived from the following formula 1-4, and the q0 is the relative diameter of the composite silicon particle at the center of the first hollow portion derived from the following formula 1-5)
[0781] Formula 1-4: d0 = r / R
[0782] (In the above formula 1-4, R is the radius of the first hollow part, r is the radius of the nano silicon particle, r=a+b (a is the radius of the composite silicon particle, b is the thickness of the first coating layer))
[0783] Formula 1-5: q0 = 1-2*d0
[0784] (In the above formula 1-5, the d0 is as defined above).
[0785] With reference to the above-mentioned Formula 1 and Formulas 1-1 to 1-5, the first hollow radius (R) of the first hollow core, the radius (r, r') of the composite silicon particles / expanded composite silicon particles, the relative diameter (d0, d1) and the relative diameter (q0, q1) of the composite silicon particles / expanded composite silicon particles at the center of the first hollow part of Examples 1 to 2 are derived respectively and are shown in the following Table 1.
[0786] In a specific example, the radius of the composite silicon particles filled in the first hollow portion is derived by assuming that the total volume of the first coating layer of the composite silicon particles when expanded twice is the same as the total volume of the first coating layer of the unexpanded composite silicon particles. Thus, the radius r1 of the expanded composite silicon particles is calculated according to the following formula 2-1.
[0787] Formula 2-1: (r1') 3 =(a1') 3+(r1) 3 -(a1) 3
[0788] (In the above formula 2-1, a1 is the radius of the nano-silicon particle, r1 is the radius of the composite silicon particle, and a1' is the radius of the nano-silicon particle after expansion)
[0789] For composite silicon with a radius of 510 nm, the calculated radius r1' of the expanded composite silicon particle derived from the above formula 2-1 is 636 nm. Next, using the above formula 1, the relative diameter d1 of the expanded composite silicon particle and the relative diameter q1 of the expanded composite silicon particle at the center of the first hollow part are shown in Table 1 below.
[0790] In addition, for the above-mentioned Examples 1 and 2, the composite silicon particle filling rate PR0 and the expanded composite silicon particle filling rate PR1 were respectively measured by the following formula A and are shown in the following Table 1.
[0791] Formula A: Filling rate = (n1 / n0)*100
[0792] (In the above formula A, n0 is the maximum number of (expanded) composite silicon particles filled in the first hollow portion according to the above formulas 1-3, and n1 is the number of (expanded) composite silicon particles filled in the first hollow portion according to the above formula 1).
[0793] Table 1
[0794]
[0795] Referring to the results in Table 1, it can be seen that in Examples 1 and 2, the composite silicon particles with radii of 500 nm and 510 nm contain a maximum of 615 and 578 in the first hollow portion with a radius of 5 μm, and a maximum of 5368 and 5049 in the first hollow portion with a radius of 10 μm.
[0796] In addition, it can be seen that in Examples 1 and 2, the radius of the expanded composite silicon particles expanded twice is 630nm and 643nm, respectively, and the radius of the expanded composite silicon particles derived from Formula 2-1 is 636nm, and the first hollow part with a radius of 5μm contains a maximum of 296, 277, and 287 particles. In addition, it can be seen that the first hollow part with a radius of 10μm contains a maximum of 2620, 2459, and 2544 particles.
[0797] Therefore, it can be seen that even when the composite silicon particles with a radius of 500 nm expand twice due to lithium ion insertion, if the first hollow core is not to be broken, the first hollow parts with a radius of 5 μm (or a radius of 10 μm) must contain no more than 296 (or 2620) particles.
[0798] Example 3
[0799] After preparing a mixed slurry including composite silicon particles prepared in the same manner as in Example 1, a first coating material (a hard coating material, a carbon material having an ISO 15184 standard pencil hardness of 4 to 6H and an average particle size (d50) of 0.05 to 0.5 μm (NanoMollisAdamas of Lemon Energy, South Korea)), carbon particles (including spherical graphite and plate-like graphene) and a solvent (including ethanol), a rotary spray dryer was used to dry the mixed slurry at a disc rotation rate (20,000 to 30,000 rpm) to prepare a primary dry powder.
[0800] Next, a first mixture including the primary dry powder and a second coating material (hard coating material, carbon-based material (NanoMollisAdamas from Lemon Energy, Korea) having a pencil hardness of 4 to 6H according to ISO 15184 and an average particle size (d50) of 0.05 to 0.5 μm) was prepared.
[0801] Next, the first mixture is sintered for the first time at a temperature of 850 to 950°C. Next, the first mixture sintered for the first time is pressurized (or uniaxially compressed) at 10 to 30 atm in one direction to prepare a compressed product. Next, the compressed product and a third coating material (a soft coating material, including asphalt with an average particle size (d50) of 0.03 to 5 μm) are mixed to prepare a second mixture, and the second mixture is sintered for the second time at a temperature of 960 to 1050°C to prepare a first intermediate, and the first intermediate is ground and classified to prepare a negative electrode active material.
[0802] The negative electrode active material comprises: primary particles, a first hollow core (thickness 20 nm, ISO 15184 standard pencil hardness 4H-6H and density 2.2-2.5 g / cm 3 ) and composite silicon particles and carbon particles filled in the first hollow part; and secondary particles, forming a second hollow core (thickness 20nm, ISO15184 standard pencil hardness B and density 1.3g / cm 3 ) and one or more primary particles filled in the second hollow portion.
[0803] The carbon particles include plate-like graphene (ISO 15184 standard pencil hardness of B to 2H, average size of 50 to 300 nm, conductivity of 5 to 30 μΩ·m, and density of 0.5 to 1.5 g / cm 3) and spherical graphite (ISO 15184 standard pencil hardness is B~2H, average particle size (d50) is 30~100nm, conductivity is 50~200μΩ·m and density is 0.5~1.5cm 3 ).
[0804] The composite silicon particles include first composite silicon particles having an average particle size (d50) of 210 nm (radius 105 nm) and second composite silicon particles having an average particle size of 310 nm (radius 155 nm).
[0805] The first composite silicon particles include a first coating layer (formed sequentially with a thickness of 2 nm, a silicon carbide layer and a thickness of 3 nm, an ISO 15184 standard pencil hardness of 2H to 3H and a density of 1.6 to 1.7 g / cm 3 Nano-silicon particles (average radius (d50) 100 nm) in the middle coating layer.
[0806] In addition, the second composite silicon particles include a first coating layer formed on the surface (a silicon carbide layer with a thickness of 2 nm and a pencil hardness of 7H or more according to ISO 15184 and a thickness of 3 nm, a pencil hardness of 2H to 3H according to ISO 15184 and a density of 1.6 to 1.7 g / cm 3 Nano-silicon particles (average radius (d50) 150 nm) in the middle coating layer.
[0807] The primary particles include a primary particle (1) having a first hollow portion with a radius of 1 μm (1000 nm, an average diameter of 2 μm) and a primary particle (2) having a first hollow portion with a radius of 1.5 μm (1500 nm). In addition, the radius c1 of the primary particle (1) is 1020 nm, the radius c2 of the primary particle (2) is 1520 nm, and the radius b of the second hollow portion of the secondary particle is 3 μm (an average diameter of 6 μm).
[0808] The negative electrode active material includes 25 to 80 weight percent of composite silicon particles, 1 to 10 weight percent of carbon particles, 1 to 40 weight percent of first hollow cores, and 1 to 40 weight percent of second hollow cores.
[0809] Example 4
[0810] After preparing a mixed slurry including composite silicon particles prepared by the same method as described in Example 1, carbon particles (including spherical graphite and plate-like graphene), a first coating material (soft coating material, including asphalt with an average particle size (d50) of 0.03 to 5 μm) and a solvent (including ethanol), a rotary spray dryer is used to dry the mixed slurry at a disc rotation number (20,000 to 30,000 rpm) to prepare a primary dry powder.
[0811] Next, a first mixture including the primary dry powder and a second coating material (hard coating material, ISO 15184 standard pencil hardness of 4 to 6H and a carbon-based material with an average particle size (d50) of 0.05 to 0.5 μm (soft coating material, including asphalt with an average particle size (d50) of 0.03 to 5 μm) is prepared.
[0812] Next, the first mixture was sintered for the first time at a temperature of 850 to 950°C. Next, the first mixture sintered for the first time was pressurized (or uniaxially compressed) at 10 to 30 atm in one direction to prepare a compressed product. Next, the compressed product and a third coating material (a hard coating material, a carbon material (Na noMollis Adamas of Lemon Energy, South Korea) with a pencil hardness of 4 to 6H according to ISO 15184 and an average particle size (d50) of 0.05 to 0.5 μm) were mixed to prepare a second mixture, and the second mixture was sintered for the second time at a temperature of 960 to 1050°C to prepare a first intermediate, and the first intermediate was ground and classified to prepare a negative electrode active material.
[0813] The negative electrode active material includes: primary particles, including a first hollow core (thickness 20nm, ISO 15184 standard pencil hardness B and density 1.3g / cm 3 ) and composite silicon particles and carbon particles filled in the first hollow part; and secondary particles, forming a second hollow core of the second hollow part (thickness 20nm, ISO 15184 standard pencil hardness 4H~6H and density 2.2~2.5g / cm 3 ) and one or more primary particles filled in the second hollow portion.
[0814] The carbon particles include plate-like graphene (ISO 15184 standard pencil hardness of B to 2H, average size of 50 to 300 nm, conductivity of 5 to 30 μΩ·m, and density of 0.5 to 1.5 g / cm 3 ) and spherical graphite (ISO 15184 standard pencil hardness is B~2H, average particle size (d50) is 30~100nm, conductivity is 50~200μΩ·m and density is 0.5~1.5cm 3 ).
[0815] The composite silicon particles include first composite silicon particles having an average particle size (d50) of 210 nm (radius 105 nm) and second composite silicon particles having an average particle size (d50) of 310 nm (radius 155 nm).
[0816] The first composite silicon particles include a first coating layer (formed sequentially with a thickness of 2 nm, a silicon carbide layer and a thickness of 3 nm, an ISO 15184 standard pencil hardness of 2H to 3H and a density of 1.6 to 1.7 g / cm 3 Nano-silicon particles (average radius (d50) 100 nm) in the middle coating layer.
[0817] In addition, the second composite silicon particles include a first coating layer (a silicon carbide layer with a thickness of 2 nm and a pencil hardness of 7H or more according to ISO 15184 and a thickness of 3 nm, a pencil hardness of 2H to 3H according to ISO 15184 and a density of 1.6 to 1.7 g / cm2) formed on the surface. 3 Nano-silicon particles (average radius (d50) 150 nm) in the middle coating layer.
[0818] The primary particles include a primary particle (1) having a first hollow portion with a radius of 1 μm (1000 nm, an average diameter of 2 μm) and a primary particle (2) having a first hollow portion with a radius of 1.5 μm (1500 nm). In addition, the radius c1 of the primary particle (1) is 1020 nm, the radius c2 of the primary particle (2) is 1520 nm, and the radius b of the second hollow portion of the secondary particle is 5 μm (an average diameter of 10 μm).
[0819] The negative electrode active material includes 25 to 80 weight percent of composite silicon particles, 1 to 10 weight percent of carbon particles, 1 to 40 weight percent of first hollow cores, and 1 to 40 weight percent of second hollow cores.
[0820] (1) Derivation of the number of first composite silicon and second composite silicon particles filled in primary particles
[0821] On the other hand, the numbers (n1, n2) of the first composite silicon particles and the second composite silicon particles filled in the first hollow portion of the primary particles in Examples 3 to 4 satisfy the condition of the following formula 2:
[0822] Formula 2:
[0823] (In the above formula 2, r1' and r2' are the radii of the first expanded composite silicon particle and the second expanded composite silicon particle, respectively, R is the radius of the first hollow portion, r1' and r2' are 1.2599*a1+b1 and 1.2599*a2+b2, respectively (a1 and b1 are the radius of the first nano-silicon particle and the thickness of the first coating layer, and a2 and b2 are the radius of the second nano-silicon particle and the thickness of the first coating layer).
[0824] The radii of the first expanded composite silicon particles of Examples 3 to 4 that expanded twice according to the above formula 2 are 131 nm and 194 nm, respectively. In addition, according to the above formula 2, the primary particles (1) whose first hollow portion has a radius of 1 μm (1000 nm) are filled with 120 first composite silicon particles (radius 105 nm) and 99 second composite silicon particles (radius 155 nm) (a total of 219 particles). In addition, the primary particles (2) whose first hollow portion has a radius of 1.5 μm (1500 nm) are filled with 450 first composite silicon particles (radius 105 nm) and 323 second composite silicon particles (radius 155 nm) (a total of 773 particles).
[0825] (2) Derivation of the number of primary particles (1) and primary particles (2) filled in the second hollow portion
[0826] The numbers of the primary particles (1) and the primary particles (2) filled in the second hollow part of the secondary particles in Examples 3 to 4 satisfy the condition of the following formula 3:
[0827] Formula 3:
[0828] (In the above formula 3, c1 and n3 are the radius and number of primary particles (1), c2 and n4 are the radius and number of primary particles (2), and d is the radius of the second hollow portion).
[0829] According to the above formula 3, the number of primary particles (1) with a radius c1 of 1020 nm and the number of primary particles (2) with a radius c2 of 1520 nm contained in the secondary particles of Examples 3 to 4 are shown in Table 2 below.
[0830] Table 2
[0831] distinguish d(nm) <![CDATA[c1,c2(nm)]]> <![CDATA[r1,r1’(nm)]]> <![CDATA[r2,r2'(nm)]]> <![CDATA[n3]]> <![CDATA[n4]]> <![CDATA[n3+n4]]> Example 3 3000 1020,1520 105,131 155,194 7 2 9 Example 4 5000 1020,1520 105,131 155,194 34 10 43
[0832] Referring to the results in Table 2, it can be seen that in the secondary particles of Examples 3 to 4 in which the radius of the second hollow portion is 3 μm and 5 μm, when 7 to 34 primary particles (1) with a radius a1 of 1020 nm and 2 to 10 primary particles (2) with a radius a2 of 1520 nm (a total of 9 to 43 primary particles) are filled, even if the nano-silicon particles expand by 2 times, the secondary particles (second hollow core) will not rupture or be damaged.
[0833] Comparative Example 1
[0834] Under an inert gas atmosphere, only the nano silicon particles (average radius (d50) 500 μm) of Example 1 were sintered at 900-1050° C. to prepare a sintered powder. Then, the sintered powder and a soft coating material (including pitch having an average particle size (d50) of 3-5 μm) were mixed and sintered at 850-975° C. to form a first coating layer (soft coating layer) to prepare an intermediate formed body (negative electrode active material), and the intermediate formed body was ground and classified.
[0835] The negative electrode active material comprises: a core, comprising nano silicon particles; and a first coating layer formed on the outer peripheral surface of the core (thickness 10-20nm, ISO 15184 standard pencil hardness B and density 1.5g / cm 3 of soft coating).
[0836] The negative electrode active material includes 25 to 80 weight percent of nano silicon particles and 20 to 75 weight percent of a first coating layer.
[0837] Comparative Example 2
[0838] A negative electrode active material was prepared in the same manner as in Example 1 except that only graphite was used as carbon particles.
[0839] The negative electrode active material comprises: a first hollow core (thickness 20-30 nm, ISO 15184 standard pencil hardness 4H-6H and density 1.8-2.3 g / cm 3 ), a first hollow portion is formed inside thereof; composite silicon particles and graphite are filled in the first hollow portion; and a second coating layer (thickness 10-20nm, ISO 15184 standard pencil hardness B and density 1.5g / cm 3 The first hollow core has an average diameter of 10 μm (radius (R) 5 μm). The graphite is spherical (average particle size (d50) 30 to 100 nm) and has a pencil hardness of B to 2H, a conductivity of 50 to 200 μΩ·m and a density of 0.5 to 1.5 cm according to ISO 15184 standard. 3 form.
[0840] The negative electrode active material includes 25 to 80 weight percent of composite silicon particles, 1 to 10 weight percent of graphite, 1 to 40 weight percent of a first hollow core, and 1 to 40 weight percent of a second coating layer.
[0841] Experimental example
[0842] (1) Determination of the diffraction angle (2θ) values of the (111) and (220) planes, the grain size of the (111) plane, the oxidation rate and the specific surface area of the composite silicon particles: The diffraction angle (2θ) values of the (111) and (220) planes, the grain size of the (111) plane, the oxidation rate and the specific surface area of the composite silicon particles in the negative electrode active materials of the embodiments and comparative examples were determined.
[0843] Specifically, the diffraction angle (2θ) values of the (111) and (220) planes of the composite silicon particles were measured using a measuring instrument (Malvern Panalytical, Empyrean). The composite silicon particles in the negative electrode active materials of the examples and comparative examples were measured and derived by using X-ray diffraction (XRD) spectra of CuKα rays with a wavelength of 1.54 nm.
[0844] In addition, when the composite silicon particles of the embodiment and the nano silicon particles of the comparative example were analyzed by X-ray diffraction of CuKα rays, the grain value was calculated by using the grain calculation value (K=9, sherrer equation) of the half-value width (FWHM) of the diffraction peak of the (111) plane. For the oxidation rate of the nano silicon particles, the oxygen ratio was measured using a measuring device (LECO, ONH 836 series), and the specific surface area was measured using a BET measuring device (Micromeritics, Tristar II 3920), and the results are shown in Table 3 below.
[0845] Table 3
[0846]
[0847] Referring to the results in Table 3, it can be seen that Examples 1 to 4 have lower oxidation degrees of the composite silicon particles than Comparative Example 1, and thus have excellent high output and long life characteristics.
[0848] In addition, in the X-ray diffraction (XRD) spectra of Examples 1 to 4, effective peaks appeared at 2θ values of approximately 27.5-28.5°, 47-48°, 55-56°, 68-69°, 75-77° and 88-90°, respectively. The effective peaks of the composite silicon particles represent the (111), (220), (311), (400), (331) and (442) crystal planes, respectively.
[0849] In addition, for Examples 1 to 3 and Comparative Example 1 in the Examples and Comparative Examples, the results of the measurement using X-ray diffraction (XRD) spectrum at the time point when the silicon carbide layer was formed on the surface of the nano-silicon particles when preparing the composite silicon particles (the Comparative Example was applied to the nano-silicon particles) are shown in the following Table 4. On the other hand, in the above Table 4, Comparative Example 1 is the result of applying only the nano-silicon particles (average radius (d50) 200nm).
[0850] Table 4
[0851]
[0852] Referring to Table 4 above, it can be seen that a silicon carbide layer is formed on the surface of the nano silicon particles in Examples 1 to 3. In addition, the (111) of the silicon carbide layer is the first peak (1st peak), and the peak intensity should be 2% or more compared with the second peak (2nd peak) of the nano silicon, which indicates that when the thickness of the silicon carbide layer is 1 to 10 nm, the average particle size of the silicon nano particles is in the region of 100 to 1000 nm, and the volume expansion of silicon according to the charge and discharge of the secondary battery can be controlled.
[0853] (2) XRD analysis of carbon particles: In the above Example 1, when graphene was prepared by milling graphite (preparation of carbon particles), the X-ray diffraction (XRD) spectrum and crystallinity change of graphite with milling time were measured. Specifically, the XRD peak change and crystallinity of the graphite (002) plane with mechanical milling time were analyzed for graphite, and the results are shown in Figure 5 And Table 5.
[0854] The assay was performed using a measurement device (Malvern Panalytical, Empyrean). The X-ray diffraction (XRD) spectrum of CuKα rays with a wavelength of 1.54 nm was used to measure and derive the diffraction angle (2θ) value and crystallinity (unit (au)) of the graphite of Example 1 along with the milling time.
[0855] Table 5
[0856]
[0857] Figure 5 Part (a) is a diagram showing the change in XRD peaks of Example 1 with graphite milling time, Figure 5 Part (b) is a graph showing the change in XRD crystallinity of Example 1 with graphite milling time.
[0858] The measurement results show that the diffraction angle (2θ) value on the graphene (002) plane of Example 1 has a maximum peak at 25-28°, and the diffraction angle (2θ) value on the (101) plane has a maximum peak at 42-47°.
[0859] Refer to the above Figure 5 The results show that in the graphene prepared in Example 1, when using 1. In the X-ray diffraction spectrum of CuKα rays, when milling for more than 60 minutes, the maximum peak intensity of the (002) plane / the maximum peak intensity of the (101) plane was measured to be more than 50 (152.13). In addition, in Example 1, it can be seen that when the graphite is mechanically milled, the XRD peak and crystallinity increase until 60 minutes, but when it exceeds 80 minutes, the crystallinity decreases relatively. It can be seen that this is the result of the increase in crystallinity due to the formation of graphene when the graphite is milled for 60 minutes.
[0860] Figure 6 Part (a) is a diagram showing the change in the XRD peak of the graphite (002) crystal plane with milling time in Example 1, Figure 6 Part (b) is a graph showing the change in the XRD peak of the graphite (101) crystal plane according to Example 1 with the milling time.
[0861] Refer to the above Figure 6 The results show that the peak of the graphite (002) crystal plane of Example 1 increases and the peak of the (101) crystal plane decreases with the milling time, thereby, the layers constituting the graphite are separated by milling to form graphene.
[0862] (3) Raman analysis of carbon particles: Raman analysis was performed on the graphene produced in Example 1, and the results are shown in Table 6. The Raman analysis was performed using a DXR Raman spectroscope from Thermo Scientific, and the measurement was performed at a laser wavelength of 532 nm.
[0863] On the other hand, the graphene formed in Example 1 has a 1D band at 2600-2800 cm-1 measured by a 532 nm excitation continuous wave (CW) laser in the Raman spectrum. -1 Peaks appear, 1G band at 1560~1600cm -1 Peaks appear, 2D band at 2680~2725cm -1 Peaks appear in the wavenumber range.
[0864] Table 6
[0865]
[0866] Referring to the results in Table 6 above, the graphene of Example 1 has a 1D band peak intensity (I 1D / I 1G ) satisfies 0.65 or less, and the 2D band peak intensity (I 2D / I 1G ) satisfies 0.35 to 0.65, and therefore it can be seen that the excellent durability of graphene and the excellent electrical conductivity can ensure the high capacity and high output characteristics of the negative electrode active material.
[0867] (4) XRD analysis of negative electrode active material: The measurement equipment (Malvern Panalytical, Empyrean) of Experimental Example (2) was used to analyze the negative electrode active material. The X-ray diffraction (XRD) spectrum of CuKα rays with a wavelength of 200 nm was used. In the negative electrode active materials of the embodiments and comparative examples, the maximum peak intensity of the (002) crystal plane of graphene (graphite in Comparative Example 2), the first peak intensity of the (111) crystal plane of the composite silicon particles, and the second peak intensity on the (220) crystal plane were measured for Examples 1 to 2 and Comparative Example 2. The results are shown in Table 7 below.
[0868] Table 7
[0869]
[0870] Referring to the results in Table 7 above, it can be seen that in Examples 1 to 2, the maximum peak intensity of the (002) surface of the graphite / the first peak intensity of the (111) surface of the composite silicon particles satisfies the conditions of 1.5 to 2.2, and the maximum peak intensity of the (002) surface of the graphite / the second peak intensity on the (220) surface of the composite silicon particles satisfies the conditions of 3.5 to 4.5, which can minimize the resistance of the negative electrode active material, have excellent conductivity and high output characteristics, prevent capacity reduction, and have excellent long life characteristics.
[0871] (5) Electrochemical evaluation (1)
[0872] (5-1) Preparation of lithium-ion battery (semi-coin cell): CR2032 semi-coin cell was prepared using the negative electrode active materials of Examples 1 to 4 and Comparative Examples 1 and 3. Specifically, 96.99 wt % of the negative electrode active materials of the Examples and Comparative Examples, 0.11 wt % of conductive materials (Oscial, Tuball, graphene carbon nanotubes), 1.65 wt % of carboxymethyl cellulose (CMC) and 1.25 wt % of styrene-butadiene rubber (SBR) were mixed to prepare a mixture. Next, 10.1 wt % of the prepared mixture and 89.9 wt % of commercial natural graphite with a capacity of 364 mAh / g were mixed to prepare a negative electrode slurry with a capacity of about 450 mAh / g. Then, the prepared slurry was coated / dried on a negative electrode current collector, and then rolled to prepare a negative electrode. The loading amount of the negative electrode is 6.5±0.5 mg / cm 2 , the electrode density is 1.60~1.65g / cc.
[0873] As the opposite pole of the prepared negative electrode, a lithium metal positive electrode (thickness 300 μm, MTI), an electrolyte and a separation membrane (including polypropylene and polyethylene) were used to prepare a CR2032 half coin battery in a conventional manner. 1M LiPF6 was dissolved in a mixed solvent of ethyl methyl carbonate (EMC) and ethylene carbonate (EC) (EMC and EC = 5:5 volume ratio), and then vinylene carbonate (VC) (containing 99.5 wt% of the mixed solvent and 0.5 wt% of vinylene carbonate) was added to prepare the electrolyte.
[0874] On the other hand, an evaluation plate was prepared in Comparative Example 3. The plate composition used 75 wt % of the negative electrode active material of Comparative Example 1, 2 wt % of the conductive material (carbon black), and 23 wt % of polyacrylic acid (PAA), and the electrode density was set to 1.0 g / cc.
[0875] (5-2) Evaluation of charge and discharge characteristics: The half coin cell prepared in (5-1) was aged at room temperature (25°C) for more than 20 hours and then subjected to electrochemical evaluation. The reference capacity of the negative electrode active material of the electrode plate was 450mAh / g, and the measurement temperature was 45°C. One cycle of chemical conversion process was carried out in the working voltage range of 0.005V to 1.5V, and the current during charge / discharge was measured as 0.1C in one cycle. Then, after two cycles based on the 0.2C capacity, a current of 0.5C was applied during charge / discharge based on the 0.2C capacity of the two cycles, and 50 cycle life evaluations were measured. At this time, the charge cut-off current was set to 0.005C, and the discharge cut-off voltage was set to 1.0V.
[0876] Through the electrochemical evaluation, the capacity (mAh / g) of the negative electrode of the embodiment and comparative example, the capacity (mAh / g) of the negative electrode plate, the charge / discharge efficiency (%) and the capacity retention rate, the life (%) were evaluated by evaluation, and the results are shown in Table 8 below.
[0877] (5-3) Evaluation of expansion characteristics: For the half-coin cells of the examples and comparative examples prepared in (5-1), the expansion rate of the negative electrode active material according to charge and discharge was evaluated. The expansion rate evaluation was performed based on the initial electrode thickness of the negative electrode of the half-coin cell. The half-coin cell was charged / discharged at a current of 0.5C for 50 cycles, and then charged at a current of 0.5C. Next, the thickness of the negative electrode was measured, and the thickness increase rate based on the initial negative electrode thickness was measured, and the results are shown in Table 7.
[0878] The thickness was measured by disassembling the coin cell after the cycle was completed, and using a DMC solvent to fully clean foreign matter on the electrode surface including salt, and then measuring using a measuring device (micrometer).
[0879] Table 8
[0880]
[0881] Referring to the results in Table 8, it can be seen that Examples 1 to 4 have excellent charge and discharge efficiency and excellent long life characteristics compared to Comparative Examples 1 and 3. In addition, the volume change of the negative electrode active material during charge and discharge of Examples 1 to 4 is lower than that of Comparative Examples 1 and 3, which shows that the rupture and destruction of the negative electrode active material during lithium ion insertion / extraction reactions can be prevented, and the capacity reduction is minimized, thereby having excellent long life characteristics.
[0882] (6) Electrochemical evaluation (2)
[0883] (6-1) Preparation of lithium secondary battery (1.0Ah pouch-type full battery): A pouch-type full battery was prepared using the negative electrode active materials of the embodiments and comparative examples. Specifically, 96.1 to 96.99% by weight of the negative electrode active materials of the embodiments 1 to 4 and comparative example 1, 0.11 to 1% by weight of the conductive material (Oscial, Tuball, graphene carbon nanotube or carbon black), 1.65% by weight of carboxymethyl cellulose (CMC) and 1.25% by weight of styrene-butadiene rubber (SBR) were used to prepare a mixture. Next, 10.1% by weight of the prepared mixture and 89.9% by weight of commercial natural graphite with a capacity of 364 mAh / g were mixed to prepare a negative electrode slurry with a capacity of about 550 mAh / g. Next, after coating / drying the prepared slurry on the negative electrode collector, rolling was performed to prepare the negative electrode. The loading amount of the negative electrode is 6.5±0.5 mg / cm 2 , the electrode density is 1.55-1.60 g / cc. Specifically, Examples 1-2 and Comparative Examples 1 and 3 each use 1 wt% of carbon black as a conductive material, and Examples 3-4 use 0.11 wt% of the carbon nanotubes as a conductive material.
[0884] Next, a positive electrode (NCM811) was used as the opposite electrode to the prepared negative electrode, and a pouch cell with a capacity of 1.0 Ah was prepared using an electrolyte and a separator (including polypropylene and polyethylene) in a conventional manner.
[0885] After dissolving 1M LiPF6 in a mixed solvent of ethyl methyl carbonate (EMC) and ethylene carbonate (EC) (EMC and EC=5:5 volume ratio), vinylene carbonate (VC) and fluoroethylene carbonate (FEC) (containing 96.5 wt% of the mixed solvent, 0.5 wt% of vinylene carbonate and 3 wt% of fluoroethylene carbonate) were added to prepare the electrolyte.
[0886] (4-2) Evaluation of charge and discharge characteristics: After the full battery prepared in (6-1) was aged at room temperature (25°C) for more than 20 hours, an electrochemical evaluation was performed at room temperature. Specifically, the full battery of the embodiment and the comparative example was subjected to a chemical conversion process of 0.1C charge / 0.1C discharge in the operating voltage range of 2.75V to 4.25V for one cycle. The current during charging was measured at 0.1C in one cycle and the cut-off current was measured at 0.005C. Next, based on the standard process of 0.2C charging and 0.01C / 0.1C discharge cut-off, after two cycles, based on the 0.2C discharge capacity of the two cycles, a charging current of 0.5C / cut-off 0.02C was applied during charging, and 500 cycle life (capacity retention rate) was measured under the conditions of 1.0C / 4.2V cutoff, and the results are shown in Table 9 below.
[0887] Table 9
[0888]
[0889] Referring to the results in Table 9, the charge and discharge efficiency and long life characteristics of the full batteries of Examples 1 to 4 are superior to those of Comparative Example 1.
[0890] So far, the present invention has been viewed with the embodiments as the center. It will be appreciated by those skilled in the art that the present invention can be implemented in a modified form without departing from the essential characteristics of the present invention. Therefore, the disclosed embodiments should be considered from an illustrative perspective, rather than a restrictive perspective. The scope of the present invention appears in the scope of the invention claims rather than the above description, and it should be interpreted that all differences falling within the scope equivalent thereto are included in the present invention.
Claims
1. A negative electrode active material, wherein: include: A first hollow core having a first hollow portion formed therein; Composite silicon particles, filled in the first hollow portion, and comprising nano silicon particles having a first coating layer formed on the surface; Carbon particles filled in the first hollow part; as well as a second coating layer formed on the outer peripheral surface of the first hollow core, The carbon particles include graphene and graphite, The first coating layer includes a middle coating layer, The second coating layer includes one or more of a hard coating layer, a middle coating layer and a soft coating layer, The hardness of the hard coating layer is higher than that of the middle coating layer, and the hardness of the middle coating layer is higher than that of the soft coating layer. The first hollow core and the second coating layer have different hardnesses.
2. A negative electrode active material, wherein: include: Primary particles, including a first hollow core having a first hollow portion, and composite silicon particles and carbon particles respectively filled in the first hollow portion; as well as The secondary particle includes a second hollow core having a second hollow portion and one or more primary particles filled in the second hollow portion. The composite silicon particles include nano silicon particles having a first coating layer formed on the surface. The carbon particles include graphene and graphite, the first coating layer includes a middle coating layer, The first hollow core and the second hollow core have different hardnesses.
3. The negative electrode active material according to any one of claims 1 and 2, wherein The average sizes of the graphene and graphite are 10 to 5000 nm respectively.
4. The negative electrode active material according to any one of claims 1 and 2, wherein The graphene comprises a layer structure of 1 to 10 layers, The maximum peak intensity of the graphene (002) plane / the maximum peak intensity of the graphene (101) plane in an X-ray diffraction spectrum is 50 or more.
5. The negative electrode active material according to any one of claims 1 and 2, wherein The D band peak intensity of the graphene relative to the G band peak intensity in the Raman spectrum (I D / I G ) is less than 0.
65.
6. The negative electrode active material according to claim 5, wherein The 2D band peak intensity (I 2D / I G ) is 0.35~0.
65.
7. The negative electrode active material according to any one of claims 1 and 2, wherein The 2D band of the graphene in the Raman spectrum is between 2680 and 2725 cm -1 There is a peak in the wavenumber range.
8. The negative electrode active material according to any one of claims 1 and 2, wherein In the X-ray diffraction spectrum of the negative electrode active material, the maximum peak intensity of the (002) plane of the graphite / the first peak intensity of the (111) plane of the composite silicon particles is 1.5 to 2.
2.
9. The negative electrode active material according to any one of claims 1 and 2, wherein In the X-ray diffraction spectrum of the negative electrode active material, the maximum peak intensity of the (002) plane of the graphite / the second peak intensity of the (220) plane of the composite silicon particles is 3.5 to 4.
5.
10. The negative electrode active material according to any one of claims 1 and 2, wherein The number (n) of composite silicon particles filled in the first hollow portion satisfies the condition of the following formula 1, Formula 1: (In the above formula 1, d is the relative diameter of the expanded composite silicon particle derived from the following formula 1-1, and q is the relative diameter of the expanded composite silicon particle at the center of the first hollow portion derived from the following formula 1-2) Formula 1-1: d = r' / R (In the above formula 1-1, R is the radius of the first hollow portion, and r' is the radius of the expanded composite silicon particle, r'=1.2599*a+b (a is the radius of the composite silicon particle, b is the thickness of the first coating layer) Formula 1-2: q = 1-2*d (In the above formula 1-2, the d is as defined above).
11. The negative electrode active material according to any one of claims 1 and 2, wherein The negative electrode active material includes first composite silicon particles and second composite silicon particles with radii r1 and r2, respectively. The number of particles (n1 and n2) of the first composite silicon and the second composite silicon filled in the first hollow portion satisfies the condition of the following formula 2, Formula 2: (In the above formula 2, r1' and r2' are the radii of the first expanded composite silicon particle and the second expanded composite silicon particle, respectively, and R is the radius of the first hollow portion, The r1' and r2' are 1.2599*a1+b1 and 1.2599*a2+b2 respectively (the a1 and b1 are the radius of the first nano-silicon particle and the thickness of the first coating layer, and the a2 and b2 are the radius of the second nano-silicon particle and the thickness of the first coating layer).
12. The negative electrode active material according to claim 2, wherein The secondary particles include primary particles (1) and primary particles (2) having radii c1 and c2, respectively. The numbers of the primary particles (1) and the primary particles (2) filled in the second hollow portion satisfy the condition of the following formula 3, Formula 3: (In the above formula 3, c1 and n3 are the radius and number of primary particles (1), c2 and n4 are the radius and number of primary particles (2), and d is the radius of the second hollow portion).
13. The negative electrode active material according to any one of claims 1 and 2, wherein The first coating layer further includes a silicon carbide layer formed between the nano-silicon particles and the middle coating layer.
14. The negative electrode active material according to any one of claims 1 and 2, wherein The negative electrode active material has an average particle size of more than 1.5 μm and less than 50 μm.
15. The negative electrode active material according to claim 1, wherein The average diameter of the first hollow part is 1.5 to 20 μm, and the average particle size of the composite silicon particles is 50 to 1500 nm. The number of composite silicon particles filled in the first hollow portion is 5 to 12,000.
16. The negative electrode active material according to claim 1, wherein The particle density of the negative electrode active material is 1 to 3 g / cm 3 , the thickness of the first hollow core is 5 to 300 nm, The thickness of the first coating layer is 3 to 110 nm. The thickness of the second coating layer is 5-100 nm.
17. The negative electrode active material according to claim 1, wherein The hard coating layer has a pencil hardness of 4H or more and a density of more than 1.8 g / cm 3 , The pencil hardness of the middle coating layer is greater than 2H and less than 4H, and the density is greater than 1.5 g / cm 3 And 1.8g / cm 3 the following, The pencil hardness of the soft coating layer is less than 2H and the density is 1.5 g / cm 3 the following.
18. The negative electrode active material according to claim 1, wherein The negative electrode active material includes 25 to 80 weight percent of composite silicon particles, 1 to 15 weight percent of carbon particles, 1 to 40 weight percent of a first hollow core, and 1 to 40 weight percent of a second coating layer.
19. A method for preparing a negative electrode active material, wherein: The method comprises: The step of preparing composite silicon particles; A step of preparing a primary dry powder by drying a mixed slurry comprising the composite silicon particles, carbon particles and a solvent; A step of preparing a first intermediate using the primary dry powder and a first coating material; and a step of forming a second coating layer on the outer peripheral surface of the first intermediate to prepare a second intermediate, The carbon particles include graphene and graphite, The first coating material includes one or more of a hard coating material, a medium coating material and a soft coating material. The second intermediate body includes: a first hollow core having a first hollow portion formed therein; composite silicon particles and carbon particles filled in the first hollow portion, and including nano silicon particles having a first coating layer formed on the surface; and a second coating layer formed on the outer peripheral surface of the first hollow core. The first coating layer includes a middle coating layer, The second coating layer includes one or more of a hard coating layer, a middle coating layer and a soft coating layer, The hardness of the hard coating layer is higher than that of the middle coating layer, and the hardness of the middle coating layer is higher than that of the soft coating layer. The first hollow core and the second coating layer have different hardnesses.
20. A method for preparing a negative electrode active material, wherein: The method comprises: The step of preparing composite silicon particles; A step of preparing a primary dry powder by drying a mixed slurry comprising the composite silicon particles, carbon particles, a first coating material and a solvent; The step of preparing a first mixture comprising the primary dry powder and a second coating material; and The step of preparing a first intermediate using the first mixture and a third coating material, The carbon particles include graphene and graphite, The first coating material and the second coating material respectively include one or more of a hard coating material and a soft coating material. The third coating material includes one or more of a hard coating material, a medium coating material and a soft coating material. The first intermediate includes: primary particles, including a first hollow core having a first hollow portion and composite silicon particles and carbon particles filled in the first hollow portion; and secondary particles, including a second hollow core having a second hollow portion and one or more primary particles filled in the second hollow portion. The composite silicon particles include nano silicon particles having a first coating layer formed on the surface. The first coating layer includes a middle coating layer, The first hollow core and the second hollow core have different hardnesses.
21. The method for preparing a negative electrode active material according to any one of claims 19 to 20, wherein: The steps of preparing the composite silicon particles include: A step of preparing a first composition comprising nano-silicon particles and carbon particles; The step of placing the first composition in a cavity, raising the temperature inside the cavity to 900-1100° C., and reducing the pressure to below normal pressure; a step of flowing hydrocarbon gas and buffer gas into the reduced pressure chamber to contact the first composition; and The step of gradually increasing the pressure inside the chamber to perform heat treatment while maintaining the elevated temperature, The carbon particles include graphene and graphite.
22. The method for preparing a negative electrode active material according to any one of claims 19 to 20, wherein: The method comprises the step of milling the graphite with the graphene.
23. A secondary battery, wherein: include: positive electrode; negative electrode; as well as an electrolyte formed between the positive electrode and the negative electrode, The negative electrode includes the negative electrode active material according to any one of claims 1 and 2.